Novel material with extremely durable intercalation of lithium and manufacturing method therefor

By depositing silicon on the porous carbon matrix to form a silicon-carbon composite material, the mechanical stress problem caused by lithium-mediated electrodes in lithium-ion batteries is solved, and higher battery performance and cycle life are achieved.

JP2025066766AActive Publication Date: 2025-04-23GROUP14 TECHNOLOGIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025007422
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2016-03-22
Filing Date
2025-01-20
Publication Date
2025-04-23
Estimated Expiration
2036-08-26

AI Technical Summary

Technical Problem

The mechanical stress caused by the expansion and contraction of lithium during the charging and discharging of lithium in the existing lithium-ion battery leads to instability in the solid-electrical boundary, affecting the cycle life and energy density of the battery.

Method used

Porous carbon with micropores, mesopores and/or macropores are used as the matrix, and silicon is deposited in pores of porous carbon by chemical vapor deposition (CVD) and other methods to form a silicon-carbon composite material, and can be further coated to reduce surface area.

Benefits of technology

The durability and energy density of lithium mediated electrodes in lithium-ion batteries are improved, the cycle life of the battery is extended, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066766000033
    Figure 2025066766000033
  • Figure 2025066766000034
    Figure 2025066766000034
  • Figure 2025066766000035
    Figure 2025066766000035
Patent Text Reader

Abstract

To provide composites of silicon and porous carbon scaffold materials, such as porous carbon material comprising micro-, meso- and / or macropores, and methods for manufacturing the same.SOLUTION: A composite comprises a porous carbon scaffold and silicon. The composite comprises silicon of 15 to 85% by weight and a nitrogen-inaccessible volume ranging from 0.05 to 0.5 cm3 / g, and the composite comprises a plurality of particles having a particle skeletal density ranging from 1.5 to 2.2 g / cm3, as measured by helium pycnometry.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (Statement of Government Interest) This invention was made in part with Government support under Award No. DE-EE0007312 awarded by the Department of Energy, Office of Energy Efficiency and Renewable Energy. The United States Government has certain rights in this invention.

[0002] (Technical field) The present invention generally relates to novel materials that exhibit extremely durable intercalation of lithium, their methods of manufacture, and their use, such as for energy storage applications. The novel materials include a porous scaffold, such as carbon, that exhibits a pore volume that includes micropores, mesopores, and / or macropores, said volume being impregnated with silicon, and in some embodiments, the impregnated silicon is of nano-dimension and / or nano-characteristics. The silicon-impregnated porous scaffold can be further coated, for example, with carbon or conductive polymer, to reduce the remaining surface area. Such silicon-impregnated carbon materials and carbon- or conductive polymer-coated silicon-impregnated carbon materials exhibit remarkable durability with respect to intercalation of lithium. Thus, the disclosed materials have utility, alone or in combination with other materials, for example, combined with carbon particles, binders, or other components to provide compositions of matter for energy storage applications. Energy storage applications include the use of the materials herein as electrode materials, particularly as anode (positive electrode) materials, for lithium ion batteries and related energy storage devices using lithium or lithium ions, such as lithium-air batteries. In certain embodiments, the materials disclosed herein have utility as anode materials for energy storage devices, such as lithium ion batteries and related energy storage devices using lithium or lithium ions. Accordingly, the present invention additionally relates to compositions and devices containing such materials, as well as methods related thereto. [Background technology]

[0003] Lithium-based electrical storage devices have the potential to replace currently used devices in any number of applications. For example, current lead-acid batteries are not suitable for next generation all-electric and hybrid electric vehicles due to irreversible stable sulfate formation during discharge. Lithium-ion batteries are a viable alternative to currently used lead-based systems due to their capabilities, as well as other considerations. Carbon is one of the raw materials used in both lithium secondary batteries and hybrid lithium-ion capacitors (LICs). Carbon anodes typically store lithium between layered graphite sheets by a mechanism called intercalation. Conventional lithium-ion batteries are composed of graphitic carbon anodes and metal oxide cathodes. However, such graphitic acid anodes typically suffer from low power performance and limited capacity.

[0004] Silicon, tin, and other lithium alloyed electrochemical modifiers have also been proposed based on their ability to store very large amounts of lithium per unit weight. However, these materials are fundamentally limited by the substantial expansion that occurs when lithium is fully inserted. This expansion and contraction when lithium is removed results in electrodes with limited cycle life and low power. The solution to date has been to use very small amounts of alloyed electrochemical modifier in large carbon electrodes. However, this approach does not provide the desired increase in lithium capacity. To increase capacity, it is desirable to find a way to increase the alloyed electrochemical modifier content in the anode composition while retaining cycle stability. Many approaches have been utilized, including nanostructured alloyed electrochemical modifiers, blending the alloyed electrochemical modifier with carbon, or applying the alloyed electrochemical modifier to the carbon using vacuum or high temperature. However, none of these approaches have been proven to combine a scalable approach that results in the desired properties.

[0005] The aforementioned expansion associated with certain materials, such as silicon materials, upon lithium insertion is an important factor in the stability, i.e., cycle life, of said materials with respect to their application for energy storage and distribution, for example, for use in rechargeable batteries. Over many cycles, the capacity of said materials is subject to fading. This capacity loss can be precipitated by a variety of different mechanisms, one of the critical mechanisms being explained in relation to the formation of a solid / electrolyte interface (SEI) at the negative electrode, which competes with reversible lithium insertion. It is known in the art that SEI is an important component of the capacity loss, as a standard degradation mechanism that can be modeled over long periods of time based on short-term and high-temperature accelerated aging.

[0006] It has been described in the art that the SEI layer plays an important role in the safety, power capability, and cycle life of Li-ion batteries. It has also been described that the formation of a chemically and mechanically stable SEI layer is important for improving the cycle life of lithium-ion batteries. The SEI layer on silicon in the anode is formed due to the reduction of organic solvents and anions on the electrode surface during the charge-discharge cycle of the battery, with a substantial degree of formation occurring during the first cycle. In addition, the cycle efficiency of silicon-based anodes can be dramatically improved using certain electrolyte additives, such as vinylene carbonate, propylene carbonate, lithium difluorooxalate borate, and fluoroethylene carbonate, other substances known in the art, and combinations thereof. The SEI layer can include fluorinated carbon and silicon species in addition to the usual Li2CO3, alkyl Li carbonate (ROCO2Li) (lithium carboxylate), LiF, ROLi (lithium alkoxide), and polyethylene oxide found on graphite electrodes. The formation of the SEI on the negative electrode is an irreversible reaction that consumes cyclable Li-ions from the positive electrode that leads to most of the capacity loss observed in the first lithiation / delithiation cycle of secondary lithium-ion batteries. In addition to the capacity loss in the first cycle, the continued formation of this layer also increases the resistance to Li-ion diffusion (i.e., the internal impedance of the battery).

[0007] Repeated expansion and contraction of silicon-based anode materials leads to instabilities of the SEI, e.g., cracking and reformation, which simultaneously contribute to the degradation of the anode's capacity. For this reason, the art describes a variety of different silicon dimensions and geometries that are favorable to reduce the tendency for chemical and mechanical decomposition and avoid fracture during cycling in lithium-ion batteries. To this end, the art (RSC Advances, 2013, 3, 7398, "Critical Silicon-Anode Sizes to Avoid Lithiation-Induced Mechanical Failure in Lithium-Ion Batteries", Ma et al.) lists critical dimensions of 90 nm for nanoparticles, 70 nm for nanowires, and 33 nm for nanofilms. Below these dimensions (for each shape), silicon nanostructures remain intact upon lithiation. Another report in the art (DOI:10.1002 / anie.200906287, "Critical dimensions of silicon nanoanodes for lithium secondary batteries", Angewandte Chemie, Vol 49, Iss. 12, pp2146-2149, 2010, Kim et al.) describes that for well-dispersed silicon nanocrystals, an approximate size of 10 nm showed higher capacity retention compared to 5 nm or 20 nm sizes.

[0008] Additionally, the nanostructure is important to prevent shattering of the silicon during expansion and contraction as well as to maintain the amorphous structure throughout cycling. Shattering is recognized as a mechanical failure of silicon due to extreme strain gradients through the bulk structure. As silicon is lithiated, it expands in volume (up to 300%). Lithium ions move very slowly through solid silicon. During lithium insertion, silicon particles can hold a large amount of lithium near the surface and not in the center of the particle. The concentration gradient creates a non-uniform expansion through the cross section. The extreme surface volume expansion causes the silicon particles to tear away from the interior, resulting in cracks and fractures. Once the silicon shatters, the cell fails as there is no known way to restore performance.

[0009] Thus, for energy storage applications, the preferred silicon dimensions are less than 1 micron, preferably less than 800 nm, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 90 nm, preferably less than 70 nm, preferably less than 50 nm, preferably less than 33 nm, preferably less than 20 nm. In particular examples, the preferred silicon dimensions are between 5 and 20 nm. In particular examples, the preferred silicon dimensions are less than 90 nm for nanoparticles. In particular examples, the preferred silicon dimensions are less than 70 nm for nanowires. In particular examples, the preferred silicon dimensions are less than 33 nm for nanofilms.

[0010] Silicon particles of the above dimensions are generally referred to as nano-sized silicon particles. Particle size is typically described as Dv50, or silicon particle size at 50% volume distribution, as measured by various methods known in the art, such as by laser diffraction particle size techniques.

[0011] Alternatively, or in addition to silicon exhibiting primary particle dimensions within the above ranges, silicon particles can also exhibit nanofeatures. Silicon nanofeatures preferably have nanofeature dimensions less than 1 micron, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm. Silicon particles with the above characteristics are generally referred to as silicon particles with nanofeatures. Nanofeatures can be identified by various methods known in the art, for example, by scanning electron microscopes.

[0012] Current techniques for achieving nano-dimensional silicon are expensive and difficult to scale up. For example, the first accepted successful production of Si nanoclusters was reported by Heath and coworkers (Science 1992, 258, 1131; PE Batson, JR Heath, Phys. Rev. Lett. 1993, 71, 911) and involves the reduction of SiCl4 at high temperature and pressure in a bomb fitted within a heating mantle. In another example, a method utilizes SiCl4 reduction at room temperature under an inert atmosphere. However, the product obtained at room temperature did not fully crystallize and required further high temperature annealing. Similar solution syntheses have been reported using the reduction of silicon salts with LiAlH4 or alkylsilanes followed by low or high temperatures, however, all such methods produce broad particle size distributions or involve aggregation of nanoparticles. Furthermore, these approaches are not suitable for enabling commercial utility. The scalability and material yields are insufficient to enable their use in the manufacture of anodes for lithium secondary batteries.

[0013] Thus, there is a need for improved, readily scalable, inexpensive methods for producing porous silicon materials containing nano-sized particles and / or exhibiting nano-features, which can be combined with suitable hard carbon materials to produce desired electrochemical properties. The present invention fulfills this need and provides further related advantages. Summary of the Invention

[0014] (Brief summary) Generally speaking, the present invention relates to composite materials in which silicon is deposited within the pore volume of a porous scaffold material. The porous scaffold material can comprise a variety of different materials. In certain preferred embodiments, the porous scaffold material is a porous carbon material having micropores, mesopores, and / or macropores. Specifically, the porous carbon material provides pores in the range of 5-1000 nm, which are subsequently filled with silicon. Thus, the present disclosure relates to a method for making a composite material in which silicon is deposited within the pore volume of a porous scaffold material. The composites exhibit highly durable intercalation of lithium, thus providing optimized lithium storage and utilization properties. These novel composites can be used in a number of electrical energy storage devices, for example, as electrode materials in lithium-based electrical energy storage devices (e.g., lithium ion batteries). Electrodes comprising the novel composites disclosed herein exhibit high reversible capacity, high first cycle efficiency, high power performance, or any combination thereof. The inventors have discovered that such improved electrochemical performance is related to the dimensions of the silicon, the integrity of the silicon and carbon materials during cycling, the formation of a stable SEI layer, the physicochemical properties of the scaffold materials, such as the surface area and pore volume properties of the carbon scaffold, and other properties, as well as the techniques used to manufacture and combine these materials.

[0015] Thus, in one embodiment, the present disclosure provides for the preparation of a novel composite comprising a porous scaffold and silicon, the composite having durable lithium intercalation. For example, the preparation method may include the following steps: a) preparing a porous scaffold material, the porous scaffold material having a pore volume in the range of 5 to 1000 nm; b) impregnating the porous scaffold with silicon to obtain a silicon-impregnated carbon material; may have

[0016] Thus, in one embodiment, the present disclosure provides for the preparation of a novel composite comprising carbon and silicon having durable lithium intercalation. For example, the preparation method may include the following steps: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to form a silicon-impregnated carbon material. may have

[0017] Thus, in one embodiment, the present disclosure provides for the production of a novel composite having a layer of carbon surrounding a silicon impregnated carbon material, the composite having durable lithium intercalation. For example, the method of production may include the following steps: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to form a silicon-impregnated carbon material; and d) applying a conductive polymer around the silicon impregnated carbon material to obtain a silicon impregnated carbon material embedded within a conductive polymer network. may have

[0018] Thus, in one embodiment, the present disclosure provides for the production of a novel composite having a layer of conductive polymer surrounding a silicon impregnated carbon material, the composite having durable lithium intercalation. For example, the method of production may include the following steps: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to form a silicon-impregnated carbon material; and d) applying a carbon layer onto the silicon-impregnated carbon material to obtain a carbon-coated silicon-impregnated carbon material. e) applying a conductive polymer around the silicon impregnated carbon material to produce a carbon coated silicon impregnated carbon material embedded within a conductive polymer network. may have

[0019] In another embodiment, there is provided a composite comprising a porous carbon scaffold and silicon, The composite has 15-85% silicon by weight, and the composite has less than 10% micropores, more than 30% mesopores, more than 30% macropores, and less than 0.5 cm pores as determined by nitrogen adsorption (nitrogen sorption). 3 Composites are provided having pore structures with a total pore volume of less than 1 / g.

[0020] In another embodiment, there is provided a composite comprising a porous carbon scaffold and silicon, The composites have 15-85% silicon by weight and the porous carbon scaffold has less than 10% micropores, more than 30% mesopores, more than 30% macropores, and pores less than 0.5 cm2 as determined by nitrogen adsorption. 3 Composites are provided having pore structures with a total pore volume of less than 1 / g.

[0021] In another embodiment, there is provided a composite comprising a porous carbon scaffold and silicon, The composite has 35-65% silicon by weight, and the composite has less than 20% micropores, more than 60% mesopores, more than 30% macropores, and 0.1-0.5 cm pores as determined by nitrogen adsorption. 3 Composites are provided having a pore structure with a total pore volume of 1 / g.

[0022] In another embodiment, there is provided a composite comprising a porous carbon scaffold and silicon, The composite has 35-65% silicon by weight and the porous carbon scaffold has less than 20% micropores, more than 60% mesopores, more than 30% macropores, and 0.1-0.5 cm2 pores as determined by nitrogen adsorption. 3 Composites are provided having a pore structure with a total pore volume of 1 / g.

[0023] Thus, the present disclosure provides novel compositions as well as methods for their preparation, which materials exhibit extremely durable intercalation of lithium when incorporated into electrodes of lithium-based energy storage devices, in some embodiments, the lithium-based electrical energy storage device is a lithium-ion battery or a lithium-ion capacitor.

[0024] These and other aspects of the present invention will become apparent upon reference to the following detailed description, to which end various references are set forth herein that describe in more detail specific background information, procedures, compounds and / or compositions, each of which is incorporated herein in its entirety. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 shows a schematic of how composite particles can be achieved via microwaveable silicon deposition onto a microwave absorbing porous carbon scaffold. [Diagram 2] FIG. 2 shows the pore volume distribution of the microporous carbon scaffold and the silicon-containing composite derived therefrom. [Diagram 3] FIG. 3 shows the pore volume distribution of a mixed micro-, meso-, macro-porous carbon scaffold and silicon-containing composites derived therefrom. [Figure 4] FIG. 4 shows the pore volume distribution of macroporous carbon scaffolds and silicon-containing composites derived therefrom. [Diagram 5] FIG. 5 shows the pore volume distribution of the microporous carbon before and after CVD treatment to cap the micropores. [Figure 6] FIG. 6 shows the anode expansion versus gravimetric capacity data for bare carbon versus carbon composite nanosilicon. [Figure 7] FIG. 7 shows anode expansion versus gravimetric capacity data for sample carbon-silicon composites. [Figure 8] FIG. 8 shows anode expansion versus volumetric capacity data for sample carbon-silicon composites. [Figure 9] FIG. 9 shows full cell data in Wh / L for various sample graphites. [Figure 10] FIG. 10 shows the pore volume distribution of mixed micro- and mesoporous carbon scaffolds and silicon-containing composites derived therefrom. [Figure 11] FIG. 11 shows the capacity retention (solid lines) and coulombic efficiency (dashed lines) for silicon carbon composites fabricated from mixed micro- and mesoporous carbon scaffolds produced at different pyrolysis temperatures (PC). [Figure 12] FIG. 12 shows an illustration showing the effect of carbon coating on silicon carbon composites. The data shown are for uncoated (striped bars) and coated (solid bars) samples measured electrochemically in half cells. (12A) Average calculated silicon capacity (mAh / g), (12B) average observed composite capacity (mAh / g), (12C) average coulombic efficiency, and (12D) average capacity retention at cycle 20 are shown. [Figure 13] FIG. 13 shows the anode expansion versus volumetric capacity upon full lithiation of various carbon-silicon composites. [Figure 14] FIG. 14 shows the cycling stability of full cells of silicon carbon composites fabricated from porous carbon scaffolds of smaller (triangle) versus larger (diamond) dimensions. [Figure 15] FIG. 15 shows the cycling stability of full cells of silicon carbon composites fabricated from carbon-coated (triangles) versus non-carbon-coated (diamond) porous carbon scaffolds. [Figure 16] FIG. 16 shows the capacity retention of the C-coated silicon carbon composite of Example 29 for full cell and pouch cell cycling. [Figure 17]FIG. 17 shows the gravimetric capacity of the C-coated silicon carbon composite of Example 29 for full cell and pouch cell cycling. [Figure 18] FIG. 18 shows the extraction capacity at various cycle rates for the various materials of Example 30. [Figure 19] FIG. 19 shows the maximum percent capacity removed at various cycle rates for the various materials of Example 30. [Figure 20] FIG. 20 shows the cycling stability at various degrees of anode densification for the novel silicon carbon composite of Example 31. [Figure 21] FIG. 21 shows the cycling stability at various degrees of anode densification for the silicon oxide comparison of Example 31. [Figure 22] FIG. 22 shows the cycling stability of full cells of silicon carbon composites fabricated from carbon-coated versus non-carbon-coated porous carbon scaffolds in Example 35. [Diagram 23] FIG. 23 shows the cycling stability of the carbon coated silicon carbon composite full cell compared to graphite in a coin cell and full cell in Example 36. [Figure 24] FIG. 24 shows the anode differential voltage plot for the full cell cycling stability of the carbon coated silicon carbon composite compared to graphite in a full cell and coin cell in Example 36. [Diagram 25] FIG. 25 shows the cathode differential voltage plots for the full cell cycling stability of the carbon coated silicon carbon composite compared to graphite in a full cell, coin cell in Example 36. [Figure 26] FIG. 26 shows the particle expansion measurement of the silicon carbon composite in Example 39 by in situ TEM. [Figure 27] FIG. 27 shows the particle expansion measurement of the carbon coated silicon carbon composite in Example 39 by in situ TEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] (Detailed Description) In the following description, some specific details are described to provide an understanding of various embodiments. However, those skilled in the art will understand that the present invention can be practiced without these detailed descriptions. In other cases, known structures are not shown or details are described to avoid unnecessarily obscuring the description of the examples. Unless otherwise required by context, throughout the following specification and claims, the term "comprises" and variations thereof, such as "contains" and "includes", are open terms, i.e., are interpreted to have an inclusive meaning such as "including, but not limited to". Furthermore, the headings provided herein are for convenience only and do not describe the scope and meaning of the invention as described in the claims.

[0027] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or property described in connection with an embodiment is included in at least one embodiment. Thus, although the phrase "one embodiment" or "an embodiment" may appear in various places throughout this specification, they do not necessarily all relate to the same embodiment. Furthermore, particular features, structures, or properties may be combined in any suitable manner in one or more embodiments. As used in this specification and the appended claims, the singular forms "a," "an," and "the" include the plural unless expressly indicated otherwise. The term "or" is generally used in the sense of including "and / or" unless expressly indicated otherwise.

[0028] (definition) As used herein, and unless otherwise stated, the following terms have the meanings specified below.

[0029] "Energy storage material" refers to a material capable of storing an electric charge, for example in the form of a physically entrained electrolyte. The energy storage material can be charged and discharged. Examples of energy storage materials include, but are not limited to, carbon, e.g., activated carbon, silicon, sulfur, lithium, and combinations thereof. The energy storage material may be used in the form of particles, or a combination of inter- and / or intra-particle mixtures of particles. The energy storage particles may be assembled into electrodes using dry processing or aqueous or non-aqueous slurry processing, as described in the art.

[0030] "Carbon material" means a material or substance that consists essentially of carbon. Examples of carbon materials include, but are not limited to, activated carbon, pyrolytic carbon, hard carbon, graphite, and other allotropes of carbon.

[0031] "Impurity" or "impurity element" means a foreign entity (e.g., a chemical element) in a material that is different from the chemical composition of the source material. For example, an impurity in a carbon material means an element or combination of elements other than carbon that is present in the carbon material. The concentration of an impurity is typically expressed in parts per million (ppm).

[0032] A "TXRF impurity" is any impurity element detected by total X-ray fluorescence (TXRF). "Total TXRF impurity content" and "total TXRF impurity concentration" are both the sum of all TXRF impurities present in a sample (e.g., a polymer gel, a carbon material, a silicon material, or a composite material containing carbon and silicon).

[0033] "Ash" means the non-volatile inorganic matter remaining after exposure of a material to high decomposition temperatures, where the ash content of a carbonaceous material is calculated from the total PIXE impurity content as measured by proton induced X-ray analysis, assuming complete conversion of the non-volatile components to the expected combustion products (i.e., oxides).

[0034] "Polymer" means a macromolecule comprised of two or more structural repeating units.

[0035] "Synthetic polymer precursor material" or "polymer precursor" refers to a compound used in the preparation of synthetic polymers. Examples of polymer precursors that can be used in the preparation methods disclosed herein include, but are not limited to, aldehydes (i.e., HC(=O)R, where R is an organic group), such as methanal (formaldehyde); ethanal (acetaldehyde); propanal (propionaldehyde); butanal (butyraldehyde); glucose; benzaldehyde and cinnamaldehyde. Examples of other polymer precursors include, but are not limited to, phenolic compounds (e.g., phenol), and polyhydroxybenzenes (e.g., dihydroxybenzenes or trihydroxybenzenes), such as resorcinol (i.e., 1,3-dihydroxybenzene), catechol, hydroquinone, and phloroglucinol. Mixtures of two or more polyhydroxybenzenes are also understood within the meaning of polymer precursor.

[0036] The term "sol" refers to a colloidal suspension of precursor particles (eg, polymer precursors) and the term "gel" refers to a wetted three-dimensional porous network obtained by concentration or reaction of precursor particles.

[0037] "Polymer gel" refers to a gel in which the network components are polymers. Generally, polymer gels are wet (aqueous or non-aqueous) three-dimensional structures comprising polymers formed from synthetic or polymeric precursors.

[0038] "Sol-gel" refers to a subclass of polymer gels, where the polymers are colloidal suspensions forming a wetted three-dimensional porous network obtained by the reaction of polymer precursors.

[0039] "Polymer hydrogel" or "hydrogel" refers to a polymer gel or a subclass of gels in which the solvent for the synthetic precursors or monomers is water or a mixture of water and one or more water-miscible solvents.

[0040] "Acid" means any substance capable of lowering the pH of a solution. Acids include Arrhenius, Bronsted, and Lewis acids. "Solid acid" means a dry or granular compound that produces an acidic solution when dissolved in a solvent. The term "acidic" means having the properties of an acid.

[0041] "Base" means any substance capable of increasing the pH of a solution. Bases include Arrhenius, Bronsted, and Lewis bases. "Solid base" means a dry or granular compound that produces a basic solution when dissolved in a solvent. The term "basic" means having the properties of a base.

[0042] A "catalyst" is a substance that changes the rate of a chemical reaction. The catalyst is cyclically regenerated so that the catalyst periodically participates in the reaction. The present disclosure contemplates sodium-free catalysts. A catalyst used in preparing a polymer gel as disclosed herein is any compound that promotes the polymerization of a polymer precursor to produce a polymer gel. A "volatile catalyst" is a catalyst that tends to volatilize at or below atmospheric pressure. Examples of volatile catalysts include, but are not limited to, the following: ammonium salts, such as ammonium bicarbonate, ammonium carbonate, ammonium hydroxide, or combinations thereof.

[0043] "Carbonize", "pyrolyze", "carbonization" and "pyrolysis" respectively refer to the process of heating a carbon-containing material in an inert atmosphere (e.g., argon or nitrogen) or in a vacuum at a residence temperature that allows pyrolysis, whereby the material of interest recovered at the end of the process is primarily carbon. "Pyrolyzed" refers to a material or substance, e.g., a carbon material, that has been subjected to a pyrolysis process.

[0044] As used with respect to an electrode, "density" means the total density of the active material (e.g., carbon-silicon composite) and any optional binders, conductivity enhancers, etc. The density of an electrode does not include the mass or volume associated with the current collector associated with the electrode.

[0045] "Dwell temperature" refers to the temperature of the furnace during a portion of the process that is held (i.e., not increased or decreased) to maintain a relatively constant temperature. For example, pyrolysis dwell temperature refers to the relatively constant temperature of the furnace during pyrolysis, and activation dwell temperature refers to the relatively constant temperature of the furnace during activation.

[0046] A "pore" is a hole in a carbon material, such as activated carbon, pyrolyzed dried polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dried polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel, etc., or a depression or opening in their surface. A pore may be a single hole or may be connected to other holes through a continuous network within the structure.

[0047] "Pore structure" refers to the arrangement of internal pores within a carbon material (e.g., activated carbon material). Components of pore structure include pore size (pore diameter), pore volume, pore area, density, pore size distribution, and pore length. In general, the pore structure of activated carbon materials includes micropores and mesopores.

[0048] "Mesopores" generally refer to pores having a diameter of about 2 nanometers to about 50 nanometers, while "micropores" refer to pores having a diameter of less than about 2 nanometers. Mesoporous carbon materials contain more than 50% of the total pore volume in mesopores, and microporous carbon materials have more than 50% of the total pore volume in micropores. Pores larger than about 50 nanometers are referred to as "macropores."

[0049] "Surface area" means the total specific surface area of ​​a material, as can be measured by the BET method. Surface area is typically measured in m 2 The BET (Brunauer-Emmett-Teller) method is performed by measuring the amount of gas adsorbed (sorbed) onto a material using an inert gas, e.g., nitrogen, and is a method commonly used in the art to measure the accessible surface area of ​​a material.

[0050] As used herein with respect to mesopores and micropores, "connected" refers to the spatial location of such pores.

[0051] A "binder" is a material capable of holding carbon particles together, and the binder and carbon can be mixed together and then formed into a sheet, pellet, disk, or other shape. Non-limiting examples of binders include fluoropolymers such as PTFE (polytetrafluoroethylene, Teflon®), PFA (perfluoroalkoxy polymer resin, also known as Teflon®), FEP (fluorinated ethylene propylene, also known as Teflon®), ETFE (polyethylene tetrafluoroethylene, commercially available as Tefzel® and Fluon®), PVF (polyvinyl fluoride, commercially available as Tedlar®), ECTFE (polyethylene chlorotrifluoroethylene, commercially available as Halar®), PVDF (polyvinylidene fluoride, commercially available as Kynar®), PCTFE (polychlorotrifluoroethylene, commercially available as Kel-F and CTFE), trifluoroethanol, and combinations thereof.

[0052] "Composite material" means a composition that includes multiple (ie, two or more) different chemical species within the same particle, for example, a particle that includes both a porous carbon material and a silicon material.

[0053] "Allotrope" means a substance that can exist in different forms. C60, graphene, diamond, hard carbon, soft carbon, graphite, carbon nanotubes are all examples of carbon allotropes. "Hard carbon" means a non-graphitized carbon material. At high temperatures (e.g., >1500°C), hard carbons remain substantially amorphous, while "soft" carbons undergo crystallization and become graphitized.

[0054] "Lithium uptake" refers to the ability of the carbon to intercalate, absorb and store lithium, measured as the ratio of the maximum number of lithium atoms to six carbon atoms.

[0055] "SEI" means the solvent / electrolyte interface, as known in the art.

[0056] "Young's modulus", also known as tensile modulus or elastic modulus, is a mechanical property of linear elastic solids. It measures the force (per unit area) required to stretch (compress) a material.

[0057] "Bulk modulus" describes bulk elasticity, the tendency of an object to deform in all directions when loaded equally in all directions. It is defined as the volume stress to volume strain and is the reciprocal of the compressibility. Bulk modulus is the extension of Young's modulus into three dimensions.

[0058] "Coulombic efficiency" means the amount of capacitive discharge achieved as a result of lithium removal (lithium extraction) from the anode of a lithium-ion based energy storage device divided by the amount of capacitive charge or uptake achieved as a result of lithium insertion. Coulombic efficiency is reported as a percentage or as a fraction, e.g., 99% = (0.99).

[0059] "Nano-dimensional" means that the material (e.g., silicon) has at least one dimension on the order of nanometers, e.g., at least one dimension less than 1 micron. For energy storage applications, preferred silicon dimensions are less than 1 micron, preferably less than 800 nm, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm. Silicon particles of the above dimensions are generally referred to as nano-dimensional silicon particles. Particle size is typically described as having a Dv50, i.e., silicon particle size at 50% volume distribution, as measured by various methods known in the art, such as by laser diffraction particle size techniques.

[0060] Alternatively or in addition to containing silicon exhibiting primary particle dimensions within the above ranges, the silicon particles may also exhibit nanofeatures. Nanofeatures refer to features such as pores, having dimensions on the order of less than 1 micron. A "nanofeatured" material is one that has nanofeatures. Silicon nanofeatures preferably include nanofeature dimensions less than 1 micron, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 μm, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm. Silicon particles with the above characteristics are generally referred to as silicon particles with nanofeatures. Nanofeatures can be identified by various methods known in the art, for example by scanning electron microscopes.

[0061] A. Porous scaffold materials For the purpose of the present invention, a porous scaffold is required, into which silicon is impregnated. In this context, the porous scaffold can be of various materials. In a preferred embodiment, the porous scaffold material mainly comprises carbon, e.g., hard carbon. Other allotropes of carbon can also be used, e.g., graphite, amorphous carbon, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene and / or carbon fibers. The introduction of porosity into the carbon material can be achieved by various means. For example, porosity in the carbon material can be achieved by adjusting the polymer precursors and / or processing conditions to create said porous carbon material, which will be described in detail in the next section.

[0062] In other embodiments, the porous scaffold can include polymeric materials. For this purpose, a wide variety of polymers have utility, including but not limited to inorganic polymers, organic polymers, and addition polymers. Examples of inorganic polymers include, but are not limited to, silicon-silicon homochain polymers, such as polysilanes, silicon carbides, polygermanium, and polystannanes. Further examples of inorganic polymers include, but are not limited to, heterochain polymers, such as polysiloxanes, polyborazylenes, polydimethylsiloxanes (PDMS), polymethylhydrosiloxanes (PMHS), and polydiphenylsiloxanes, polysilazanes, such as perhydridopolysilazanes (PHPS), polyphosphazenes, poly(dichlorophosphazenes), polyphosphates, polythiazyls, and polysulfides. Examples of organic polymers include, but are not limited to, low density polyethylene (LDPE), high density polyethylene (HDPE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), nylon, nylon-6, nylon-6,6, Teflon (polytetrafluoroethylene), thermoplastic polyurethane (TPU), polyurea, poly(lactide), poly(glycolide) and combinations thereof, phenolic resins, polyamides, polyaramids, polyethylene terephthalate, polychloroprene, polyacrylonitrile, polyaniline, polyimide, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PDOT:PSS), and others. Organic polymers may be synthetic or natural. In some embodiments, the polymer is a polysaccharide, such as starch, cellulose, cellobiose, amylose, amyl pectin, gum arabic, lignin. In some embodiments, the polysaccharides are derived from the caramelization of mono- or oligosaccharides, such as fructose, glucose, sucrose, maltose, raffinose.

[0063] Concomitant with the myriad of different polymers that can potentially provide a porous substrate, various processing techniques are understood to achieve said porosity. In this context, the general methods for imparting porosity to various materials are numerous, as known in the art, including but not limited to emulsification, micelle formation, gasification, dissolution followed by solvent removal (e.g., freeze-drying), axial pressing and sintering, gravity sintering, powder rolling and sintering, isostatic pressing and sintering, metal spraying, metal coating and sintering, metal injection molding and sintering, etc. It is also understood that other techniques for creating porous polymeric materials create porous gels, such as freeze-dried gels, aerogels.

[0064] In certain embodiments, the porous scaffolding material comprises a porous ceramic material. In certain embodiments, the porous scaffolding material comprises a porous ceramic foam. In this context, as known in the art, common methods for imparting porosity to ceramic materials are varied and include, but are not limited to, creating porosity. Common methods and materials suitable for constructing porous ceramics include, but are not limited to, porous aluminum oxide, porous zirconia-reinforced alumina, porous partially stabilized zirconia, porous alumina, porous sintered silicon carbide, sintered silicon nitride, porous cordierite, porous zirconium oxide, clay-bonded silicon carbide, and the like.

[0065] In certain embodiments, the porous scaffold comprises porous silica or other silicon materials that contain oxygen. The preparation of silicon gels, including sols and gels, and other porous silica materials is known in the art.

[0066] In certain embodiments, the porous material comprises a porous metal. Suitable metals in this regard include, but are not limited to, porous aluminum, porous steel, porous nickel, porous Inconnel®, porous Hastelloy®, porous titanium, porous copper, porous brass, porous gold, porous silver, porous germanium, and other metals that can be formed into porous structures, as known in the art. In some embodiments, the porous scaffold material comprises a porous metal foam. Types of metals and associated manufacturing methods are known in the art. Such methods include, but are not limited to, casting (including foaming, infiltration, and lost foam casting), vapor deposition (chemical and physical), gas eutectic formation, and powder metallurgy techniques (e.g., powder sintering, compaction in the presence of foaming agents, and fiber metallurgy techniques).

[0067] B. Porous Carbon Polymer Methods for preparing porous carbon materials from polymer precursors are known in the art. For example, methods for preparing carbon materials are described in U.S. Patent Nos. 7,723,262, 8,293,818, 8,404,384, 8,654,507, 8,916,296, 9,269,502, U.S. Patent Application Nos. 12 / 965,709 and 13 / 486,731, and International Patent Application No. PCT / US2014 / 029106, the entire disclosures of which are incorporated herein by reference in their entirety for all purposes. Thus, in one embodiment, the present disclosure provides a method for preparing any of the above-mentioned carbon materials or polymer gels. The carbon material can be synthesized by pyrolysis of a single precursor, for example, a sugar material, specifically, sucrose, fructose, glucose, dextrin, maltodextrin, starch, amylopectin, amylose, lignin, gum arabic, other sugars known in the art, and combinations thereof. Alternatively, the carbon material can be synthesized by pyrolysis of a composite resin. For example, a polymer precursor, specifically, phenol, resorcinol, bisphenol A, urea, melamine, and other suitable compounds known in the art, and combinations thereof, can be formed by a sol-gel process using crosslinkers such as formaldehyde, furfural, other crosslinkers known in the art, and combinations thereof, in a suitable solvent such as water, ethanol, methanol, and other solvents known in the art. The resin can be acid or basic and can include a catalyst. The catalyst can be volatile or non-volatile. The pyrolysis temperature and residence time can be varied as known in the art.

[0068] In some embodiments, the method comprises producing a polymer gel by a sol-gel process, a condensation process or a crosslinking process, including a monomer precursor and a crosslinker, two pre-existing polymers and a crosslinker, or a single polymer and a crosslinker, and then pyrolyzing the polymer gel. The polymer gel may be dried (e.g., freeze-dried) prior to pyrolysis, although drying is not required.

[0069] In some embodiments, the polymer gel is freeze dried or lypophilized to leave a porosity of the desired range and nature, e.g., to have macroporosity. Without being bound by theory, this includes porosity in freeze-dried gels or cryogels. In some embodiments, the freeze-dried gel is first reduced in size to a monolithic material into particles, which are frozen very quickly and dried under vacuum to obtain a cryogel. Particle size reduction can be achieved by various methods known in the art, such as grinding, milling, grinding by various means, etc. Such methods are suitable for producing particles having a particle volume average diameter (Dv50) of less than 10 cm, e.g., less than 5 cm, e.g., less than 2 cm, e.g., less than 1 cm, e.g., less than 5 mm, e.g., less than 1 mm, e.g., less than 100 microns, e.g., less than 10 microns. Very rapid freezing can be achieved by exposing the particles to a very cold liquid, e.g., liquid nitrogen, or by other techniques known in the art for rapid freezing. Without wishing to be bound by theory, extremely rapid freezing creates a large degree of ice surface area, which upon sublimation under vacuum as known in the art, results in a large surface area in the freeze-dried polymer or cryogel.

[0070] The sol-gel process offers considerable flexibility for the incorporation of various electrochemical modifiers, which can be incorporated at any number of stages. In one embodiment, a method is provided for preparing a polymer gel containing an electrochemical modifier. In another embodiment, a method is provided for preparing a pyrolyzed polymer gel. Details of the variable process parameters of various embodiments of the disclosed method are described below.

[0071] The target carbon properties can be derived from a variety of polymer chemistries, so long as the polymerization reaction produces a resin / polymer with the required carbon backbone. Different polymer families include novolacs, resoles, acrylates, styrenes, urethanes, rubbers (neoprene, styrene-butadiene, etc.), nylons, etc. Preparation of any of these polymer resins can be done via many different processes including sol-gel, emulsion / suspension, solid state, solution state, melt state, etc. for any polymerization and crosslinking steps.

[0072] The polymer gel can be prepared by a sol-gel process. For example, the polymer gel can be prepared by copolymerizing one or more polymer precursors in a suitable solvent. In one embodiment, one or more polymer precursors are copolymerized under acidic conditions. In an embodiment, the first polymer precursor is a phenolic compound and the second polymer precursor is an aldehyde compound. In one embodiment, the phenolic compound in the method according to the invention is phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof; the aldehyde compound is formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof. In a further embodiment, the phenolic compound is resorcinol, phenol, or a combination thereof, and the aldehyde compound is formaldehyde. In a further embodiment, the phenolic compound is resorcinol, and the aldehyde compound is formaldehyde. Other polymer precursors include nitrogen-containing compounds, such as melamine, urea, and ammonia.

[0073] In some embodiments, the electrochemical modifier is incorporated into the material as a polymer. For example, an organic or carbon-containing polymer, such as RF, may be copolymerized with the polymer containing the electrochemical modifier. In one embodiment, the electrochemical modifier-containing polymer contains silicon. In one embodiment, the polymer is tetraethylorthosilane (TEOS), and a TEOS solution is added to the RF solution before or after polymerization. In another embodiment, the polymer is a polysilane with organic side groups. In some cases, these side groups are methyl groups, in other cases, these groups are phenyl groups, and in other cases, the side chains include phenyl, pyrrole, acetate, vinyl, and siloxane moieties. In some cases, the side chains include Group 14 elements (silicon, germanium, tin, or lead). In other cases, the side chains include Group 13 elements (boron, aluminum, boron, gallium, indium). In other cases, the side chains include Group 15 elements (nitrogen, phosphorus, arsenic). In other cases, the side chain contains a Group 16 element (oxygen, sulfur, selenium).

[0074] In another embodiment, the electrochemical modifier is a silole. In some cases, the electrochemical modifier is a phenol-silole or a silafluorene. In other cases, the electrochemical modifier is a poly-silole or a poly-silafluorene. In some cases, silicon may be substituted with germanium (germole or germafluorene), zinc (stanol or stannafluorene), nitrogen (carbazole) or phosphorus (phosphole, phosphafluorene). In all cases, the heteroatom-containing material may be a small molecule, oligomer or polymer. The phosphorus atom may also be bonded to oxygen or may not be bonded.

[0075] In some embodiments, the reactant contains phosphorus. In certain other embodiments, the phosphorus is in the form of phosphoric acid. In certain other embodiments, the phosphorus may be in the form of a salt. The anion of the salt comprises one or more of phosphate, phosphite, phosphide, hydrogen phosphate, dihydrogen phosphate, hexafluorophosphate, hypophosphite, polyphosphate, pyrophosphate ions, or combinations thereof. In certain other embodiments, the phosphorus may be in the form of a salt in which the cation of the salt comprises one or more phosphonium ions. The non-phosphate containing anion or cation pair for any of the above embodiments can be selected for those known and described in the art. Exemplary cations paired with phosphate-containing anions include, but are not limited to, ammonium ions, tetraethylammonium ions, and tetramethylammonium ions. Exemplary anions to pair with phosphate-containing cations include, but are not limited to, carbonate, dicarbonate, acetate ions, and the like.

[0076] In some cases, the crosslinker is important because of its chemical and electrochemical properties. In other cases, the crosslinker is important because it locks into the geometry of the polymer. In other cases, both the geometry and chemical composition of the polymer are important.

[0077] Crosslinkers can react at either low or high temperatures. In some cases, part of the reaction occurs at low temperatures and the rest of the reaction occurs at higher temperatures. Both the degree of crosslinking and the rate of reaction can be measured by a variety of chemical techniques (TGA, FTIR, NMR, XRD, etc.) and physical techniques (indentation, tensile testing, modulus, hardness, etc.).

[0078] In some cases, it is preferable to have the electrochemical modifier and / or crosslinker evenly distributed throughout the initial copolymer-homogeneous mixture. In other cases, it is important to have a non-uniform distribution of the crosslinker and / or electrochemical modification throughout the initial copolymer.

[0079] The structure of the polymer precursor is not particularly limited, but the polymer precursor can be reacted with another polymer precursor or a second polymer precursor to form a polymer. In some embodiments, the polymer precursor is selected from alcohols, phenols, polyhydric alcohols, sugars, alkylamines, aromatic amines, aldehydes, ketones, carboxylic acids, esters, ureas, acid halides, alkenes, alkynes, acrylates, epoxides, and isocyanates.

[0080] Various monomers, molecular components, oligomers and polymeric materials can be combined to produce a variety of polymers, such as novolacs, resols, novolac-type epoxides (composed of one or more phenols, resorcinol, formaldehyde, epichlorohydrin, bisphenol-A, bisphenol-F, epoxides), rubbers (isoprene, styrene-butadiene, styrene-butadiene-styrene, isobutylene, polyacrylate rubbers, ethylene-acrylate rubbers, bromo-isobutylene, isoprene, polybutadiene, chlorobutadiene isoprene, polychloroprene, epichlorohydrin, ethylene propylene, ethylene propylene diene monomer, polyether urethanes, perfluorocarbon rubbers, fluorosilicones, hydrogenated nitrile butadiene, acrylonitrile butadiene, polyurethanes), nylons (nylon-6, nylon-6,6, nylon-6,9; nylon-6,10; nylon-6,12, nylon-11, nylon-12, nylon-4,6 and the like), acrylates (methyl acrylate, ethyl acrylate, 2-chloroethyl-vinyl ether, 2-ethylhexyl acrylate, hydroxyethyl methacrylate, butyl acrylate, butyl methacrylate, acrylonitrile), polystyrene, polyurethanes (ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, tripropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, ethanolamine, diethanolamine, methyldiethanolamine, phenyldiethanolamine, glycerol, trimethylolpropane, 1,2,6-hexanetriol, triethanolamine, pentaerythritol, diethyltoluenediamine, dimethylthiotoluenediamine).

[0081] In some cases, the polymer precursors include (a) alcohols, phenolic compounds, and other monohydric or polyhydric alcohol compounds, and (b) aldehydes, ketones, and combinations thereof. Representative alcohols in this regard include linear or branched, saturated or unsaturated alcohols. Another representative phenolic compound is bisphenol A and related bisphenol molecules. Suitable phenolic compounds include polyhydroxybenzenes, such as dihydroxybenzenes or trihydroxybenzenes. Another representative phenolic compound is bisphenol A and related bisphenol molecules. Representative polyhydroxybenzenes include resorcinol (i.e., 1,3-dihydroxybenzene), catechol, hydroquinone, and fluoroglucinol. Mixtures of two or more polyhydroxybenzenes can also be used. Phenols (monohydroxybenzenes) can also be used. Representative polyhydroxy compounds include sugars (e.g., glucose, etc.) and other polyols (e.g., mannitol, etc.). The aldehydes of interest include: straight-chain saturated aldehydes such as methanal (formaldehyde), ethanal (acetaldehyde), propanal (propionaldehyde), butanal (butyraldehyde), etc.; straight-chain unsaturated aldehydes such as ethenone and other ketenes, 2-propenal (acrylaldehyde), 2-butenal (crotonaldehyde), 3-butenal, etc.; branched saturated and unsaturated aldehydes; and aldehydes of the aromatic type such as benzaldehyde, salicylaldehyde, hydrocinnamaldehyde, etc. Suitable ketones include: linear saturated ketones such as propanone and 2-butanone; linear unsaturated ketones such as propenone, 2-butenone and 3-butenone (methyl vinyl ketone); branched saturated and unsaturated ketones; and aromatic type ketones such as methyl benzyl ketone (phenylacetone), ethyl benzyl ketone, etc. The polymer precursor material may be a combination of the above precursors.

[0082] In one embodiment, the method includes using a first and a second polymer precursor, and in some embodiments, the first or the second polymer precursor is a carbonyl-containing compound, and the other of the first or the second polymer precursor is an alcohol-containing compound. In some embodiments, the first polymer precursor is a phenolic compound, and the second polymer precursor is an aldehyde compound, such as formaldehyde. In one aspect of the method, the phenolic compound is phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof, and the aldehyde compound is formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof. In a further embodiment, the phenolic compound is resorcinol, phenol, or a combination thereof, and the aldehyde compound is formaldehyde. In yet another embodiment, the phenolic compound is resorcinol, and the aldehyde compound is formaldehyde. In some embodiments, the polymer precursors are an alcohol and a carbonyl compound (eg, resorcinol and an aldehyde), which are present in a ratio of about 0.5:1.0, respectively.

[0083] In some embodiments, one of the polymer precursors is an alcohol-containing species, and another polymer precursor is a carbonyl-containing species.The relative amount of the alcohol-containing species (e.g., alcohol, phenolic compounds and mono- or poly-hydroxy compounds, or mixtures thereof) reacted with the carbonyl-containing species (e.g., aldehyde, ketone, or combinations thereof) can vary widely.In some embodiments, the ratio of the alcohol-containing species to the aldehyde is selected such that the total number of moles of reactive alcohol groups in the alcohol-containing species is approximately the same as the total number of moles of reactive carbonyl groups in the aldehyde species.Similarly, the ratio of the alcohol-containing species to the ketone species is selected such that the total number of moles of reactive alcohol groups in the alcohol-containing species is approximately the same as the total number of moles of reactive carbonyl groups in the ketone species.The same generally applies when the carbonyl-containing species contains a combination of aldehyde species and ketone species.

[0084] In other embodiments, the polymer precursor is a urea or amine-containing compound. For example, in some embodiments, the polymer precursor is urea or melamine. Other embodiments include polymer precursors selected from isocyanates or other active carbonyl compounds, such as acid halides. Still other embodiments use phenolic precursors, including, but not limited to, phenols, resorcinols, and other hydroxy- and aromatic ring-containing molecules.

[0085] In some embodiments of the methods described herein, the molar ratio of phenol precursor to catalyst is from about 5:1 to about 2000:1, or alternatively, the molar ratio of phenol precursor to catalyst is from about 20:1 to about 200:1. In other embodiments, the molar ratio of phenol precursor to catalyst is from about 25:1 to about 100:1. In further embodiments, the molar ratio of phenol precursor to catalyst is from about 5:1 to about 10:1. In further embodiments, the molar ratio of phenol precursor to catalyst is from about 100:1 to about 5:1.

[0086] In one particular embodiment, one polymer precursor is resorcinol and / or phenol and another polymer precursor is formaldehyde, and the ratio of resorcinol and / or phenol to catalyst can be varied to obtain desired properties of the resulting polymer gel and carbon material. In some embodiments of the methods described herein, the molar ratio of resorcinol and / or phenol to catalyst is about 10:1 to about 2000:1, or the molar ratio of resorcinol and / or phenol to catalyst is about 20:1 to about 200:1. The molar ratio of resorcinol and / or phenol to catalyst is about 25:1 to about 100:1, or the molar ratio of resorcinol and / or phenol to catalyst is about 5:1 to about 10:1. In further embodiments, the molar ratio of resorcinol and / or phenol to catalyst is about 5:1 to about 10:1, or the molar ratio of resorcinol and / or phenol to catalyst is about 100:1 to about 5:1.

[0087] The total solids content in the solution or suspension prior to forming the polymer gel can vary. The weight ratio of resorcinol to water is about 0.05-1: about 0.70-1. Alternatively, the weight ratio of resorcinol to water is about 0.15-1: about 0.6-1. Alternatively, the weight ratio of resorcinol to water is about 0.15-1: about 0.35-1. Alternatively, the weight ratio of resorcinol to water is about 0.25-1: about 0.5-1. Alternatively, the weight ratio of resorcinol to water is about 0.3-1: about 0.35-0.6.

[0088] Examples of solvents useful in preparing the polymer gel disclosed herein include, but are not limited to, water, or alcohol, such as ethanol, t-butanol, methanol, or mixtures thereof, and aqueous mixtures thereof. Such solvents are useful for dissolving polymer precursors, such as dissolving phenolic compounds. Furthermore, in some processes, such solvents are used to exchange the solvent in the polymer gel before freezing and drying, in which case the solvent in the polymerization of the precursor (e.g., resorcinol and formaldehyde) is exchanged with pure alcohol. In one embodiment of the present application, the polymer gel is prepared by a method that does not include solvent exchange.

[0089] Suitable catalysts for preparing polymer gels include volatile basic catalysts that promote polymerization to convert precursors into monolithic polymers. Catalysts include various combinations of the above-mentioned catalysts. In embodiments that include phenolic compounds or other polymer precursors, such catalysts are used in the range of phenolic compound:catalyst molar ratios of 5:1 to 200:1. For example, in specific embodiments, such catalysts can be used in the range of phenolic compound:catalyst molar ratios of 5:1 to 10:1.

[0090] In some embodiments, the gel polymerization process is carried out under catalytic conditions. Thus, in some embodiments, the process comprises combining a catalyst with the solventless mixture. In some embodiments, the catalyst is a solid at room temperature and pressure.

[0091] In some embodiments, the catalyst is a liquid at room temperature and pressure. In some embodiments, the catalyst is a liquid at room temperature and pressure that does not dissolve one or more other polymer precursors.

[0092] In some embodiments, the catalyst comprises a basic volatile catalyst. For example, in one embodiment, the basic volatile catalyst comprises ammonium carbonate, ammonium bicarbonate, ammonium acetate, ammonium hydroxide, or a combination thereof. In a further embodiment, the basic volatile catalyst is ammonium carbonate. In another further embodiment, the basic volatile catalyst is ammonium acetate.

[0093] The molar ratio of catalyst to polymer precursor (e.g., phenolic compound) can affect the final properties of the polymer gel and the final properties of the carbon material. Thus, in some embodiments, such catalysts are used in a range of molar ratios of polymer precursor:catalyst from 5:1 to 2000:1. In some embodiments, such catalysts can be used in a range of molar ratios of polymer precursor:catalyst from 10:1 to 400:1. For example, in other embodiments, such catalysts can be used in a range of molar ratios of polymer precursor:catalyst from 5:1 to 100:1. For example, in some embodiments, the molar ratio of catalyst to polymer precursor is about 400:1. In other embodiments, the molar ratio of catalyst to polymer precursor is about 100:1. In other embodiments, the molar ratio of catalyst to polymer precursor is about 50:1. In other embodiments, the molar ratio of catalyst to polymer precursor is about 10:1. In certain of the above embodiments, the polymer precursor is a phenolic compound, such as resorcinol or phenol.

[0094] In yet another embodiment, the method comprises mixing an acid. In certain embodiments, the acid is solid at room temperature and pressure. In some embodiments, the acid is liquid at room temperature and pressure. In some embodiments, the acid is liquid at room temperature and pressure that does not cause dissolution of one or more other polymer precursors.

[0095] The acid can be selected from any number of acids suitable for the polymerization method. For example, in some embodiments, the acid is acetic acid, and in other embodiments, the acid is oxalic acid. In further embodiments, the acid is mixed with the first or second solvent in an acid to solvent ratio of 99:1, 90:10, 75:25, 50:50, 25:75, 20:80, 10:90, or 1:90. In other embodiments, the acid is acetic acid and the first or second solvent is water. In other embodiments, the acidity is provided by adding a solid acid.

[0096] The total content of acid in the mixture can be varied to alter the properties of the final product. In some embodiments, the acid is present at about 1% to about 50% by weight of the mixture. In other embodiments, the acid is present at about 5% to about 25%. In other embodiments, the acid is present at about 10% to about 20%, such as about 10%, about 15% or about 20%.

[0097] In certain embodiments, the polymer precursor components are mixed together and then held at a sufficient time and temperature to achieve polymerization, one or more of the polymer precursor components may have a particle size (particle size) of less than about 20 mm in dimension, such as less than 10 mm, such as less than 7 mm, such as less than 5 mm, such as less than 2 mm, such as less than 1 mm, such as less than 100 microns, such as less than 10 microns. In some embodiments, the particle size of one or more of the polymer precursor components is reduced during the mixing process.

[0098] Mixing of one or more polymer precursor components in the absence of a solvent can be accomplished by methods described in the art, such as ball milling, jet milling, Fritsch milling, planetary mixing, and other mixing methodologies for mixing or blending solid particles while controlling process conditions (e.g., temperature). The mixing or blending step can be accomplished before, during, and / or after (or a combination thereof) incubation at the reaction temperature.

[0099] The reaction parameters include aging the mixed mixture at a temperature and time sufficient to allow one or more polymer precursors to react with each other and form a polymer. In this regard, suitable aging temperatures range from about room temperature to about the melting temperature of one or more polymer precursors. In some embodiments, suitable aging temperatures range from about room temperature to about the glass transition temperature of one or more polymer precursors. For example, in some embodiments, the solvent-free mixture is aged at a temperature of about 20°C to about 600°C, such as about 20°C to about 500°C, such as about 20°C to about 400°C, such as about 20°C to about 300°C, such as about 20°C to about 200°C. In certain embodiments, the solvent-free mixture is aged at a temperature of about 50°C to about 250°C.

[0100] The reaction time is typically sufficient to allow the polymer precursors to react and form a polymer. For example, the mixture may be aged for 1 hour to 48 hours or more or less, depending on the desired result. Typical embodiments include aging for a period of about 2 hours to about 48 hours. For example, in some embodiments, aging comprises about 12 hours. In other embodiments, aging comprises about 4 hours to about 8 hours (e.g., about 6 hours).

[0101] In certain embodiments, an electrochemical modifier is incorporated during the polymerization process described above. For example, in some embodiments, the electrochemical modifier is in the form of metal particles, metal pastes, metal salts, metal oxides, or molten metals, dissolved or suspended in the mixture that produces the gel resin.

[0102] Exemplary electrochemical modifiers for producing composite materials may fall into one or more of the chemical classes. In some embodiments, the electrochemical modifier is a sugar, such as, but not limited to, chitin, chitosan, glucose, sucrose, fructose, cellulose, and combinations thereof. In one embodiment, the electrochemical modifier is a biopolymer, such as lignin. In one embodiment, the electrochemical modifier is a protein, such as gelatin. In one embodiment, the electrochemical modifier is a biopolymer, such as lignin. In one embodiment, the electrochemical modifier is an amine compound, such as urea or melamine, or combinations thereof. In certain embodiments, the electrochemical modifier is a halogen salt, including, but not limited to, sodium chloride, lithium bromide, potassium fluoride, and combinations thereof. In certain embodiments, the electrochemical modifier is a nitrate salt, including, but not limited to, lithium nitrate, sodium nitrate, and combinations thereof. In certain embodiments, the electrochemical modifier is a carbide compound, including, but not limited to, calcium carbide, silicon carbide, and combinations thereof. In certain embodiments, the electrochemical modifier comprises a metal, and exemplary species include, but are not limited to, aluminum isopropoxide, manganese acetate, nickel acetate, iron acetate, tin chloride, silicon chloride, and combinations thereof.In certain embodiments, the electrochemical modifier comprises a phosphate compound, including, but are not limited to, phytic acid, phosphoric acid, ammonium dihydrogen phosphate, and combinations thereof.In certain embodiments, the electrochemical modifier comprises silicon, and exemplary species include, but are not limited to, silicon powder, silicon nanotubes, polycrystalline silicon, nanocrystalline silicon, amorphous silicon, porous silicon, nano-sized silicon, nanofeatured silicon, nano-sized and nanofeatured silicon, silicyne, and black silicon, and combinations thereof.

[0103] Electrochemical modifiers can be combined with various polymer systems either through physical mixing or chemical reaction with latent (or secondary) polymer functionalities. Examples of latent polymer functionalities include, but are not limited to, epoxide groups, unsaturation (double and triple bonds), acid groups, alcohol groups, amine groups, basic groups, etc. Crosslinking by latent functionalities (functional groups) can be achieved via heteroatoms (e.g., vulcanization with sulfur, acid / base / ring-opening reactions with phosphoric acid), reaction with organic acids or bases (as discussed above), coordination to transition metals (including, but not limited to, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ag, Au), ring-opening or ring-closing reactions (rotaxanes, spiro compounds, etc.).

[0104] Polymerization to form a polymer gel can be accomplished by various means described in the art and can include the addition of an electrochemical modifier. For example, polymerization can be accomplished by incubating the appropriate polymer precursor material and, optionally, the electrochemical modifier in the presence of a suitable catalyst for a sufficient period of time. Polymerization times can range from minutes or hours to days, depending on the temperature (higher temperatures can result in faster reaction rates and correspondingly shorter times). Polymerization temperatures can range from room temperature to temperatures approaching (but below) the boiling point of the starting solution. For example, in some embodiments, the polymer gel is aged at a temperature of about 20°C to about 120°C, such as about 20°C to about 100°C. In other embodiments, the temperature is in the range of about 30°C to about 90°C, about 45°C or about 85°C. In other embodiments, the temperature ranges from about 65°C to about 80°C, while other embodiments include aging at two or more temperatures, for example, at about 45°C and about 75°C to 85°C or about 80°C to 85°C.

[0105] The electrochemical modifiers can also be added to the polymer system via physical blending, which can include, but is not limited to, melt blending of polymers and / or copolymers, inclusion of discrete particles, chemical vapor deposition of the electrochemical modifier, and co-precipitation of the electrochemical modifier with the main polymeric material.

[0106] In another embodiment, the electrochemical modifier is a particle. The electrochemical modifier particles can have different particle size distributions. In one embodiment, the electrochemical modifier particles have a D50 of 10 nm or 50 nm or 100 nm or 150 nm or 200 nm or 500 nm or 1 μm or 1 μm or 2 μm or 3 μm or 5 μm or 10 μm or 20 μm or 40 μm or 50 μm or less or 100 μm or less. In some embodiments, the polymer and the particle form a mixture. In other embodiments, the particle is covalently bonded to the polymer. In other embodiments, the particle is ionically bonded to the polymer. In some cases, the particle is silicon, and in other cases, the particle is a different Group 14 element (Ge, Sn, Pb), Group 15 element (P, As, Sb), Group 16 element (S, Se, Te). In some cases, the particle includes a single element, and in other cases, a mixture of two or more elements.

[0107] The electrochemically modified particles can be dispersed in an organic polymer solution or prepolymer in a variety of ways. In one embodiment, the particles are dispersed by sonication. In another embodiment, the particles are dispersed by mixing. In another embodiment, the particles are dispersed by modifying the surface chemistry of the particles and the pH of the solution. In another embodiment, the particles are dispersed using a surfactant. In one embodiment, the surfactant is SPAN80. In another embodiment, the particles are dispersed in an emulsion or suspension. In one embodiment, the surfactant is used in combination with a hydrocarbon solvent. In one embodiment, the hydrocarbon is cyclohexane. In one embodiment, the hydrocarbon is mineral oil. In another embodiment, the hydrocarbon is vegetable oil.

[0108] In some cases, the electrochemical modifier can be added via a metal salt solution. The metal salt solution or suspension can include an acid and / or alcohol to improve the solubility of the metal salt. Yet another embodiment includes contacting the polymer gel (either before or after any drying step) with a paste that includes the electrochemical modifier. Yet another embodiment includes contacting the polymer gel (either before or after any drying step) with a metal or metal oxide sol that includes the desired electrochemical modifier.

[0109] In addition to the exemplary electrochemical modifiers, the composite material may include one or more additional forms (i.e., allotropes) of carbon. In this regard, the inclusion of different allotropes of carbon, such as graphite, amorphous carbon, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene, and / or carbon fibers, into the composite material has been found to be effective in optimizing the electrochemical properties of the composite material. Various allotropes of carbon can be incorporated into the carbon material during any stage of the manufacturing method described herein. For example, during the solution stage, during the gelation stage, during the curing stage, during the gelation stage, during the pyrolysis stage, during the grinding stage, or after grinding. In some embodiments, a second carbon form can be incorporated into the composite material by adding the second carbon form before or during the polymerization of the polymer gel, as described in more detail herein. The polymerized polymer gel containing the second carbon form is then processed according to the general techniques described herein to obtain a carbon material containing the second allotrope of carbon.

[0110] In some embodiments, the organic polymer and the electrochemical modifier have different solvents, ratios of solvents, mixtures of solvents, catalyst types, catalyst ratios, solvent pH, acid types, or bases.

[0111] As expected, the electrochemical modifier content of the final composite can be varied by varying either the relative solids concentration of the carbon-containing polymer solution and / or the relative solids concentration of the electrochemical modifier containing polymer solution. In one embodiment, the solids concentration of the organic polymer solution can be varied from 1% to 99% solids, or 10% to 90% solids, or 20% to 80% solids, or 20% to 50% or 30% to 40% solids. In one embodiment, the solids concentration of the polymer solution is 35%. In one embodiment, the solids concentration of the electrochemical modifier polymer solution can be varied from 1% to 99% solids, or 10% to 90% solids, or 20% to 80% solids, or 20% to 50% or 30% to 40% solids. In one embodiment, the solids concentration of the electrochemical modifier solution is 35%. In one embodiment, the electrochemical modifier is a TEOS polymer and is mixed with ethanol. In another embodiment, the TEOS polymer is mixed with acetone or isopropyl alcohol.

[0112] Varying the ratio of organic polymer to electrochemical modifier polymer solution in any given mixture is expected to change the final ratio of carbon to electrochemical modifier in the final composite. In one embodiment, the ratio of organic polymer to electrochemical modifier polymer is about 10:1, or 9:1, or 8:1, or 7:1, or 6:1, or 5:1, or 4:1, or 3:1, or 2:1, or 1:1, or 1:2, or 1:3, or 1:4, or 1:5, or 1:6, or 1:7, or 1:8, or 1:9, or 1:10.

[0113] In one embodiment, the organic polymer / electrochemical modifier polymer solution is heated until a gel is formed. In one embodiment, the TEOS / RF solution is heated until a gel is formed. In one embodiment, the heating is performed in a closed vessel. In one embodiment, the heating is performed in a polymer reactor, such as a stirred polymer reactor. In one embodiment, the solution is heated in an emulsion or in an inverse emulsion or suspension. The temperature at which gelation occurs is known to affect the structure of the polymer and can be modified to control the structure of the final composite. In one aspect, the gel is formed at 40° C. or 50° C. or 60° C. or 70° C. or 80° C. or 90° C. or 100° C. or 110° C. or 120° C. or 130° C. In one embodiment, the gel is formed in a two-step reaction. For example, one temperature gels the organic polymer and a different temperature gels the electrochemical modifier polymer. In one embodiment, the two-stage polymerization is carried out at 40° C. or 50° C. or 60° C. or 70° C. or 80° C. or 90° C. or 100° C. or 110° C. or 120° C. or 130° C., and then the second step is carried out at 40° C. or 50° C. or 60° C. or 70° C. or 80° C. or 90° C. or 100° C. or 110° C. or 120° C. or 130° C. In some embodiments, the organic polymer is fully gelled and then the electrochemical modifier polymer solution is added via solvent exchange to dope the organic polymer. In some embodiments, the electrochemical modifier polymer is fully gelled and then the organic polymer solution is added via solvent exchange to dope the electrochemical modifier polymer.

[0114] In some embodiments, the proportion of solvent in the reaction mixture is low or the reaction can be essentially solvent-free. For example, the proportion of solvent in the reaction mixture can be less than 80% of the total mass of the reaction mixture, such as less than 70%, such as less than 60%, such as less than 50%, such as less than 40%, such as less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 1%, such as less than 0.1%, such as less than 0.01%. Without being bound by theory, the pyrolytic carbon yield from the polymeric material can be about 50%. Thus, the ratio of pyrolytic carbon generated per unit mass of treated polymer can be less than about 10, less than about 7, less than about 5, less than about 4, less than about 3, less than about 2.5, less than about 2.1. In some embodiments, the ratio of pyrolytic carbon generated per unit mass of treated polymer is about 2. In some embodiments, the ratio of pyrolytic carbon generated per unit mass of treated polymer is less than 2.

[0115] The pyrolytic carbon produced from a low-solvent or essentially solvent-free reaction mixture can be activated. The ratio of activated carbon to treated polymer is higher than the ratio of pyrolytic carbon to treated polymer, depending on the desired activation level. Without being bound by theory, the activated carbon yield from pyrolytic carbon material can be about 50%. Thus, the ratio of activated carbon produced per unit mass of treated polymer can be less than about 14, less than about 10, less than about 8, less than about 6, less than about 5, less than about 4.5, less than about 4.1. In some embodiments, the ratio of activated carbon produced per unit mass of treated polymer is about 4 or less.

[0116] The structure of the polymer precursor suitable for use in the low-solvent or essentially solvent-free reaction mixture is not particularly limited, so long as the polymer precursor can react with another polymer precursor or react with a second polymer precursor to form a polymer.Polymer precursors include amine-containing compounds, alcohol-containing compounds and carbonyl-containing compounds.For example, in some embodiments, the polymer precursor is selected from alcohols, phenols, polyhydric alcohols, sugars, alkylamines, aromatic amines, aldehydes, ketones, carboxylic acids, esters, ureas, acid halides and isocyanates.

[0117] In one embodiment using a low-solvent or essentially solvent-free reaction mixture, the method includes using a first and a second polymer precursor. In some embodiments, the first or second polymer precursor is a carbonyl-containing compound, and the other of the first or second polymer precursor is an alcohol-containing compound. In some embodiments, the first polymer precursor is a phenolic compound, and the second polymer precursor is an aldehyde compound (e.g., formaldehyde). In one aspect, the phenolic compound is phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof, and the aldehyde compound is formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof. In a further embodiment, the phenolic compound is resorcinol, phenol, or a combination thereof, and the aldehyde compound is formaldehyde. In yet another embodiment, the phenolic compound is resorcinol, and the aldehyde compound is formaldehyde. In some embodiments, the polymer precursors are an alcohol and a carbonyl compound (eg, resorcinol and an aldehyde), which are present in a ratio of about 0.5:1.0, respectively.

[0118] Suitable polymer precursor materials for the low-solvent or essentially solvent-free reaction mixture as disclosed herein include (a) alcohols, phenolic compounds, and other mono- or polyhydroxy compounds, and (b) aldehydes, ketones, and combinations thereof. Representative alcohols in this context include linear and branched, saturated and unsaturated alcohols. Suitable phenolic compounds include polyhydroxybenzenes, such as dihydroxy or trihydroxybenzenes. Representative polyhydroxybenzenes include resorcinol (i.e., 1,3-dihydroxybenzene), catechol, hydroquinone, and phloroglucinol. Other suitable compounds in this regard are bisphenols, such as bisphenol A. Mixtures of two or more of the polyhydroxybenzenes can also be used. Phenols (monohydroxybenzenes) can also be used. Representative polyhydroxy compounds include sugars, such as glucose, sucrose, fructose, chitin, and other polyols, such as mannitol. Aldehydes in this context include straight-chain saturated aldehydes such as methanal (formaldehyde), ethanal (acetaldehyde), propanal (propionaldehyde), butanal (butyraldehyde); straight-chain unsaturated aldehydes such as ethenone and other ketenes, 2-propenal (acrylaldehyde), 2-butenal (crotonaldehyde), 3-butenal, etc.; branched saturated and unsaturated aldehydes; aromatic aldehydes such as benzaldehyde, salicylaldehyde, hydrocinnamaldehyde, etc. Suitable ketones include linear saturated ketones such as propanone, 2-butanone, etc.; linear unsaturated ketones such as propenone, 2-butenone, 3-butenone (methyl vinyl ketone); branched saturated and unsaturated ketones, etc.; aromatic ketones such as methyl benzyl ketone (phenylacetone), ethyl benzyl ketone, etc. The polymer precursor material may be a combination of the above precursors.

[0119] In some embodiments, one polymer precursor in the low-solvent or essentially solvent-free reaction mixture is an alcohol-containing species and another polymer precursor is a carbonyl-containing species. The relative amount of the alcohol-containing species (e.g., alcohol, phenolic compounds, and mono- or polyhydroxy compounds or combinations thereof) reacted with the carbonyl-containing species (e.g., aldehyde, ketone, or combinations thereof) can be substantially varied. In some embodiments, the ratio of the alcohol-containing species to the aldehyde species can be selected such that the total number of moles of reactive alcohol groups in the alcohol-containing species is approximately the same as the total number of moles of reactive carbonyl groups in the aldehyde species. Similarly, the ratio of the alcohol-containing species to the ketone species can be selected such that the total number of moles of reactive alcohol groups in the alcohol-containing species is approximately the same as the total number of moles of reactive carbonyl groups in the ketone species. The same general 1:1 molar ratio applies when the carbonyl-containing species includes a combination of aldehyde and ketone species.

[0120] In other embodiments, the polymer precursor in the low-solvent or essentially solvent-free reaction mixture is a urea or amine-containing compound. For example, in some embodiments, the polymer precursor is urea, melamine, hexamethylenetetramine (HMT), or a combination thereof. Other embodiments include polymer precursors selected from other activated carbonyl compounds, such as isocyanates or acid halides.

[0121] Some embodiments of the disclosed method include the preparation of low-solvent or solvent-free polymer gels (and carbon materials) that include electrochemical modifiers. Such electrochemical modifiers include, but are not limited to, nitrogen, silicon, and sulfur. In other embodiments, the electrochemical modifiers include fluorine, iron, tin, silicon, nickel, aluminum, zinc, or manganese. The electrochemical modifiers can be included in the preparation procedure at any stage. For example, in some embodiments, the electrochemical modifiers are mixed with the mixture, the polymer phase, or the continuous phase.

[0122] Blending of one or more polymer precursor components in the absence of a solvent can be accomplished by methods described in the art, such as ball milling, jet milling, frisch grinding, planetary mixing, and other mixing methods that mix or blend solid particles while controlling process conditions (e.g., temperature). The mixing or blending step can be accomplished before, during, and / or after (or a combination thereof) incubation at the reaction temperature.

[0123] Reaction parameters include aging the blended mixture at a temperature and for a time sufficient to cause one or more polymer precursors to react with each other to form a polymer. In this regard, suitable aging temperatures range from about room temperature to at or near the melting temperature of one or more of the polymer precursors. In some embodiments, suitable aging temperatures range from about room temperature to at or near the glass transition temperature of one or more of the polymer precursors. For example, in some embodiments, the solvent-free mixture is aged at a temperature of about 20°C to about 600°C, such as about 20°C to about 500°C, such as about 20°C to about 400°C, such as about 20°C to about 300°C, such as about 20°C to about 200°C. In certain embodiments, the solvent-free mixture is aged at a temperature of about 50 to about 250°C.

[0124] The porous carbon material can be obtained by pyrolysis of the polymer produced from the precursor as described above. The temperature and residence time of pyrolysis can be varied. For example, the residence time can be varied from 1 minute to 10 minutes, 10 minutes to 30 minutes, 30 minutes to 1 hour, 1 hour to 2 hours, 4 hours to 24 hours. The temperature can be varied, for example, the pyrolysis temperature can be varied from 200°C to 300°C, 350°C to 450°C, 450°C to 550°C, 540°C to 650°C, 650°C to 750°C, 750°C to 850°C, 850°C to 950°C, 950°C to 1050°C, 1050°C to 1150°C, 1150°C to 1250°C. Pyrolysis can be achieved in an inert gas such as nitrogen or argon. In some embodiments, an alternative gas is used, or a mixture of an inert gas such as nitrogen and an alternative gas is used. Suitable alternative gases in this context include, but are not limited to, carbon dioxide, carbon monoxide, water (water vapor), air, oxygen, and further combinations thereof.

[0125] Either before and / or after pyrolysis, the porous carbon particles can undergo particle size reduction. Particle size reduction can be achieved by a variety of techniques known in the art, such as jet milling in the presence of various gases, including air, nitrogen, argon, helium, supercritical steam, and other gases known in the art. Other particle size reduction methods, such as grinding, ball milling, jet milling, water jet milling, and other techniques known in the art, can also be used.

[0126] In some embodiments, the surface area of ​​the porous carbon material is greater than 500 m 2 / g, e.g. 750m 2 / g, e.g. 1000m 2 / g, e.g., 1250m 2 / g, e.g. 1500m 2 / g, e.g. 1750m 2 / g, e.g. 2000m 2 / g, e.g. 2500m 2 / g, e.g. 3000m 2 / g over 3000m 2 In other embodiments, the surface area of ​​the porous carbon material may be greater than 500 m / g. 2 The surface area of ​​the porous carbon material may be less than 200 to 500 m / g in some embodiments. 2 The surface area of ​​the porous carbon material is, in some embodiments, 100 to 200 m 2 The surface area of ​​the porous carbon material is, in some embodiments, 50 to 100 m 2 The surface area of ​​the porous carbon material is, in some embodiments, 10 to 50 m 2 / g. The surface area of ​​the porous carbon material is 10 m 2 / g.

[0127] The pore volume of the porous carbon material is 0.5 cm 3 / g, e.g., 0.6 cm 3 / g, e.g., 0.7 cm 3 / g, e.g., 0.8 cm 3 / g, e.g., 0.9 cm 3 / g, 1.0cm 3 / g, e.g., 1.1 cm 3 / g, e.g., 1.2 cm 3 / g, e.g., 1.4 cm 3 / g, e.g., 1.6 cm 3 / g, e.g., 1.8 cm 3 / g, e.g., 2.0 cm 3 In another embodiment, the pore volume of the porous silicon material is greater than 0.5 cm 3 / g, e.g. 0.1 cm 3 / g~0.5cm 3 In certain other embodiments, the pore volume of the porous silicon material is less than or equal to 0.01 cm3 / g. 3 / g~0.1cm 3 / g.

[0128] In some other embodiments, the porous carbon material has a tap density of 1.0 g / cm 3 Less than, for example, less than 0.8 g / cm 3, e.g. 0.6g / cm 3 Less than, for example, less than 0.5 g / cm 3 Less than, for example, 0.4 g / cm 3 , e.g. less than 0.3 g / cm 3 , e.g. 0.2g / cm 3 Less than, for example, 0.1 g / cm 3 is less than.

[0129] The surface functionality of the porous carbon material can be varied. One property that can predict surface functionality is the pH of the porous carbon material. The porous carbon materials of the present disclosure have pH values ​​ranging from less than 1 to about 14, such as less than 5, 5-8, and greater than 8. In some embodiments, the pH of the porous carbon can be less than 4, less than 3, less than 2, or less than 1. In other embodiments, the pH of the porous carbon is about 5-6, 6-7, about 7-8, 8-9, or 9-10. In still other embodiments, the pH is high and the pH range of the porous carbon is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.

[0130] The pore volume distribution of the porous carbon scaffold can be varied. For example, the % micropores is less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, or such as less than 0.1%. In some embodiments, there is no detectable pore volume in the porous carbon scaffold.

[0131] The mesopores of the porous carbon scaffold material can vary. For example, the % mesopores is less than 30% by weight, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, or such as less than 0.1%. In some embodiments, there is no detectable pore volume in the porous carbon scaffold.

[0132] In some embodiments, the pore volume distribution of the porous carbon scaffold material has more than 50% macropores, such as more than 60% macropores, for example more than 70% macropores, such as more than 80% macropores, for example more than 90% macropores, such as 95% or more macropores, for example more than 98% macropores, such as more than 99% macropores, for example more than 99.5% macropores, such as more than 99.9% macropores.

[0133] In certain preferred embodiments, the pore volume of the porous carbon scaffold comprises a mixture of micropores, mesopores and macropores. Thus, in certain embodiments, the porous carbon scaffold has 0-20% micropores, 30-70% mesopores and less than 10% macropores. In certain other embodiments, the porous carbon scaffold has 0-20% or less micropores, 0-20% mesopores and 70-95% macropores. In certain other embodiments, the porous carbon scaffold has 20-50% micropores, 50-80% mesopores and 0-10% macropores. In certain other embodiments, the porous carbon scaffold has 40-60% micropores, 40-60% mesopores and 0-10% macropores. In certain other embodiments, the porous carbon scaffold has 80-95% micropores, 0-10% mesopores, and 0-10% macropores. In certain other embodiments, the porous carbon scaffold has 0-10% micropores, 30-50% mesopores, and 50-70% macropores. In certain other embodiments, the porous carbon scaffold has 0-10% micropores, 70-80% mesopores, and 0-20% macropores. In certain other embodiments, the porous carbon scaffold has 0-20% micropores, 70-95% mesopores, and 0-10% macropores. In certain other embodiments, the porous carbon scaffold has 0-10% micropores, 70-95% mesopores, and 0-20% macropores.

[0134] In certain embodiments, the % of pore volume in a porous carbon scaffold exhibiting pores that are 100-1000 A (10-100 nm) is more than 30% of the total pore volume, such as more than 40% of the total pore volume, for example more than 50% of the total pore volume, such as more than 60% of the total pore volume, for example more than 70% of the total pore volume, for example more than 80% of the total pore volume, for example more than 90% of the total pore volume, for example more than 95% of the total pore volume, such as more than 98% of the total pore volume, for example more than 99% of the total pore volume, for example more than 99.5% of the total pore volume, for example more than 99.9% of the total pore volume.

[0135] In certain preferred embodiments, the pore volume in a porous carbon scaffold exhibiting pores between 100 and 1000 A (10 to 100 nm) is less than 0.1 cm 3 / g, e.g. 0.2 cm 3 / g, e.g. 0.3 cm 3 / g, e.g. 0.4 cm 3 / g, e.g., 0.5 cm 3 / g, e.g. 0.6 cm 3 / g, e.g. 0.7 cm 3 / g, e.g., 0.8 cm 3 / g, e.g. 0.9 cm 3 / g, e.g., 1.0 cm 3 / g, e.g., 1.1 cm 3 / g, e.g. 1.2 cm 3 / g, e.g. 1.3 cm 3 / g, e.g. 1.4 cm 3 / g, e.g. 1.5 cm 3 / g, e.g., 2.0 cm 3 / g.

[0136] In certain preferred embodiments, the porous carbon scaffold is 0.5 cm 3 In certain preferred embodiments, the porous carbon scaffold has a total pore volume of more than 1.0 cm3 / g and the % macropores are greater than 80%. 3 / g and the % of macropores is greater than 90%. In certain other preferred embodiments, the porous carbon scaffold has a diameter of 0.5 cm 3In certain other preferred embodiments, the porous carbon scaffold has a total pore volume of greater than 1.0 cm3 / g and the % pores between 100 and 1000 A are greater than 80%. 3 / g, with more than 90% of the pores being between 100 and 1000 A.

[0137] The porous carbon scaffold, i.e., carbon without electrochemical modifiers, may have a majority (e.g., greater than 50%) of the pore volume present in pores of a certain diameter. For example, in some embodiments, greater than 50%, 60%, 70%, 80%, 90%, or 95% of the total pore volume is present in pores with a diameter of 1 nm or less. In other embodiments, greater than 50%, 60%, 70%, 80%, 90%, or 95% of the total pore volume is present in pores with a diameter of 100 nm or less. In other embodiments, greater than 50%, 60%, 70%, 80%, 90%, or 95% of the total pore volume is present in pores with a diameter of 0.5 nm or less.

[0138] In some embodiments, the tap density of an electrochemical modifier-free carbon may be predictive of its ability to incorporate electrochemical modifiers and thus electrochemical performance, e.g., volumetric capacity. Without being limited thereto, the pore volume of an electrochemical modifier-free carbon may be related to its tap density, and electrochemical modifier-free carbons having low pore volumes are often found to have high tap densities (and vice versa). Thus, electrochemical modifier-free carbons may be provided that provide low tap densities (e.g., <0.3 g / cc), medium tap densities (e.g., 0.3-0.5 g / cc), or high tap densities (e.g., >0.5 g / cc).

[0139] In yet other embodiments, the carbon without electrochemical modifiers has a tap density of 0.3 g / cc or greater. In yet other embodiments, the carbon without electrochemical modifiers has a tap density in the range of about 0.3 g / cc to about 0.5 g / cc. In some embodiments, the carbon without electrochemical modifiers has a tap density in the range of 0.35 g / cc to about 0.45 g / cc. In some other embodiments, the carbon without electrochemical modifiers has a tap density in the range of about 0.30 g / cc to about 0.40 g / cc. In some embodiments, the carbon without electrochemical modifiers has a tap density in the range of 0.40 g / cc to about 0.50 g / cc. In some of the above embodiments, the carbon without electrochemical modifiers has a media total pore volume (e.g., about 0.1 cc / g to about 0.6 cc / g).

[0140] In still other embodiments, the carbon without electrochemical modifiers can include a tap density of greater than about 0.5 g / cc. In some other embodiments, the carbon without electrochemical modifiers has a tap density in the range of about 0.5 g / cc to about 2.0 g / cc. In some other embodiments, the carbon without electrochemical modifiers has a tap density in the range of about 0.5 g / cc to about 1.0 g / cc. In some embodiments, the carbon without electrochemical modifiers has a tap density in the range of 0.5 g / cc to about 0.75 g / cc. In some embodiments, the carbon without electrochemical modifiers has a tap density in the range of 0.75 g / cc to about 1.0 g / cc, such as about 0.75 g / cc to about 0.95 g / cc, such as about 0.75 to about 1.2 g / cc. In some of the above embodiments, the carbon without electrochemical modifiers has a low, medium, or high total pore volume.

[0141] Their skeletal density, measured by helium pycnometry, can also characterize the density of the carbon without electrochemical modifiers. In certain embodiments, the skeletal density of the carbon without electrochemical modifiers is in the range of about 1 g / cc to about 3 g / cc, such as about 1.5 g / cc to about 2.3 g / cc. In other embodiments, the skeletal density is in the range of about 1.5 cc / g to about 1.6 cc / g, about 1.6 cc / g to about 1.7 cc / g, about 1.7 cc / g to about 1.8 cc / g, about 1.8 cc / g to about 1.9 cc / g, about 1.9 cc / g to about 2.0 cc / g, about 2.0 cc / g to about 2.1 cc / g, about 2.1 cc / g to about 2.2 cc / g, or about 2.2 cc / g to about 2.3 cc / g, about 2.3 cc / g to about 2.4 cc / g, such as about 2.4 cc / g to about 2.5 cc / g.

[0142] In either case, the properties of the carbon without the electrochemical modifier can be easily measured before containing the electrochemical modifier. The properties of the carbon without the electrochemical modifier can also be measured by removing the electrochemical modifier after the fact. This can be easily done by dissolving the silicon in a solvent that does not affect the carbon and then measuring the properties of the carbon without the electrochemical modifier.

[0143] C. Incorporation of silicon into scaffold materials to create composite materials Nano-sized silicon is difficult to handle and difficult to process in conventional electrodes. Due to the high surface area and desirability to agglomerate, uniform dispersion and coating requires special procedures and / or binder systems. To be a gem (drop) for replacement of existing graphite anode materials, the next generation Si-C materials need to be micron-sized. In preferred embodiments, the composite size distribution is relatively uniform, e.g., with upper and lower boundaries within the preferred ranges, Dv10 is 5 nm or more, Dv50 is 500 nm or more and 5 μm or less, and Dv90 is 50 μm or less. In certain other embodiments, the composite particles have a particle size distribution in which Dv10 is 50 nm or more, Dv50 is 1 μm to 10 μm, and Dv90 is 30 μm or less. In certain other embodiments, the composite particles have the following particle size distribution: Dv10 is 100 nm or more, Dv50 is 2 μm to 8 μm, and Dv90 is 20 μm or less. In certain further embodiments, the composite particles have a particle size distribution with Dv10 equal to or greater than 250 nm, Dv50 between 4 μm and 6 μm, and Dv90 equal to or less than 15 μm.

[0144] Unlike existing composite materials that embed silicon into a mass of inert material, it can be understood that silicon requires space to expand and contract in order to achieve optimal performance. The high pore volume carbon of the present invention is seen as a sink for embedding or attaching silicon, and is configured to fill a desired range of pore volumes to produce an impregnated carbon material of a desired size range. In this way, the template, e.g., the porous carbon material, not only contributes to the overall electron and ion conducting ability of the composite particle, but also plays an important role as a framework and in situ template for expansion / contraction. This scaffolding structure allows for the movement of electrons and possible ions, but its primary role is simply to fix the silicon in a single location and is configured to expand / contract outward while remaining within the pores.

[0145] In certain embodiments, silicon is introduced into the porous carbon by impregnation with nanoparticles. Thus, nano-sized silicon or silicon with nano-sized and nano-features is first produced. In a preferred embodiment, nano-sized silicon or silicon with nano-sized and nano-features is produced by the methods described in U.S. Patent Application No. 62 / 205,542, "Porous Silicon Materials with Nano-Features," U.S. Patent Application No. 62 / 208,357, "Porous Silicon Materials with Nano-Features," and / or U.S. Patent Application No. 62 / 209,651, "Composites of Porous Silicon Materials and Carbon Materials with Nano-Features," all of which are incorporated herein by reference in their entirety for all purposes.

[0146] The porous carbon can be mixed with the nanosilicon, for example, in a stirred reactor vessel. In this reactor vessel, the carbon particles, for example, micro-sized porous carbon particles, are co-suspended with the nanosilicon of the desired particle size. The suspension environment can be varied as known in the art, for example, aqueous or non-aqueous. In certain embodiments, the suspension can be multi-component, including either miscible or immiscible co-solvents. Suitable co-solvents for aqueous (water) environments are known in the art, including, but not limited to, acetone, ethanol, methanol, and the like. A wide variety of non-aqueous environments are known in the art, including, but not limited to, heptane, hexane, cyclohexane, and oils such as mineral oil and vegetable oil. Without wishing to be bound by theory, the mixing in the reactor vessel allows for the diffusion of silicon nanoparticles within the porous carbon particles. The resulting nanosilicon-impregnated carbon particles can be harvested, for example, by centrifugation, filtration, and subsequent drying, as known in the art.

[0147] For this purpose, the porous carbon particles having the desired degree and type of porosity are subjected to a treatment that results in the formation of silicon within said pores. Due to this treatment, the porous carbon particles can have a first particle size (primary particle size) reduced, for example, to provide a Dv50 of 1-1000 microns, such as 1-100 microns, for example 1-50 microns, for example 1-20 microns, for example 1-15 microns, for example 2-12 microns, for example 5-10 microns. The particle size reduction can be carried out as known in the art and can be carried out, for example, by jet milling, as described elsewhere herein.

[0148] In a preferred embodiment, to achieve silicon deposition via chemical vapor deposition (CVD), silicon is generated within the pores of the porous carbon by exposing the porous carbon particles to silane gas at elevated temperatures in the presence of a silicon-containing gas, preferably silane. The silane gas can be mixed with other inert gases, such as nitrogen gas. The temperature and time of the treatment can be varied, for example, the temperature is in the range of 300-400°C, such as 400-500°C, such as 500-600°C, such as 600-700°C, such as 700-800°C, such as 800-900°C. The gas mixture can include 0.1-1% silane and the remaining inert gas. Alternatively, the gas mixture can include 1%-10% silane and the remaining inert gas. Alternatively, the gas mixture can include 10%-20% silane and the remaining inert gas. Alternatively, the gas mixture can include 20%-50% silane and the remaining inert gas. Alternatively, the mixture of gases may contain 50% or more silane and the remaining inert gas. Alternatively, the gas may be essentially 100% silane gas. The reactor in which the CVD process is carried out may be, for example, a fluidized bed reactor, a static bed reactor, an elevator kiln, a rotary kiln, a box kiln, or other suitable reactor type, according to various designs known in the art. The reactor material is suitable for this operation, as known in the art. In a preferred embodiment, the porous carbon particles are processed under conditions that provide uniform access to the gas phase, and the porous carbon particles are processed in a fluidized reactor or other form that is agitated to provide uniform gas access.

[0149] In some embodiments, the CVD process is a plasma enhanced chemical vapor deposition (PECVD) process. This process is known in the art to provide the utility of depositing thin films from a gaseous (vapor) to a solid state on a substrate. A chemical reaction is included in the process that occurs after the generation of a plasma of the reactive gas. The plasma is generally created by RF (AC) frequency or direct current discharge between two electrodes, the space between which is filled by said reactive gas. In certain embodiments, the PECVD process is utilized on porous carbon that is coated on a suitable substrate, for example a copper foil substrate. PECVD can be performed at various temperatures, for example 300-800°C, for example 300-600°C, for example 300-500°C, for example 300-400°C, for example 350°C. The power can be varied, for example 25WRF, the silane gas flow rate required for the process can be varied, and the process time can be varied as known in the art.

[0150] It is understood that the silicon impregnated into the porous carbon, regardless of the method, has certain properties that are optimal for its utility as an energy storage material. For example, the size and shape of the silicon can be varied to match the extent and nature of the pore volume within the porous carbon particles, without being bound by theory. For example, silicon can be impregnated by CVD or other suitable process into pores within porous carbon particles having pore dimensions that are 5 nm to 1000 nm, such as 10 nm to 500 nm, such as 10 nm to 200 nm, such as 10 nm to 100 nm, such as 33 nm to 150 nm, such as 20 nm to 100 nm. Other ranges of carbon pore sizes in terms of pore volume are micropores, mesopores or macropores, and are described elsewhere in this disclosure.

[0151] The oxygen content in the silicon can be less than 50%, for example, less than 30%, for example, less than 20%, for example, less than 15%, for example, less than 10%, for example, less than 5%, for example, less than 1%, for example, less than 0.1%. In an embodiment, the oxygen content in the silicon is 1 to 30%. In an embodiment, the oxygen content in the silicon is 1 to 20%. In an embodiment, the oxygen content in the silicon is 1 to 10%. In an embodiment, the oxygen content in the porous silicon material is 5 to 10%.

[0152] In certain embodiments in which silicon contains oxygen, silicon and a compound of the general formula SiO x The oxygen is included such that the silicon is present as a mixture with silicon oxide of x = 0.01 x 0.02 x 0.01, where x is a non-integer (real number) that can vary continuously from 0.01 to 2. In some embodiments, the percentage of oxygen present at the surface of the porous silicon nanofeatures is higher than at the interior of the particles.

[0153] In certain embodiments, the silicon comprises crystalline silicon. In certain embodiments, the silicon comprises polycrystalline silicon. In certain embodiments, the silicon comprises micro-polycrystalline silicon. In certain embodiments, the silicon comprises nano-polycrystalline silicon. In certain other embodiments, the silicon comprises amorphous silicon. In certain other embodiments, the silicon comprises both crystalline and amorphous silicon.

[0154] In certain embodiments, the carbon scaffolds that are impregnated or otherwise embedded with silicon can include various carbon allotropes and / or geometries. To this end, carbon scaffolds that can be impregnated or otherwise embedded with silicon include graphite, nanographite, graphene, nanographene, conductive carbon, e.g., carbon black, carbon nanowires, carbon nanotubes, etc., and combinations thereof.

[0155] In certain embodiments, the carbon scaffold impregnated or embedded with silicon is removed to obtain a template silicon material with desired dimensional properties. Removal of the scaffold carbon can be performed, as known in the art, for example, by heat of chemical activation under conditions that do not cause the silicon to undergo undesirable changes in its electrochemical properties. Alternatively, if the scaffold is a porous polymer or other material that is soluble in a suitable solvent, the scaffold can be removed by dissolution.

[0156] D. Carbon coating of composite materials Without wishing to be bound by theory, the electrochemical performance of the composites produced by silicon infiltration into the porous carbon material can be achieved by coating, for example by coating the composite material in a carbon layer. In this context, the surface layer may comprise a carbon layer, as described in this section, or another suitable layer, a conductive polymer layer, as described in the next section.

[0157] It is understood that the surface layer provides a suitable SEI layer. In this case, the surface carbon layer needs to be a good ion conductor to carry Li-ions. Alternatively, the carbon layer can include an artificial SEI layer, for example, the carbon layer can include poly(3,4-ethylenedioxythiophene)-co-poly(ethylene glycol) copolymer. The coating can include nitrogen and / or oxygen functionality to further improve the layer in terms of promoting a stable SEI layer. The coating needs to provide sufficient electrical conductivity, adhesion, and cohesion between particles. The surface should provide a stable SEI layer, the latter typically consisting of species such as LiF, Li2CO3, Li2O, etc. Inorganic materials with a relatively low bulk modulus can provide a more stable SEI layer, for example, a more amorphous layer versus a crystalline layer is preferred, for example, Li2CO3 versus LiF.

[0158] For this purpose, a layer of carbon can be applied to the silicon-impregnated carbon material. Without being bound by theory, this carbon layer should provide a low surface area, low surface roughness and / or a low degree of morphological defects to provide a more stable SEI layer, higher first cycle efficiency and higher cycle stability in lithium-ion batteries. In the context of providing a surface layer to the silicon-impregnated porous carbon material, various carbon allotropes can be understood, including graphite, graphene, hard or soft carbon, e.g. pyrolytic carbon.

[0159] In another embodiment, the coating can be accomplished with a precursor solution as known in the art, followed by a carbonization process. For example, the particles can be coated by the Wurster process or related spray drying processes known in the art to apply a thin layer of precursor material onto the particles. The precursor coating can then be pyrolyzed by further fluidization of the Wurster coated particles, for example, at elevated temperature and in the presence of an inert gas, consistent with the descriptions disclosed elsewhere herein.

[0160] In another embodiment, the particles can be coated with a carbonaceous layer achieved by chemical vapor deposition (CVD). Without wishing to be bound by theory, it is believed that the CVD method for depositing a carbon layer (e.g., from a hydrocarbon gas) provides graphitizable carbon (hereinafter also referred to in the art as "soft" carbon). CVD procedures generally described in the art can be applied to the composite materials disclosed herein, for example to produce particles of porous silicon in which nano-sized silicon or nano-sized and nano-featured silicon is impregnated or otherwise introduced into the carbon pore volume of the desired range of pore sizes. CVD is generally achieved by exposing the porous silicon material to a suitable deposition gas containing carbon atoms at high temperature for a period of time. Suitable gases in this context include, but are not limited to, methane, propane, butane, cyclohexane, ethane, propylene, and acetylene. The temperature can be varied, for example, from 350 to 1050°C, for example, from 350 to 450°C, for example, from 450 to 550°C, for example, from 550 to 650°C, for example, from 650 to 750°C, for example, from 750 to 850°C, for example, from 850 to 950°C, for example, from 950 to 1050°C. The deposition time can be varied, for example, from 0 to 5 minutes, for example, from 5 to 15 minutes, for example, from 15 to 30 minutes, for example, from 30 to 60 minutes, for example, from 60 to 120 minutes, for example, from 120 to 240 minutes. In some embodiments, the deposition time is greater than 240 minutes. In some embodiments, the deposition gas is methane, and the deposition temperature is 950°C or greater in certain embodiments. In some embodiments, the deposition gas is propane, and the deposition temperature is 750°C or less in certain embodiments. In some embodiments, the deposition gas is cyclohexane, and the deposition temperature is 800°C or greater.

[0161] In certain embodiments, the reactor itself can be agitated, which can agitate the porous carbon scaffold to impregnate the silicon. For example, the impregnation process can be performed in a static mode, where the particles are not agitated. In a static mode, the silicon-containing reactant flows so as to contact over, around, or otherwise contact the particles to be coated. In other exemplary embodiments, the particles can be fluidized. For example, the impregnation of the silicon-containing reactant can be performed in a fluidized bed reactor. A variety of different reactor designs can be used, as known in the art, including, but not limited to, rotary kilns, roller hearth kilns, rotary kilns, box kilns, and modified fluidized bed designs.

[0162] Thus, the present disclosure provides for the preparation of a composite silicon-carbon material, in which the carbon scaffold material is a porous carbon material, and silicon impregnation is achieved by contacting the porous carbon material with a silicon-containing reactant. For example, the method may include the following steps: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to high temperatures in the presence of a silicon-containing reactant in a static or stirred reactor to form a silicon-impregnated carbon material. may have the following structure:

[0163] In another embodiment, the present disclosure provides for the preparation of a composite silicon-carbon material, in which the carbon scaffold material is a porous carbon material, silicon impregnation is achieved by contacting with a silicon-containing reactant, and a terminal carbon coating is achieved by contacting the composite with a carbon-containing reactant. For example, the method may include the following steps: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to elevated temperature in the presence of a silicon-containing reactant in a static or stirred reactor to form a silicon-impregnated carbon material; d) subjecting the silicon-impregnated carbon material to high temperatures in the presence of a carbon-containing reactant in a static or stirred reactor to obtain a carbon end-coated silicon-carbon composite material. may have

[0164] In another embodiment, the present disclosure provides for the preparation of a composite silicon-carbon material in which the carbon scaffold material is a porous carbon material, silicon impregnation is achieved by contacting with a silicon-containing reactant, and a terminal conductive polymer coating is achieved by contacting the composite with a conductive polymer and, optionally, pyrolyzing the material. For example, the method may comprise the following steps: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to elevated temperature in the presence of a silicon-containing reactant in a static or stirred reactor to form a silicon-impregnated carbon material; d) subjecting the silicon impregnated carbon material to high temperature in the presence of a conductive polymer in a static or stirred reactor to obtain a terminal conductive polymer coated silicon-carbon composite material; e) optionally pyrolyzing the material of d) may have

[0165] Silicon-impregnated porous carbon composites can also be end-carbon coated via hydrothermal carbonization, where the particles are treated in various manners according to the art. Hydrothermal carbonization can be carried out in an aqueous environment under high temperature and pressure to obtain silicon-carbon composites. Examples of temperatures for carrying out hydrothermal carbonization can be, for example, 150°C to 300°C, for example, 170°C to 270°C, for example, 180°C to 260°C, for example, 200°C to 250°C. Alternatively, hydrothermal carbonization can be carried out at higher temperatures, for example, 200°C to 800°C, for example, 300°C to 700°C, for example, 400°C to 600°C. In some embodiments, hydrothermal carbonization can be carried out at temperatures and pressures that achieve a graphitic structure. Ranges of pressures suitable for carrying out hydrothermal carbonization are known in the art, and the pressure can, for example, be varied, for example, increased, over the course of the reaction. Pressures for hydrothermal carbonization range from 0.1 MPa to 200 MPa. In certain embodiments, the pressure of the hydrothermal carbonization is 0.5 MPa to 5 MPa. In other embodiments, the pressure of the hydrothermal carbonization is 1 MPa to 10 MPa, or 5 to 20 MPa. In still other embodiments, the pressure of the hydrothermal carbonization is 10 MPa to 50 MPa. In still other embodiments, the pressure of the hydrothermal carbonization is 50 MPa to 150 MPa. In still other embodiments, the pressure of the hydrothermal carbonization is 100 MPa to 200 MPa. Feedstocks suitable as carbon sources for hydrothermal carbonization are also known in the art. Such feedstocks for hydrothermal carbonization typically contain carbon and oxygen and include, but are not limited to, sugars, oils, biowastes, polymers, and polymer precursors as described elsewhere in this disclosure.

[0166] Thus, the present disclosure provides for the production of a composite silicon-carbon material in which the carbon scaffold material is a porous carbon material, silicon impregnation is achieved by contacting with a silicon-containing reactant, and a terminal carbon coating is formed by hydrothermal carbonization. For example, the method may comprise the steps of: a) mixing and storing polymer and / or polymer precursor materials for a period of time at a temperature sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material; c) subjecting the porous carbon material to elevated temperature in the presence of a silicon-containing reactant in a static or stirred reactor to form a silicon-impregnated carbon material; d) hydrothermally carbonizing the silicon-impregnated carbon material to obtain a composite comprising a silicon-impregnated carbon material end-capped by hydrothermal carbonization, and suspending particles of the silicon alloy in the liquid medium. may have

[0167] Without being bound by theory, it is important that the surface of carbon particles must achieve the desired temperature to achieve the desired degree of reaction and deposition by silicon-containing gas.Conventional engineering principles show that it is difficult to heat the inside and outside of a particle, for example, the particle is heated via convection heating (possibly heating from the outside surface, including but not limited to microwave or other mechanisms including radiation heating), and then the temperature inside the particle is heated via conductive heating from the outside to the inside of the carbon particle.In the case of porous particles, it is not clear that the inside of the particle is heated at the same time as the outside, as long as it has a surface area that has equal access to gas molecules that collide with the carbon on the particle surface and impart heat via convection.

[0168] Without being bound by theory, the reaction conditions are such that the mean free path length of the silicon-containing gas is comparable to or less than the diameter and / or depth of the pores desired to be filled. Such cases are known in the art to be controlled by Knudsen diffusion, a means of diffusion that occurs when the scale length of the system is equal to or less than the mean free path of the particles involved. Consider the diffusion of gas molecules through very small capillary pores. If the pore dimensions are smaller than the mean free path of the diffusing gas molecules and the density of the gas is low, the gas molecules will often collide with the pore walls adjacent to each other. This method is known as Knudsen flow or Knudsen diffusion. The Knudsen number is a good measure of the relative importance of Knudsen diffusion. A Knudsen number much larger than 1 indicates that Knudsen diffusion is important. In practice, Knudsen diffusion only applies to gases, since the mean free path of the molecules in the liquid state is very small, typically close to the diameter of the molecules themselves. If the pore dimensions are much larger than the mean free path length of the gas, the diffusion is characterized as Fisk diffusion.

[0169] This method can vary for deposition methods, for example, it can be ambient pressure or about 101 kPa. In certain embodiments, the pressure can be less than ambient pressure, for example, less than 101 kPa, for example, less than 10.1 kPa, for example, less than 1.01 kPa. In certain embodiments, the gas comprises a mixture of a silicon-containing deposition gas and an inert gas, for example, a combination of silane and nitrogen. In this case, the partial pressure of the deposition gas can be less than 101 kPa, for example, less than 10.1 kPa, for example, less than 1.01 kPa. In certain embodiments, the pressure and temperature are such that the silicon-containing gas is in a supercritical state.

[0170] Thus, in certain embodiments, the silicon-containing reactant can be supercritical silane, for example, silane at a temperature greater than about 270 K (-3 C) and a pressure greater than about 45 bar. In further embodiments, the silicon-containing reactant can be supercritical silane, for example, silane at a temperature between 0 and 100° C. and a pressure between 45 and 100 bar. In further embodiments, the silicon-containing reactant can be supercritical silane, for example, silane at a temperature between 100 and 600° C. and a pressure between 45 and 100 bar. In further embodiments, the silicon-containing reactant can be supercritical silane, for example, silane at a temperature between 300 and 500° C. and a pressure between 50 and 100 bar. In further embodiments, the silicon-containing reactant can be supercritical silane, for example, silane at a temperature between 400 and 550° C. and a pressure between 50 and 80 bar.

[0171] In certain embodiments, both pressure and temperature are varied over time within the course of silicon impregnation of the porous carbon scaffold. For example, the porous carbon scaffold can be maintained at a temperature and pressure, below or above ambient temperature and below ambient pressure. In this case, the combination of low pressure and high temperature allows for desorption of volatile components that facilitate access for silicon-containing reactants that could potentially clog or otherwise occupy the porosity within the porous carbon scaffold. Examples of temperature and pressure conditions include, for example, 50-900°C, 0.1-101 kPa, and various combinations thereof. These conditions can be used as a first stage in the absence of silicon-containing reactants, followed by a second stage of temperature and pressure in the presence of silicon-containing reactants. Examples of the latter temperature and pressure ranges are found throughout this disclosure.

[0172] CVD can be accomplished through various modes according to the art. For example, CVD can be performed in a static mode, where the particles are not agitated and the CVD gas flows over or around the particles to be coated or otherwise permeates them. In other exemplary embodiments, the particles can be fluidized, for example, CVD can be performed in a fluidized bed reactor. As known in the art, a variety of different reactor designs can be employed in this context, including but not limited to elevator kilns, roller hearth kilns, rotary kilns, box kilns, and fluidized bed designs. These designs can be combined with various silicon-containing gases used as deposition gases, including but not limited to silane, disilane, trisilane, tetrasilane, chlorosilane, dichlorosilane, trichlorosilane, tetrachlorosilane, etc.

[0173] In the case of rotary kilns, various methods are known to facilitate proper dispersion and tumbling of particles within the reactor, providing maximum contact between the porous carbon and the silicon-containing reactants. These methods include equipment modifications such as lifters, helical flights, various screw / propeller designs, etc. Also known in the art are strategies for feeding additional non-reactive particles into the rotary kiln to promote dispersion and minimal agglomeration of the porous carbon scaffold particles.

[0174] CVD process can also use microwave to heat carbon particles to be processed.Therefore, by adopting engineering design principles known in the art, the above reactor configuration can also be combined with microwave as part of the process.Without being bound by theory, carbon particles are efficient microwave absorbers, and it is possible to understand a reactor in which the particles are irradiated with microwaves to heat them before the introduction of silicon-containing gas that attaches to the particles.

[0175] E. Dielectric heating Dielectric heating is a method by which the application of high frequency alternating electric fields or radio or microwave electromagnetic radiation heats dielectric materials. Molecular rotation occurs in materials containing polar molecules with electric dipole moments, which causes them to align in an electromagnetic field. When the electromagnetic field is oscillating, these molecules rotate continuously by aligning, as they are in an electromagnetic wave or rapidly oscillating electric field. This is called dipole rotation or dipolar polarization. When the electromagnetic field is alternating, the molecules reverse direction. As the rotating molecules push, pull, and collide with other molecules (via electric forces), they distribute energy to neighboring molecules and atoms in the material. Once distributed, this energy manifests as heat.

[0176] Temperature is related to the average kinetic energy of the atoms or molecules in a material, and by agitating the molecules in this way, the temperature of the substance increases. Dipole rotation is therefore the mechanism by which energy in the form of electromagnetic radiation can increase the temperature of an object. Dipole rotation, a mechanism usually referred to as dielectric heating, is most widely observable in microwave ovens, which act most effectively on liquid water, and to a much lesser extent on fats and sugars, as well as other carbon-containing substances.

[0177] Dielectric heating involves the heating of an electrically insulating material due to dielectric losses. A changing electric field across the material dissipates energy as the molecules attempt to align with the continuously changing electric field. This changing electric field may be caused by electromagnetic waves propagating in free space (as in a microwave oven) or by a rapidly alternating electric field in a capacitor. In the latter case, there are no freely propagating electromagnetic waves and one can see a changing electric field similar to an electrical component in the near field of an antenna. In this case, the heating is achieved by changing the electric field in a capacitive cavity at radio frequencies (RF), but at frequencies where no actual radio waves are generated or absorbed. In this sense, the effect is a direct electrical analogue of magnetic induction heating, which is also a near field effect (does not involve radio waves).

[0178] Frequencies in the range of 10-100 MHz are necessary to cause efficient dielectric heating, but higher frequencies work equally well, and in some materials (especially liquids), lower frequencies often have a significant heating effect due to more conventional mechanisms. Dielectric heating at low frequencies requires a distance from the electromagnetic emitter to the absorber of less than 1 / 2π ≒ 1 / 6 of the wavelength, as the near-field effect. Hence the contact or near-contact method. Usually, very large capacitors can be effectively used between metal plates, sandwiching the object to be heated (usually non-metallic) and taking into account the location of the dielectric of the object to be heated (usually non-metallic). However, actual electrical contact is not necessary to heat the dielectric inside the capacitor, because the electric field created inside the capacitor with a voltage applied does not require electrical contact between the capacitor plates and the (non-conducting) dielectric material between the plates. Because low frequency electric fields penetrate non-conductive materials much more deeply than microwaves, heating pockets of water and living matter inside dry materials like wood, they can be used to rapidly heat and prepare many non-conductive foods and produce, as long as they fit between the capacitor plates.

[0179] At very high frequencies, the wavelength of the electromagnetic field becomes shorter than the distance between the metal walls of the heating cavity, or even smaller than the dimensions of the walls themselves. This is the case in microwave ovens. In such cases, conventional far-field electromagnetic waves (where the cavity no longer acts as a pure capacitor but acts as an antenna) form, are absorbed and heated, but the dipole rotation mechanism of thermal welding remains the same. However, microwaves are not as efficient at causing the heating effects of low-frequency fields that rely on slower molecular motions, such as those due to ion-drag forces.

[0180] Microwave heating is a subcategory of dielectric heating at frequencies above 100 MHz, where electromagnetic waves are launched from a small-dimensional emitter and can be guided through space to a target. Modern microwave ovens use electromagnetic waves with electric fields at much higher frequencies and shorter wavelengths than RF heaters. A typical domestic microwave oven operates at 2.45 GHz, but 915 MHz ovens also exist. This means that the wavelengths used for microwave heating are 12 or 33 cm (4.7 or 13.0 in). This provides highly efficient, but less penetrative, dielectric heating. A capacitor-like set of plates can be used at microwave frequencies, but is not necessary, since microwaves already exist as far-field electromagnetic radiation. Its absorption does not require the same proximity as a small antenna, as RF heating does. Therefore, the object to be heated (non-metallic) can simply be placed in the path of the wave and it can be heated in a non-contact manner.

[0181] Thus, microwave absorbing materials can convert electromagnetic waves into thermal energy and dissipate it. Without being bound by theory, the microwave absorption capacity of a material is primarily determined by its relative permittivity, relative permeability, electromagnetic impedance match, and microstructure of the material, e.g., its porosity and / or nanostructure or microstructure. When a beam of microwaves is irradiated onto the surface of a microwave absorbing material, a suitable match condition for the electromagnetic impedance can allow for nearly zero reflection of the incident microwaves, ultimately resulting in the transfer of thermal energy to the absorbing material.

[0182] F. Microwave heating of carbon materials Carbon materials can absorb microwaves, i.e., are easily heated by microwave radiation, i.e., infrared and radio waves in the region of the electromagnetic spectrum. More specifically, they are defined as waves with wavelengths between 0.001m and 1m, corresponding to frequencies between 300 and 0.3GHz. The ability of carbon to heat in the presence of a microwave electric field is defined by its dielectric tangent tanδ = ε'' / ε'. The dielectric tangent is composed of two parameters, the dielectric constant (or real permittivity) ε', and the dielectric loss factor (or imaginary permittivity) ε'', defined by ε = ε'-iε'' [where ε is the complex permittivity. ]. The dielectric constant (ε') determines how much of the incident energy is reflected and how much is absorbed, while the dielectric loss factor (ε'') measures the dissipation of electrical energy in the form of heat within the material. For optimal microwave energy coupling, a moderate value of ε' should be coupled to a high value of ε''' (and a high value of tanδ) to convert microwave energy into thermal energy. Thus, some materials do not have a high enough loss factor (transparent to microwaves) to allow dielectric heating, while others, for example some inorganic oxides and most carbon materials, are excellent microwave absorbers. On the other hand, conductive materials reflect microwaves. For example, graphite and highly graphitized carbon can reflect a significant proportion of microwave radiation. In the case of carbon, where the delocalized π electrons can move freely over a relatively large area, additional and very interesting phenomena can occur. The kinetic energy of some electrons can allow them to jump out of the material, resulting in the ionization of the surrounding atmosphere. At the macroscopic level, this phenomenon is recognized as spark or electric arc formation. However, at the microscopic level, these hot spots are actually plasmas. Most of these plasmas can be considered as microplasmas from the point of view of space and time, since they are confined to a small region of space and, finally, only a small part of the second. The intensive generation of such microplasmas can have important implications for the methods involved.

[0183] Without being bound by theory, heating of carbon materials by microwave heating offers many advantages over conventional heating, such as: (i) non-contact heating; (ii) energy transfer instead of heat transfer; (iii) rapid heating; (iv) selective material heating; (v) volumetric heating; (vi) rapid start-up and shut-down; (vii) heating from inside the material body; and (viii) higher levels of safety and automation. Carbon materials with high capacity to absorb microwave energy and convert it into heat are shown in Table 1 (courtesy of JA Menendez, A. Arenillas, B. Fidalgo, Y. Fernandez, L. Zubizarreta, EG Calvo, JM Bermudez, “Microwave heating processes involving carbon materials”, Fuel Processing Technology, 2010, 91 (1), 1-8). Table 1 shows the dielectric loss tangents of different carbon examples. As can be seen, the loss tangent of most carbons, except for coal, is higher than that of distilled water (tan δ=0.118 for distilled water at 2.45 GHz and room temperature).

[0184] [Table 1]

[0185] The potential for microwave absorption by carbon also allows for the potential for microwave enhancement of carbon-catalyzed reactions, i.e., reactions that occur on or within carbon particles. Without being bound by theory, there are at least two scenarios in which microwaves enhance such reactions on or within carbon particles: (i) reactions that require high temperatures, and (ii) reactions involving chemical compounds, such as organic compounds, that have low dielectric losses that prevent them from heating up sufficiently under microwave irradiation. In the context of the present invention, the carbon material acts as both a reactive surface (e.g., catalyst) and a microwave receptor.

[0186] G. Fabrication of silicon-carbon composites by microwave-enabled decomposition of silicon-containing moieties on porous carbon substrates The present invention describes a method for synthesizing a composite material from one or more microwave absorbing materials. Herein, the microwave absorbing material is heated by exposure to microwave radiation and introduced into one or more additional raw materials that pyrolyze within or in the pores of the microwave heated material. In a preferred embodiment, the microwave heated material is, for example, porous, for example, containing micropores, mesopores, or macropores, or a combination thereof. In a preferred embodiment, the porous inductively heated material is a carbon material. The porous microwave heated carbon material may be inherently capable of absorbing microwaves or may be doped with chemical species such that the doped material is capable of absorbing microwaves. Heating the porous substrate material by microwaves allows for localized heating of the substrate particles without directly heating other materials within the reactor system, for example, the material container, the reactor walls, and the atmosphere (gas) within the reactor. This localized heating allows for high efficiency and provides highly localized decomposition of the silicon-containing reactant raw materials. Suitable reactants in this regard include, but are not limited to, silicon-containing gases and silicon-containing liquids. In a preferred embodiment, the silicon-containing feedstock is silane gas. Thus, the method disclosed herein provides the advantage of producing homogeneous silicon composite particles.

[0187] In general, the present invention relates to composite materials in which silicon is deposited in the pore volume of a porous scaffold material that is a microwave absorber. The porous microwave absorbing scaffold material can include a variety of different materials. In certain preferred embodiments, the porous scaffold material is a porous carbon material having micropores, mesopores, and / or macropores. Specifically, the porous carbon material provides pores in the range of 5-1000 nm, and silicon is subsequently loaded into the pores. Accordingly, the present disclosure also relates to a method for producing a composite material in which silicon is deposited in the pore volume of a porous scaffold material. A schematic of the method is shown in FIG. 1. The resulting composites exhibit remarkably durable intercalation of lithium, providing optimized lithium storage and utilization. These novel composites are useful in any number of electrical energy storage devices, and can be used, for example, as electrode materials in lithium-based electrical energy storage devices, specifically lithium ion batteries. Electrodes comprising the novel composites disclosed herein exhibit high reversible capacity, high first cycle efficiency, high power performance, or any combination thereof. The inventors have found that such improved electrochemical performance is related to the dimensions of the silicon, the integrity of the silicon and carbon materials (silicon and carbon materials) during cycling, the formation of a stable SEI layer, the physicochemical properties of the scaffold materials, such as the surface area and pore volume properties of the carbon scaffold, and other properties, as well as the techniques used to manufacture and compound the materials.

[0188] Thus, in one embodiment, the present disclosure provides for the production of a novel composite material comprising a porous scaffold and silicon, the composite having durable lithium intercalation. For example, the production method may include the following steps: a) preparing a microwave absorbing porous scaffold material, the microwave absorbing porous scaffold material having a pore volume in the range of 5 to 1000 nm; b) heating the microwave absorbing porous scaffold material by microwaves in the presence of the silicon-containing feedstock to a temperature sufficient to allow decomposition of the silicon-containing feedstock to obtain a carbon material impregnated with silicon. It has the following structure.

[0189] Thus, in one embodiment, the present disclosure provides for the production of a novel composite material comprising carbon and silicon and having durable lithium intercalation. For example, the production method may include the following steps: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a microwave absorbing porous carbon material having a pore volume in the range of 5 to 1000 nm; c) heating the microwave absorbing porous carbon material by microwaves in the presence of the silicon-containing feedstock to a temperature sufficient to allow decomposition of the silicon-containing feedstock to obtain a carbon material impregnated with silicon: It has the following structure.

[0190] In another embodiment, the present disclosure provides for the preparation of a novel composite material having durable lithium intercalation, the composite comprising carbon and silicon doped with a microwave absorbing material. For example, the preparation method may include the following steps: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material having a pore volume in the range of 5 to 1000 nm; c) doping the porous carbon material with a microwave heatable material; d) heating the resulting microwave absorbing porous carbon material by microwaves in the presence of the silicon-containing feedstock to a temperature sufficient to permit decomposition of the silicon-containing feedstock to obtain a silicon-impregnated carbon material. It has the following structure.

[0191] In a related embodiment, the present disclosure provides for the production of novel composite materials having durable lithium intercalation, the composite comprising carbon and silicon made from a polymeric material that includes a microwave absorbing material. For example, the method of production may include the following steps: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material having a pore volume in the range of 5 to 1000 nm; c) heating the microwave absorbing porous carbon material by microwaves in the presence of the silicon-containing feedstock to a temperature sufficient to permit decomposition of the silicon-containing feedstock to obtain a silicon-impregnated carbon material. It has the following structure.

[0192] Thus, in one embodiment, the present disclosure provides for the production of a novel composite material having a layer of carbon surrounding a silicon-impregnated carbon material, with durable lithium intercalation. For example, the production method may include the following steps: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material having a pore volume in the range of 5 to 1000 nm; c) heating the microwave absorbing porous carbon material by microwaves in the presence of the silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to obtain a silicon-impregnated carbon material; d) applying a carbon layer onto the silicon-impregnated carbon material to obtain a carbon-coated silicon-impregnated carbon material. It has the following structure.

[0193] Thus, in one embodiment, the present disclosure provides for the production of a novel composite material with durable lithium intercalation, the composite having a layer of conductive polymer material surrounding a silicon impregnated carbon material. For example, the method of production may include the following steps: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a microwave absorbing porous carbon material having a pore volume in the range of 5 to 1000 nm; c) heating the microwave absorbing porous carbon material by microwaves in the presence of the silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing raw material to obtain a silicon-impregnated carbon material; d) applying a conductive polymer around the silicon impregnated carbon material to obtain a silicon impregnated carbon material further embedded within a conductive polymer network. It has the following structure.

[0194] Thus, the present disclosure provides novel compositions as well as methods for their preparation, which materials exhibit remarkably durable intercalation of lithium when incorporated into electrodes of lithium-based energy storage devices, in some embodiments, the lithium-based electrical energy storage device is a lithium-ion battery or a lithium-ion capacitor.

[0195] H. Coating of composite materials with conductive polymer materials The composite material including the porous silicon material can have various surface treatments or properties to further improve the electrochemical performance as defined by the capacity, stability and power performance. In one embodiment, the composite is covered by an ion-conducting polymer having a thickness of 1 nm to 10 microns. In another embodiment, the composite is covered by a ceramic protective coating having a thickness of 1 nm to 10 microns. In yet another embodiment, the composite is covered by an organic film having a thickness of 1 nm to 10 microns. The thickness can be measured using various techniques known in the art such as, but not limited to, XPS sputtering, FIB / SEM or SIMS.

[0196] The composite material can be coated with an ion-conducting polymer. Exemplary materials include, but are not limited to, polyaniline-based materials, polypyrrole-based materials, combinations of the two such as poly-pyrrole-co-aniline, polythiophene-based materials, oligomers, PEDOT-PSS, polyvinylidene fluoride and other vinylenes and fluorides, neoprene, silicones, urethanes, styrene-butadiene rubber-based materials, and other rubbers such as isoprene.

[0197] The composite material can be coated with a ceramic protective coating. Coating materials include, but are not limited to, oxide-based coatings such as alumina, titania, zirconia, chromium oxide, etc. The coating material may also be non-oxygen-containing such as carbides, nitrides, borides, and silicides. The purpose of the ceramic is to protect the surface of the composite material.

[0198] The composite material can be coated with an organic material. The organic material can be found in nature or synthetically synthesized. Examples of organic coating materials include, but are not limited to, lignin, cellulose, chitosan, polysaccharides, and lipids.

[0199] The process of coating particles can be readily accomplished by one of ordinary skill in the art. Commonly used methods include vapor deposition, e.g., atomic layer deposition, chemical vapor deposition, plasma-assisted deposition, physical vapor deposition, sputtering, spray drying, emulsion, spin coating, electrodeposition, and direct-particle selective growth by seeds or other means.

[0200] A coating on a composite material is meant to prevent corrosion as well as provide mechanical stability during expansion / contraction. For this purpose, the hardness and elasticity of the material are important. These hardness and elasticity values ​​can be measured using methods known in the art. Depending on the choice of material, the Mohs hardness of the coating can be between 0 and 10. Without being bound by theory, the Mohs hardness of the coating can be either 0-5, 0-4, 0-4, 0-3, 0-2, or 0-1. In other examples, the Mohs hardness of the coating can range from 5-10, 6-10, 7-10, 8-10, or 9-10. The coating can exhibit an unusually high Mohs hardness >10. Without being bound by theory, the hardness can also be measured using the Vickers scale rather than Mohs hardness.

[0201] In yet another embodiment, the Young's modulus of the coating can be measured between 0 and 1210 GPa. In one embodiment, the Young's modulus of the coating is between 0.01 and 11 GPa, 0.01 and 5 GPa, 0.01 and 2 GPa, 0.01 and 0.5 GPa, 0.01 and 0.1 GPa, or 1 and 4 GPa. In another example, the Young's modulus of the coating can be greater than 11. The Young's modulus can be between 11 and 1000 GPa, 20 and 1000 GPa, 50 and 1000 GPa, 100 and 1000 GPa, 200 and 1000 GPa, or 400 and 700 GPa.

[0202] The thickness of the coating can change the performance of the composite material and can be directly related to the physical properties of the coating. In one embodiment, the thickness of the coating is between 1 nm and 10 microns, between 1 nm and 5 microns, between 1 nm and 1 micron, between 1 nm and 50 nm. In another embodiment, the thickness of the coating is between 5 microns and 10 microns. In yet another embodiment, the coating is a monoatomic monolayer.

[0203] The mass of the coating relative to the mass of the composite particle varies depending on the nature of both the coating and the composite particle. Without being bound by theory, the ratio of the mass of the coating to the mass of the composite particle can change the gravimetric and volumetric capacity of the material. In this embodiment, the mass of the composite particle refers to any or all materials that are not considered conductive polymer or ceramic coatings. In one embodiment, the ratio of the mass of the coating to the mass of the composite particle is less than 1:50. In other embodiments, the ratio of the mass of the coating to the mass of the composite particle is between 1:50 and 1:1, between 1:50 and 1:5, between 1:50 and 1:10, between 1:50 and 1:20, between 1:20 and 1:30. The ratio of the mass of the coating to the mass of the composite particle can be greater than 1:1, indicating that there is more coating than composite material.

[0204] The volume of the coating relative to the volume of the composite particle varies depending on the nature of both the coating and the composite particle. Without being bound by theory, the ratio of the volume of the coating to the volume of the composite particle can change the gravimetric and volumetric capacity of the material. In this embodiment, the volume of the composite particle refers to any or all of the material that is not considered a conductive polymer or ceramic coating. In one embodiment, the ratio of the volume of the coating to the volume of the composite particle is less than 1:50. In another embodiment, the ratio of the volume of the coating to the volume of the composite particle is between 1:50 and 1:1, between 1:50 and 1:5, between 1:50 and 1:10, between 1:50 and 1:20, between 1:20 and 1:30. In yet another embodiment, the ratio of the volume of the coating to the volume of the composite particle can be greater than 1:1, indicating that there is more coating than composite material.

[0205] The oxygen content in the coating on the composite material can be less than 80%, for example less than 70%, for example less than 60%, for example less than 50%, for example less than 40%, for example less than 30%, for example less than 20%, for example less than 20%, for example less than 10%. In one embodiment, the oxygen content in the coating on the composite material is 10-80%. In one embodiment, the oxygen content in the coating on the composite material is 20-70%. In one embodiment, the oxygen content in the coating on the composite material is 30-60%. In one embodiment, the oxygen content in the coating on the composite material is 40-50%. In yet another embodiment, the oxygen content in the coating on the composite material is less than 10%.

[0206] The nitrogen content in the coating on the composite material can be less than 50%, such as less than 30%, such as less than 20%, such as less than 15%, such as less than 10%, such as less than 5%, such as less than 1%, such as less than 0.1%. In an embodiment, the nitrogen content in the coating on the composite material is 1-30%. In an embodiment, the nitrogen content in the coating on the composite material is 1-20%. In an embodiment, the nitrogen content in the coating on the composite material is 1-10%. In an embodiment, the nitrogen content in the coating on the composite material is 5-10%.

[0207] In certain embodiments, the conductive polymer is pyrolyzed to give a pyrolyzed conductive polymer coating. There are various embodiments in which the conductive polymer can be added as a second carbon composite to the nanofeatures impregnated into the carbon scaffold and / or the composite of silicon with nano-dimensions and nano-features. For example, the silicon-carbon composite can be suspended in a solvent containing dissolved conductive polymer, and the suspension can then be dried as known in the art. In another embodiment, solid particles of the conductive polymer can be mixed with solid silicon particles, and the mixture of particles is stored at an elevated temperature. In a preferred embodiment, the temperature is near or above the glass transition temperature of the polymer. In an additional preferred embodiment, the temperature is near or above the softening temperature of the polymer. In an additional preferred embodiment, the temperature is near or above the melting temperature of the polymer. The elevated temperature can be about 100°C or about 120°C, or about 140°C or about 160°C, about 180°C, or about 200°C. Pyrolysis can be carried out at high temperatures as known in the art, for example, at 300° C., or 350° C., or 400° C., or 450° C., or 500° C., or 600° C., or 700° C., or 800° C. In certain embodiments, the nanofeatures or nanofeatures and nano-sized silicon can be pyrolyzed at 850° C., 900° C., 1000° C., 1050° C., or 1100° C. Exemplary conductive polymers include, but are not limited to, polyacrylonitrile (PAN), polyaniline, polypyrrole, polyacetylene, polyphenylene, polyphenylene sulfide, polythiophene, poly(fluorene), polypyrenes, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylene sulfide) (PPS), poly(p-phenylenevinylene) (PPV), and mixtures thereof. The ratio of silicon to conductive polymer for nanofeatures or nanofeatures and nanodimensions can be varied, for example, from 95:5 to 9:95.In certain embodiments, the ratio of silicon to conductive polymer is from 95:5 to 60:40, or from 90:10 to 70:30.

[0208] In another embodiment, the present disclosure provides for the manufacture of composite silicon-carbon materials. The silicon material is a nano-sized silicon material or a nano-sized silicon material with nano-sized features that is impregnated into a carbon scaffold according to the methods generally described herein, and the resulting silicon carbon composite is further coated with a second carbon coating, which is achieved by applying a conductive polymer. In a particular embodiment, the conductive polymer is pyrolyzed to achieve a pyrolyzed conductive polymer coating. There are various embodiments in which the conductive polymer can be composited with the nano-features and / or nano-features and nano-sized silicon carbon composites. For example, the silicon carbon composite can be suspended in a solvent containing dissolved conductive polymer, and the suspension can then be dried as known in the art. In another embodiment, solid particles of the conductive polymer can be mixed with solid silicon carbon composite particles, and the mixture of particles is stored at an elevated temperature. In a preferred embodiment, the temperature is near or above the glass transition temperature of the polymer. In an additional preferred embodiment, the temperature is near or above the softening temperature of the polymer. In an additional preferred embodiment, the temperature is near or above the melting temperature of the polymer. The elevated temperature can be about 100° C., or about 120° C., or about 140° C., or about 160° C., or about 180° C., or about 200° C. Pyrolysis can be carried out at elevated temperatures as known in the art, for example, 300° C., or 350° C., or 400° C., or 450° C., or 500° C., or 600° C., or 700° C., or 800° C. In certain embodiments, the nanofeatures or the mixture of nanofeatures and nano-sized silicon can be pyrolyzed at 850° C., 900° C., 1000° C., 1050° C., or 1100° C.Exemplary conductive polymers include, but are not limited to, polyacrylonitrile (PAN), polyaniline, polypyrrole, polyacetylene, polyphenylene, polyphenylene sulfide, polythiophene, poly(fluorene), polypyrenes, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylene sulfide) (PPS), poly(p-phenylene vinylene) (PPV), and mixtures thereof. The ratio of nanofeatures or nanofeatures and nanodimensions of silicon to the composite can be varied, for example, from 95:5 to 9:95. In certain embodiments, the ratio of composite to conductive polymer is 95:5 to 60:40, or 90:10 to 70:30.

[0209] I. Electrochemical performance of the composite with highly durable lithium insertion As mentioned above, the present disclosure relates to composites having a core of a porous carbon scaffold, nanosilicon impregnated or otherwise introduced by CVD in the presence of silane gas or produced using other suitable techniques, on top of the scaffold core, and further, any final coating, e.g., carbon, achieved by CVD in the presence of propane or by other suitable techniques, or a coating with a conductive polymer. Such composites exhibit very durable intercalation of lithium and are extremely useful as anode materials for lithium-based (or sodium-based) or other electrical storage devices. Without being bound by theory, it is believed that the nano-dimensional silicon resulting from the filling in the desired pore volume structure of the porous carbon scaffold (e.g., silicon-filled pores in the range of 5-1000 nm or other ranges disclosed herein), together with the advantageous properties of the other components of the composite, including the carbon or conductive polymer coating, can provide composites with different and advantageous properties, at least in part, depending on the method of its preparation, and by variation of the manufacturing parameters, to achieve electrochemical performance, for example, when the composite has an anode of a lithium ion energy storage device.

[0210] In certain embodiments, the electrochemical performance of the composites disclosed herein is tested in half cells. Alternatively, the performance of the composites with highly durable lithium intercalation disclosed herein is tested in full cells, such as full coin cells, full pouch cells, prismatic cells, or other battery configurations known in the art. The anode composition including the composites with highly durable lithium intercalation disclosed herein can further include various species as known in the art. Additional formulation components include, but are not limited to, the group consisting of conductive additives, such as conductive carbons such as Super P, Ketjen Black carbon, conductive polymers, etc., binders, such as styrene-butadiene rubber sodium carboxymethyl cellulose (SBR-Na CMC), polyvinylidene fluoride (PVDF), etc., and combinations thereof. Various types and species of electrodes are known in the art. The weight percent of active material in the electrode can vary, for example, in the range of 1-5%, for example, 5-15%, for example, 15-25%, for example, 25-35%, for example, 35-45%, for example, 45-55%, for example, 55-65%, for example, 65-75%, for example, 75-85%, preferably 85-95%. In a preferred embodiment, the active material comprises 80-95% of the electrode. In a particular embodiment, the amount of conductive additive in the electrode can vary, for example, in the range of 1-5%, for example, 5-15%, for example, 15-25%, preferably 25-35%. In a preferred embodiment, the amount of conductive additive in the electrode is 5-25%. In a particular embodiment, the amount of binder can vary, for example, 1-5%, for example, 5-15%, for example, 15-25%, for example, 25-35%. In a particular embodiment, the amount of conductive additive in the electrode is 5-25%.

[0211] The composites with highly durable lithium intercalation disclosed herein improve the properties of any number of electrical energy storage devices, for example, the composites with highly durable lithium intercalation disclosed herein have been shown to improve the first cycle efficiency of lithium-based batteries. Thus, one embodiment of the present disclosure provides a composite with highly durable lithium intercalation disclosed herein, which has a first cycle efficiency of greater than 50% when the composite is incorporated into an electrode of a lithium-based energy storage device, such as a lithium-ion battery. For example, in some embodiments, a composite with a surface area of ​​50 m 2 The present invention provides a composite having highly durable intercalation of lithium as disclosed herein, greater than 100 mAh / g, wherein the carbon material has a first cycle efficiency of greater than 50% and a reversible capacity of at least 600 mAh / g when the material is incorporated into an electrode of a lithium-based energy storage device. In other embodiments, the first cycle efficiency is greater than 55%. In some other embodiments, the first cycle efficiency is greater than 60%. In still other embodiments, the first cycle efficiency is greater than 65%. In other embodiments, the first cycle efficiency is greater than 70%. In other embodiments, the first cycle efficiency is greater than 75%, and in other embodiments, the first cycle efficiency is greater than 80%, greater than 90%, greater than 95%, greater than 98%, or greater than 99%.

[0212] The silicon-carbon composite material may be prelithiated as known in the art. In certain embodiments, the prelithiation is accomplished electrochemically. For example, in a half cell, a lithiated anode comprising a porous silicon material may be prelithiated before assembly into a full-cell lithium-ion battery. In certain embodiments, the prelithiation is accomplished by doping the cathode with a lithium-containing compound, e.g., a lithium-containing salt. Examples of suitable lithium salts in this context include, but are not limited to, dilithium tetrabromonickelate(II), dilithium tetrachlorocaprate(II), lithium azide, lithium benzoate, lithium bromide, lithium carbonate, lithium chloride, lithium cyclohexanebutyrate, lithium fluoride, lithium formate, lithium hexafluoroarsenate(V), lithium hexafluorophosphate, lithium hydroxide, lithium iodide, lithium iodate, lithium metaborate, lithium perchlorate, lithium phosphate, lithium sulfate, lithium tetraborate, tetrachloroaluminate, lithium tetrafluoroborate, lithium thiocyanate, lithium trifluoromethanesulfonate, lithium trifluoromethanesulfonate, and combinations thereof.

[0213] Anodes containing silicon-carbon composites can be paired with various cathode materials to form full-cell lithium-ion batteries. Examples of suitable cathode materials are known in the art. Examples of such cathode materials include LiCoO2 (LCO), LiNi 0.8 Co 0.15 Al 0.05 O2(NCA), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NMC), LiMn2O4 and variants (LMO), and LiFePO4 (LFP).

[0214] For full cell lithium ion batteries having an anode further comprising a silicon-carbon composite material, the cathode to anode pairing can be varied. For example, the cathode to anode capacity ratio can be varied in one embodiment from 0.7 to 1.3. The cathode to anode capacity ratio can be varied in the range of 0.7 to 1.0, such as 0.8 to 1.0, such as 0.8 to 1.0, such as 0.9 to 1.0, such as 0.95 to 1.0. In another embodiment, the cathode to anode capacity ratio can be varied in the range of 1.0 to 1.3, such as 1.0 to 1.2, such as 1.0 to 1.15, such as 1.0 to 1.1, such as 1.0 to 1.05. In another embodiment, the cathode to anode capacity ratio can be varied in the range of 0.8 to 1.2, such as 0.9 to 1.1, such as 0.95 to 1.05.

[0215] For a full-cell lithium-ion battery having an anode further comprising a silicon-carbon composite material, the voltage window for charging and discharging can be varied. In this regard, the voltage window can be varied as known in the art depending on various properties of the lithium-ion battery. For example, the selection of the cathode plays a role in the selected voltage window as known in the art. An example of the voltage window can be, for example, 2.0V to 5.0V, such as 2.5V to 4.5V, such as 2.5V to 4.2V, with respect to the potential versus Li / Li+.

[0216] For full-cell lithium-ion batteries having an anode further comprising a silicon-carbon composite material, the recipe for conditioning the cell can be modified as known in the art. For example, conditioning can be accomplished by one or more charge-discharge cycles at different rates, e.g., slower than the desired cycle rate. As known in the art, the conditioning step can also include opening the lithium-ion battery, venting gases generated during the conditioning process, and then resealing the lithium-ion battery.

[0217] In full cell lithium ion batteries having an anode further comprising a silicon-carbon composite material, the cycle rate can be varied as known in the art. For example, the rate can be C / 20 to 20C, such as C / 10 to 10C, such as C / 5 to 5C. In certain embodiments, the cycle rate is C / 10. In certain embodiments, the cycle rate is C / 5. In certain embodiments, the cycle rate is C / 2. In certain embodiments, the cycle rate is 1C. In certain embodiments, the cycle rate is 1C and the rate is periodically reduced to a slower rate, for example, using a C / 10 rate for every 20th cycle and cycling at 1C. In certain embodiments, the cycle rate is 2C. In certain embodiments, the cycle rate is 4C. In certain embodiments, the cycle rate is 5C. In certain embodiments, the cycle rate is 10C. In certain embodiments, the cycle rate is 20C.

[0218] In some of the above embodiments, the highly durable lithium intercalation composites disclosed herein also have a melting point of about 5 m. 2 / g~about 400m 2 / g, or a pore volume in the range of about 0.05 to about 1.0 cc / g, or both. For example, in some embodiments, the surface area is about 200 m 2 / g~about 300m 2 / g range or a surface area of ​​approximately 250 m 2 / g.

[0219] In certain embodiments, the highly durable lithium intercalation composites disclosed herein can be used to measure up to 200 m 2 / g, e.g., 100m 2 / g, e.g. 50m 2 In a further embodiment, the composite material has a surface area of ​​less than 30 m 2 / g, e.g., 20m 2 / g, e.g. 10m 2 / g, e.g. 5m 2 / g, e.g. 2m 2 / g, e.g. 1m 2 / g.

[0220] In another embodiment, the highly durable lithium intercalation composites disclosed herein can be used to 2 / g, e.g., 20m 2 / g, less than 10m 2 / g, e.g. 5m 2 / g, less than 1m 2 The composite material has a surface area of ​​less than about 1 m / g and, when incorporated into an electrode of a lithium-based energy storage device, has a first cycle efficiency of greater than 50% and a reversible capacity of at least 600 mAh / g. In other embodiments, the first cycle efficiency is greater than 55%. In other embodiments, the first cycle efficiency is greater than 60%. In still other embodiments, the first cycle efficiency is greater than 65%. In other embodiments, the first cycle efficiency is greater than 70%. In other embodiments, the first cycle efficiency is greater than 75%. In other embodiments, the first cycle efficiency is greater than 80%, greater than 90%, greater than 95%, greater than 98%, or greater than 99%. In some embodiments of the invention, the composite material also has a surface area of ​​less than about 1 m 2 / g~about 400m 2 / g, or a pore volume in the range of about 0.01 to about 1.0 cc / g, or both. For example, in some embodiments, the surface area is about 200 m 2 / g~about 300m 2 / g, or a surface area of ​​about 250 m 2 / g.

[0221] The electrochemical properties (e.g., first cycle efficiency, capacity, etc.) of the composites with highly durable intercalation of lithium disclosed herein can be determined by incorporation into electrodes known to those skilled in the art. The composites are electrochemically tested. Testing methods may vary depending on the electrode composition, as known in the art. In one example, pure silicon is tested between 1.0 V and 10 MV above and below at a current of 400 mA / g, after two formation cycles of 1.0 to 70 mV at a current of 200 mA / g, relative to the mass of the composite. Alternatively, the composites are tested by limiting the capacity to a predetermined value and measuring the stability and voltage variation of the composite.

[0222] The first cycle efficiency of the composites with highly durable insertion of lithium disclosed herein can be determined by comparing the lithium inserted into the anode during the first cycle with the lithium removed from the anode in the first cycle before lithiation modification. When insertion and removal are equal, the efficiency is 100%. As known in the art, the anode materials can be tested in half cells, where the electrolyte is 1:1 ethylene carbonate:diethyl carbonate (EC:DEC) in 1M LiPF6 when the counter electrode is lithium metal, and a commercially available polypropylene separator is used. In certain embodiments, the electrolyte can include various additives known to provide improved performance, such as fluoroethylene carbonate (FEC), or other related fluorinated carbonate compounds, or ester co-solvents, such as methyl butyrate, vinylene carbonate, and other electrolyte additives known to improve the electrochemical performance of silicon-containing anode materials.

[0223] The coulombic efficiency can be averaged over cycles 7 to 25, for example, when tested in half cells. In certain embodiments, the average efficiency of the composites with highly durable intercalation of lithium is greater than 0.9, or greater than 90%. In certain embodiments, the average efficiency is greater than 0.95 or greater than 95%. In preferred embodiments, the average efficiency is greater than 0.98 or greater than 98%. In preferred embodiments, the average efficiency is greater than 0.99 or greater than 99%. In even more preferred embodiments, the average efficiency is greater than 0.991 or greater than 99.1%. In even more preferred embodiments, the average efficiency is greater than 0.992% or greater than 99.2%. In even more preferred embodiments, the average efficiency is greater than 0.993% or greater than 99.3%. In even more preferred embodiments, the average efficiency is greater than 0.994 or greater than 99.4%. In even more preferred embodiments, the average efficiency is greater than 0.995 or greater than 99.5%. In further preferred embodiments, the average efficiency is greater than 0.996, or greater than 99.6%. In further preferred embodiments, the average efficiency is greater than 0.997, or greater than 99.7%. In further preferred embodiments, the average efficiency is greater than 0.998, or greater than 99.8%. In further preferred embodiments, the average efficiency is greater than 0.999, or greater than 99.9%. In further preferred embodiments, the average efficiency is greater than 0.9999, or greater than 99.99%.

[0224] In another embodiment, the present disclosure provides a composite material having highly durable lithium intercalation, wherein when the material is incorporated into an electrode of a lithium-based energy storage device, such as a lithium ion battery, the composite has a volumetric capacity (volumetric capacity density) (i.e., reversible capacity) of at least 400 mAh / cc, independent of the alloyed electrochemical modifier. The volumetric capacity of the composite can be calculated by multiplying the maximum gravimetric capacity (mAh / g) by the skeletal density in pycnometers (g / cc) without the presence of electrochemical modifiers. In other embodiments, the volumetric capacity is at least 450 mAh / cc. In some other embodiments, the volumetric capacity is at least 500 mAh / cc. In still other embodiments, the volumetric capacity is at least 550 mAh / cc. In still other embodiments, the volumetric capacity is at least 600 mAh / cc. In other embodiments, the volumetric capacity is at least 650 mAh / cc. In other embodiments, the volumetric capacity is at least 700 mAh / cc. In another embodiment, the volumetric capacity of the carbon component of the composite is between 700 and 1100 mAh / cc.

[0225] In another embodiment, the present disclosure provides a composite material with highly durable lithium intercalation, where the composite has a volumetric capacity (i.e., reversible capacity) of at least 800 mAh / cc when the material is incorporated into an electrode of a lithium-based energy storage device, such as a lithium-ion battery. The volumetric capacity of the composite can be calculated by multiplying the maximum gravimetric capacity (mAh / g) by the skeletal density in pycnometer (g / cc) prior to electrochemical testing. In other embodiments, the volumetric capacity is at least 900 mAh / cc. In some other embodiments, the volumetric capacity is at least 1000 mAh / cc. In still other embodiments, the volumetric capacity is at least 1100 mAh / cc. In still other embodiments, the volumetric capacity is at least 1200 mAh / cc. In other embodiments, the volumetric capacity is at least 1300 mAh / cc. In other embodiments, the volumetric capacity is at least 1400 mAh / cc, at least 1500 mAh / cc, at least 1600 mAh / cc, at least 1700 mAh / cc, at least 1800 mAh / cc, or at least 1900 mAh / cc. In still other embodiments, the volumetric capacity is between 2000 and 8000 mAh / cc. In still other embodiments, the volumetric capacity is between 4000 and 7000 mAh / cc. In certain embodiments, the composite has a volumetric capacity in the range of about 2500 mAh / cc to about 3500 mAh / cc.

[0226] In another embodiment, the present disclosure provides a composite material having highly durable lithium intercalation, where when the material is incorporated into an electrode of a lithium-based energy storage device, such as a lithium-ion battery, the composite has a volumetric capacity (volumetric capacity density) (i.e., reversible capacity), independent of the alloyed electrochemical modifier, of at least 150 mAh / cc. In other embodiments, the gravimetric capacity is at least 200 mAh / g. In some other embodiments, the gravimetric capacity is at least 300 mAh / g. In still other embodiments, the gravimetric capacity is at least 400 mAh / g. In other embodiments, the gravimetric capacity is at least 500 mAh / g. In other embodiments, the gravimetric capacity is at least 600 mAh / g, and in some other embodiments, the gravimetric capacity is at least 700 mAh / g, at least 800 mAh / g, at least 900 mAh / g, at least 1000 mAh / g, at least 1100 mAh / g, at least 1200 mAh / g, at least 1300 mAh / g, at least 1400 mAh / g, at least 1600 mAh / g, at least 1800 mAh / g, at least 2500 mAh / g, at least 2500 mAh / g, at least 2500 mAh / g, at least 2500 mAh / g, at least 2500 mAh / g, at least 2500 mAh / g, at least 2500 mAh / g, at least 3000 mAh / g, at least 3500 mAh / g. In still other embodiments, the gravimetric capacity is between 1200 and 3500 mAh / g. In certain embodiments, the composite material has a gravimetric capacity in the range of about 700 mAh / g to about 2000 mAh / g. In some particular embodiments, the composite material has a gravimetric capacity in the range of about 1000 mAh / g to about 1500 mAh / g. In some particular embodiments, the composite material has a gravimetric capacity in the range of about 550 mAh / g to about 750 mAh / g. In some particular embodiments, the composite material has a gravimetric capacity in the range of 400 mAh / g to about 500 mAh / g. Some examples of any of the composite materials can include an electrochemical modifier as described in more detail below.

[0227] J. Physicochemical properties of the composites with highly durable lithium intercalation affect their electrochemical performance As mentioned above, traditional lithium-based energy storage devices include graphitic anode materials. The disadvantages of graphitic carbon are numerous in lithium-ion batteries. In one disadvantage, graphite undergoes phase and volume changes during battery operation; that is, it is a material that physically expands / contracts when lithium is inserted, but also physically moves individual sheets laterally to maintain a low-energy storage state. Second, graphite has low capacity; given the regular crystalline structure of graphite, it requires six carbons to store one lithium ion; the structure cannot accommodate additional lithium. Third, it restricts the movement of lithium ions to a 2D plane, reducing the kinetics and rate capability of the material in the battery. This means that graphite does not perform well at the high rates at which power is required. This power disadvantage is one of the limiting factors in the use of lithium-ion batteries in all-electric vehicles.

[0228] Thus, without being bound by theory, there are physicochemical properties of the composite that allow for very durable intercalation of lithium. Examples of important features in this context are the silicon content, morphology and dimensions within the composite, as described below throughout this disclosure.

[0229] In certain embodiments, the silicon particles embedded within the composite have nano-dimensional features that may have a characteristic length scale that is preferably less than 1 μm, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm, preferably less than 10 nm, preferably less than 5 nm.

[0230] In certain embodiments, the silicon embedded within the composite is in the shape of a sphere. In certain other embodiments, the porous silicon particles are non-spherical, for example, rod-like or fibrous structures. In a preferred embodiment, the silicon is present as a layer coating the interior of the pores within the porous carbon scaffold. The depth of this silicon layer can vary, for example, the depth is 5 nm to 10 nm, for example 5 nm to 20 nm, for example 5 nm to 30 nm, for example 5 nm to 33 nm, for example 10 nm to 30 nm, for example 10 nm to 50 nm, for example 10 nm to 100 nm, for example 10 to 150 nm, for example 50 nm to 150 nm, for example 100 to 300 nm, for example 300 to 1000 nm.

[0231] In a preferred embodiment, the silicon embedded in the composite is nano-sized and resides within the pores of the porous carbon scaffold. For example, the embedded silicon can be impregnated and deposited by CVD or other suitable methods into pores within porous carbon particles having pore sizes of 5-1000 nm, e.g., 10-500 nm, e.g., 10-200 nm, e.g., 10-100 nm, e.g., 33-150 nm, e.g., 20-100 nm. Other ranges of carbon pore sizes in terms of fractional pore volume are also contemplated, including micropores, mesopores, or macropores.

[0232] In certain embodiments, the porous silicon particles embedded within the composite material fill the pores within the porous carbon scaffold material. The percentage of pore volume within the porous carbon scaffold filled with silicon can vary. For example, the silicon embedded within the porous carbon scaffold material can occupy 5% to 15% of the total available pore volume within the porous carbon scaffold. In other embodiments, the silicon embedded within the porous carbon scaffold material can occupy 15% to 25% of the total available pore volume within the porous carbon scaffold. In other embodiments, the silicon embedded within the porous carbon scaffold material can occupy 25% to 35% of the total available pore volume within the porous carbon scaffold. In other embodiments, the silicon embedded within the porous carbon scaffold material can occupy 20% to 40% of the total available pore volume within the porous carbon scaffold. In other embodiments, the silicon embedded within the porous carbon scaffold material can occupy 25% to 50% of the total available pore volume within the porous carbon scaffold. In another embodiment, the silicon embedded within the porous carbon scaffolding material can occupy 30% to 70% of the total available pore volume within the porous carbon scaffold, for example, 30% to 60% of the total available pore volume within the porous carbon scaffold. In another embodiment, the silicon embedded within the porous carbon scaffolding material can occupy 60% to 80% of the total available pore volume within the porous carbon scaffold. In another embodiment, the silicon embedded within the porous carbon scaffolding material can occupy 80% to 100% of the total available pore volume within the porous carbon scaffold.

[0233] In a preferred embodiment, the silicon embedded within the porous carbon scaffold material is configured to occupy a portion of the total available pore volume within the porous carbon scaffold, with the remainder of the pore volume available to silicon and to expand upon lithium uptake. Without being bound by theory in this context, this remaining pore volume may or may not be accessible to nitrogen and therefore may or may not be observed when using nitrogen gas adsorption as disclosed herein.

[0234] Thus, in some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and composite particles comprising the porous carbon scaffold and embedded silicon have a pore size of at least 0.01 cm 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and the composite particle comprising the porous carbon scaffold and the embedded silicon has a pore volume of at least 0.1 cm. 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and the composite particle comprising the porous carbon scaffold and the embedded silicon has a pore volume of at least 0.2 cm. 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and the composite particle comprising the porous carbon scaffold and the embedded silicon has a pore volume of at least 0.4 cm 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and the composite particle comprising the porous carbon scaffold and the embedded silicon has a pore volume of at least 0.6 cm. 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and the composite particle comprising the porous carbon scaffold and the embedded silicon has a pore volume of at least 0.8 cm 3 / g pore volume.

[0235] Thus, in some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and a composite particle comprising the porous carbon scaffold and embedded silicon has a size of less than 0.5 cm 3In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and a composite particle comprising a porous carbon scaffold and embedded silicon has a pore volume of less than 0.4 cm 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and a composite particle comprising the porous carbon scaffold and embedded silicon has a pore volume of less than 0.3 cm 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and a composite particle comprising the porous carbon scaffold and embedded silicon has a pore volume of less than 0.2 cm 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and composite particles comprising the porous carbon scaffold and embedded silicon have a pore volume of less than 0.1 cm 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and composite particles comprising the porous carbon scaffold and embedded silicon have a pore volume of less than 0.05 cm. 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and composite particles comprising the porous carbon scaffold and embedded silicon have a pore volume of less than 0.02 cm. 3 In some embodiments, the silicon embedded within the porous carbon scaffold material occupies between 30% and 70% of the total available pore volume within the porous carbon scaffold, and composite particles comprising the porous carbon scaffold and embedded silicon have a pore volume of less than 0.01 cm. 3 / g.

[0236] In certain other embodiments, the silicon embedded in the pore volume of the porous silicon is substantially present in the macropores, as evidenced by the reduction in macropore volume in the composite material embedded in silicon, compared to the porous carbon scaffold material before adding silicon.Thus, in some embodiments, the embedded silicon results in at least 10% reduction in macropore volume, such as at least 20% reduction in macropore volume, such as at least 30% reduction in macropore volume, such as at least 40% reduction in macropore volume, such as at least 50% reduction in macropore volume, such as at least 60% reduction in macropore volume, such as at least 70% reduction in macropore volume, such as at least 80% reduction in macropore volume, such as at least 90% reduction in macropore volume.

[0237] In certain other embodiments, the silicon embedded in the pore volume of the porous silicon is substantially present in the mesopores, as evidenced by a reduction in mesopore volume in the silicon-embedded composite compared to the porous carbon scaffold before the addition of silicon.Thus, in some embodiments, the embedded silicon results in at least a 10% reduction in mesopore volume, such as at least a 20% reduction in mesopore volume, such as at least a 30% reduction in mesopore volume, such as at least a 40% reduction in mesopore volume, such as at least a 50% reduction in mesopore volume, such as at least a 60% reduction in mesopore volume, such as at least a 70% reduction in mesopore volume, such as at least a 80% reduction in mesopore volume, such as at least a 90% reduction in mesopore volume.

[0238] In certain other embodiments, the silicon embedded in the pore volume of the porous silicon is substantially present in the micropores, as evidenced by the reduction in the micropore volume in the silicon-embedded composite material compared to the porous carbon scaffold material before adding silicon.Thus, in some embodiments, the embedded silicon results in at least 10% reduction in micropore volume, such as at least 20% reduction in micropore volume, such as at least 30% reduction in micropore volume, such as at least 40% reduction in micropore volume, such as at least 50% reduction in micropore volume, such as at least 60% reduction in micropore volume, such as at least 70% reduction in micropore volume, such as at least 80% reduction in micropore volume, such as at least 90% reduction in micropore volume.

[0239] In certain embodiments, silicon is embedded in essentially all available reserve volume within the porous carbon scaffold particles, covering the surface of the particles, and the silicon loading represents more than 100% of the total pore volume of the porous carbon scaffold prior to the addition of silicon. For example, silicon loading in this context is more than 105%, such as more than 110%, for example more than 120%, for example more than 130%, for example more than 150%, for example more than 200%.

[0240] In certain embodiments, the pore volume distribution of the composite material is documented by high resolution transmission electron spectroscopy (HRTEM).

[0241] In certain embodiments, the composite material has less than 20% micropores, more than 30% mesopores, and more than 30% macropores. In certain embodiments, the composite material has less than 10% micropores, more than 30% mesopores, and more than 30% macropores. In certain embodiments, the composite material has less than 5% micropores, more than 30% mesopores, and more than 30% macropores. In certain embodiments, the composite material has less than 5% micropores, more than 40% mesopores, and more than 40% macropores. In certain embodiments, the composite material has less than 1% micropores, more than 40% mesopores, and more than 40% macropores.

[0242] In certain embodiments, the composite material has less than 10% micropores, more than 70% mesopores, and more than 20% macropores. In certain embodiments, the composite material has less than 10% micropores, more than 20% mesopores, and more than 70% macropores. In certain embodiments, the composite material has less than 10% micropores, more than 10% mesopores, and more than 80% macropores. In certain embodiments, the composite material has less than 10% micropores, more than 80% mesopores, and more than 10% macropores.

[0243] In certain embodiments, the composite material has less than 5% micropores, more than 70% mesopores, and more than 20% macropores. In certain embodiments, the composite material has less than 5% micropores, more than 20% mesopores, and more than 70% macropores. In certain embodiments, the composite material has less than 5% micropores, more than 5% mesopores, and more than 80% macropores. In certain embodiments, the composite material has less than 5% micropores, more than 80% mesopores, and more than 10% macropores.

[0244] In certain embodiments, the composite material has less than 1% micropores, more than 70% mesopores, and more than 20% macropores. In certain embodiments, the composite material has less than 1% micropores, more than 20% mesopores, and more than 70% macropores. In certain embodiments, the composite material has less than 1% micropores, more than 10% mesopores, and more than 80% macropores. In certain embodiments, the composite material has less than 1% micropores, more than 80% mesopores, and more than 10% macropores.

[0245] In certain embodiments, the composite has less than 4% micropores, more than 84% mesopores, and less than 13% macropores.

[0246] In certain embodiments, the composite has a pore volume of 0.01 to 0.5, with a pore volume distribution having less than 20% micropores, more than 50% mesopores, and less than 30% macropores. 3 / g, with a pore volume distribution having less than 10% micropores, more than 60% mesopores, and less than 20% macropores. In certain embodiments, the composite has a pore volume of 0.1-0.3 cm 3 / g, with a pore volume distribution having less than 5% micropores, more than 70% mesopores, and less than 15% macropores. In certain embodiments, the composite has a pore volume of 0.1-0.3 cm 3 / g, with a pore volume distribution having less than 5% micropores, more than 85% mesopores, and less than 10% macropores.

[0247] In a preferred embodiment, the silicon is embedded in a portion of the porous carbon scaffold and the pores are covered with a coating that surrounds the composite particle, for example, the coating can include carbon or a conductive polymer, as described elsewhere in this disclosure. In this context, without being bound by theory, the pore volume may not be accessible to nitrogen and therefore may not be detectable by nitrogen adsorption. However, the void space within the resulting composite particle can be confirmed by other means, for example, by measuring the tap density, or envelope density, for example, by pycnometry techniques.

[0248] Thus, a composite material with highly durable lithium intercalation can contain silicon embedded within the porous carbon scaffold material at 30%-70% of the total available pore volume within the porous carbon scaffold, with the composite particles being less than 0.7 g / cm. 3 Less than, for example, 0.6 g / cm 3 Less than, for example, 0.5 g / cm 3 Less than, for example, 0.4 g / cm 3 Less than, for example, 0.3 g / cm 3 Less than, for example, 0.2 g / cm 3 Less than, for example, 0.15 g / cm 3 Less than, for example, 0.1 g / cm 3 has a tap density of less than

[0249] In some embodiments, a composite material having highly durable intercalation of lithium can include silicon embedded within a porous carbon scaffold material at 30%-70% of the total available pore volume within the porous carbon scaffold, and the composite particles can have a density of 2.1 g / cm 3 Less than, for example, 2.0 g / cm 3 Less than, for example, 1.9 g / cm 3 Less than 1.8g / cm 3 Less than, for example, 1.7 g / cm 3 Less than, for example, 1.6 g / cm 3 Less than, for example, 1.4 g / cm 3 Less than, for example, 1.2 g / cm 3 Less than, for example, 1.0 g / cm 3In certain embodiments, the composite material has a skeletal density, as measured by pycnometry, of less than 1.8 to 2.2 g / cm 3 , for example 1.9 to 2.1 g / cm 3 , for example 2.0 to 2.1 g / cm 3 It has a skeletal density of

[0250] The silicon content in the composite material exhibiting very durable lithium intercalation can be varied. For example, the silicon content in the composite can range from 5 to 95% by weight. In certain embodiments, the silicon content in the composite can range from 10% to 80%, such as 20% to 70%, such as 30% to 60%, such as 40% to 50%. In some embodiments, the silicon content in the composite can range from 10% to 50%, such as 20% to 40%, such as 30% to 40%. In other embodiments, the silicon content in the composite can range from 40% to 80%, such as 50% to 70%, such as 60% to 70%. In a specific embodiment, the silicon content in the composite can range from 10% to 20%. In a specific embodiment, the silicon content in the composite can range from 15% to 25%. In a specific embodiment, the silicon content in the composite can range from 25% to 35%. In a specific embodiment, the silicon content in the composite can be in the range of 35% to 45%. In a specific embodiment, the silicon content in the composite can be in the range of 45% to 55%. In a specific embodiment, the silicon content in the composite can be in the range of 55% to 65%. In a specific embodiment, the silicon content in the composite can be in the range of 65% to 75%. In a specific embodiment, the silicon content in the composite can be in the range of 75% to 85%.

[0251] Since the total pore volume (determined by nitrogen gas adsorption) may be related in part to the lithium ion storage, internal ionic dynamics, and available composite / electrolyte surface available for charge transfer, this is one parameter that can be tuned to obtain desired electrochemical properties.

[0252] Thus, the surface area and pore volume of a composite that exhibits extremely durable lithium intercalation can be varied. For example, a composite that exhibits extremely durable intercalation of lithium has a surface area of ​​10 m 2 / g~200m 2 / g. In certain embodiments, the surface area of ​​the complex may be in the range of 10 m 2 / g~100m 2 / g range, e.g. 20m 2 / g~200m 2 / g range, e.g. 20m 2 / g~150m 2 / g, e.g. 10m 2 / g~100m 2 In some embodiments, the surface area of ​​the complex may range from 20 m 2 / g~80m 2 / g, for example, 20m 2 / g~70m 2 / g, e.g. 30m 2 / g~70m 2 / g, e.g. 40m 2 / g~60m 2 / g range.

[0253] The pore volume of the composite, which shows extremely durable intercalation of lithium, is less than 0.01 cm 3 / g~0.2cm 3 In some embodiments, the pore volume of the composite material can be in the range of 0.01 cm3 / g. 3 / g~0.15cm 3 / g, e.g. 0.01 cm 3 / g~0.1cm 3 / g, e.g. 0.01 cm 3 / g~0.05cm 3 / g.

[0254] The pore volume distribution of the composite material exhibiting extremely durable lithium intercalation can vary, for example, with a % of micropores less than 30%, such as less than 20%, for example less than 10%, such as less than 5%, for example less than 4%, for example less than 3%, such as less than 2%, for example less than 1%, such as less than 0.5%, for example less than 0.2%, for example less than 0.1%. In certain embodiments, the composite material exhibiting extremely durable lithium intercalation has no detectable micropore volume.

[0255] In some embodiments, the pore volume distribution of the composite exhibiting highly durable intercalation of lithium has less than 30% mesopores, such as less than 20% mesopores, for example less than 10% mesopores, such as less than 5% mesopores, for example less than 4% mesopores, for example less than 3% mesopores, such as less than 2% mesopores, for example less than 1% mesopores, such as less than 0.5% mesopores, for example less than 0.2% mesopores, for example less than 0.1% mesopores. In some embodiments, there is no detectable mesopore volume in the composite exhibiting highly durable intercalation of lithium.

[0256] In some embodiments, the pore volume distribution of the composite material exhibiting highly durable intercalation of lithium has more than 50% macropores, such as more than 60% macropores, for example more than 70% macropores, such as more than 80% macropores, for example more than 90% macropores, such as more than 95% macropores, for example more than 98% macropores, such as more than 99% macropores, for example more than 99.5% macropores, such as more than 99.9% macropores.

[0257] Particular embodiments of the pore volume distribution of the composite material exhibiting very durable intercalation of lithium include various embodiments of the several paragraphs above. For example, the composite material exhibiting very durable intercalation of lithium has less than 30% micropores, less than 30% mesopores, and more than 50% macropores. In other embodiments, the composite material exhibiting very durable intercalation of lithium has less than 20% micropores, less than 20% mesopores, and more than 70% macropores. In other embodiments, the composite material exhibiting very durable intercalation of lithium has less than 10% micropores, less than 10% mesopores, and more than 80% macropores. In other embodiments, the composite material exhibiting very durable intercalation of lithium has less than 10% micropores, less than 10% mesopores, and more than 90% macropores. In other embodiments, the composite material exhibiting very durable intercalation of lithium has less than 5% micropores, less than 5% mesopores, and more than 90% macropores. In other embodiments, composite materials that exhibit highly durable intercalation of lithium have less than 5% micropores, less than 5% mesopores, and greater than 95% macropores.

[0258] In certain embodiments, the surface layer of the composite exhibits a low Young's modulus to accommodate the volumetric deformation associated with lithium ion uptake and insertion without destroying or otherwise providing additional opportunities for new SEI formation, In this context, the surface layer is sufficient to provide the composite with a Young's modulus of less than 100 GPa, such as less than 10 GPa, such as less than 1 GPa, such as less than 0.1 GPa.

[0259] In certain embodiments, the surface layer of the composite exhibits a low bulk modulus to accommodate the volumetric deformation associated with lithium ion uptake and insertion while not destroying or otherwise providing additional opportunities for new SEI formation. In this context, the surface layer is sufficient to provide the composite with a bulk modulus of less than 100 GPa, such as less than 10 GPa, such as less than 1 GPa, such as less than 0.1 GPa.

[0260] In certain other embodiments, the surface layer of the composite exhibits a high bulk modulus in order to constrain the volumetric deformation associated with the uptake or insertion of lithium ions, thereby avoiding destroying or otherwise denying additional opportunities for new SEI formation. In this context, the surface layer is sufficient to provide the composite with a bulk modulus of greater than 10 GPa, such as greater than 50 GPa, such as greater than 100 GPa, such as greater than 1000 GPa.

[0261] In some embodiments, the surface area of ​​the composite exhibiting a highly durable intercalation is greater than 500 m 2 In other embodiments, the surface area of ​​the composite material exhibiting very durable intercalation of lithium can be greater than 300 m / g in some embodiments. 2 In some embodiments, the surface area of ​​a composite material exhibiting very durable intercalation of lithium can be less than 200-300 m / g. 2 In some embodiments, the surface area of ​​the composite material exhibiting highly durable intercalation of lithium is between 100 and 200 m 2 In some embodiments, the surface area of ​​the composite material exhibiting highly durable intercalation of lithium is between 50 and 100 m 2 In some embodiments, the surface area of ​​the composite material exhibiting highly durable intercalation of lithium is between 10 and 50 m 2 In some embodiments, the surface area of ​​a composite material exhibiting highly durable intercalation of lithium is greater than 10 m 2 In some embodiments, the surface area of ​​a composite material exhibiting highly durable intercalation of lithium is less than 5 m 2 In some embodiments, the surface area of ​​a composite material exhibiting highly durable intercalation of lithium is less than 2 m 2 In some embodiments, the surface area of ​​a composite material exhibiting highly durable intercalation of lithium is less than 1 m 2In some embodiments, the surface area of ​​a composite material exhibiting very durable intercalation of lithium is less than 0.5 m / g in some embodiments. 2 In some embodiments, the surface area of ​​a composite that exhibits highly durable intercalation of lithium is less than 0.1 m 2 / g.

[0262] The surface area of ​​the composite material can be modified by activation. Activation methods can use steam, chemical activation, CO2 or other gases. Methods for activating carbon materials are well known in the art.

[0263] Volumetric and gravimetric capacities can be determined using any number of methods known in the art, for example, by incorporating an electrode half-cell with a lithium metal counter electrode, for example, in a coin cell. Gravimetric capacity is determined by dividing the measured capacity by the mass of the electrochemically active carbon material. Volumetric capacity is determined by dividing the measured capacity by the volume of the electrode, including binder and conductive additives. Methods for determining volumetric and gravimetric capacity are described in more detail in the Examples.

[0264] The composite can contain lithium metal in the pores of the composite, for example in the pores of the porous carbon within the composite, via doping or via electrochemical cycling. Lithium coverage within the pores is believed to be beneficial to both the capacity and cycling stability of the hard carbon. Coverage within the pores can result in novel nanofiber lithium. In some cases, lithium can be coated on the outside of the particle. External lithium coverage is detrimental to overall performance, as will be explained in the examples. The presence of both internal and external lithium metal can be measured by sectioning the material with a scanning electron microscope (SEM) and focused ion beam (FIB). In contrast to hard carbon in the SEM, metallic lithium can be easily detected. After cycling, the material can be sliced ​​and imaged when it has lithium inserted below 0V. In one embodiment, the material displays lithium within the micropores. In another embodiment, the material displays lithium within the mesopores. In yet another embodiment, the material does not display lithium coverage on the surface of the material. In yet another embodiment, silicon is stored in multiple pore sizes and shapes. The shape and pore size distribution of the material can uniquely and preferentially promote pore coverage prior to surface coating. Ideal pore sizes for lithium storage are described elsewhere in this disclosure.

[0265] The particle size distribution of the composites exhibiting very durable lithium intercalation is important in determining the power performance and volumetric capacity. Improved packing can lead to increased volumetric capacity. In an embodiment, the distribution can be Gaussian with a single peak, bimodal, or multimodal (>2 distinct peaks) in shape. The particle size properties of the composites can be described by D0 (smallest particle in the distribution), Dv50 (average particle size), and Dv100 (maximum dimension of the largest particle). The optimal combination of particle packing and performance will be some combination of the following size ranges:

[0266] In one embodiment, the Dv0 of the composite exhibiting highly durable intercalation of lithium can range from 1 nm to 5 microns. In another embodiment, the Dv0 of the composite ranges from 5 nm to 1 micron, or 5 nm to 500 nm, or 5 nm to 100 nm, or 10 nm to 50 nm. In another embodiment, the Dv0 of the composite ranges from 500 nm to 2 microns, 750 nm to 1 micron, or 1 micron to 2 microns. In yet another embodiment, the Dv0 of the composite ranges from 2 to 5 microns or greater than 5 microns. Particle size reduction in the above embodiments can be performed as known in the art, for example, by jet milling in the presence of various gases including air, nitrogen, argon, helium, supercritical steam, and other gases known in the art.

[0267] In one embodiment, the composite exhibits highly durable intercalation of lithium in the range of 5 nm to 20 microns. In another embodiment, the composite has a Dv50 in the range of 5 nm to 1 micron, 5 nm to 500 nm, 5 nm to 100 nm, or 10 nm to 50 nm. In another embodiment, the composite has a Dv50 in the range of 500 to 2 microns, 750 nm to 1 micron, or 1 micron to 2 microns. In yet another embodiment, the composite has a Dv50 in the range of 2 to 20 microns, or 3 microns to 10 microns, or 4 microns to 8 microns, or greater than 20 microns.

[0268] In one embodiment, the Dv100 of the composite exhibiting highly durable intercalation of lithium may range from 8 nm to 100 microns. In another embodiment, the Dv100 of the composite ranges from 5 nm to 1 micron, 5 nm to 500 nm, 5 nm to 100 nm, or 10 nm to 50 nm. In another embodiment, the Dv100 of the composite ranges from 500 to 2 microns, 750 nm to 1 micron, or 1 micron to 2 microns. In yet another embodiment, the Dv100 of the composite ranges from 2 to 100 microns, 5 to 50 microns, 8 to 40 microns, 10 to 35 microns, 15 to 30 microns, 20 to 30 microns, about 25 microns, or greater than 100 microns.

[0269] The span (Dv50) / (Dv90-Dv10), where Dv10, Dv50 and Dv90 represent the particle sizes at 10%, 50% and 90% of the volume distribution, can vary from 100 to 10, 10 to 5, 5 to 2, 2 to 1. In some embodiments, the span can be less than 1. The composite comprising the particle size distribution of the carbon and porous silicon materials can be, for example, bimodal or trimodal.

[0270] In yet other embodiments, the present disclosure provides a composite material that exhibits highly durable intercalation of lithium, where when the composite material is incorporated into an electrode of a lithium-based energy storage device, the composite material has a volumetric capacity that is at least 10% greater than when the lithium-based energy storage device includes a graphite electrode. In some embodiments, the lithium-based energy storage device is a lithium-ion battery. In other embodiments, the composite material has a volumetric capacity in a lithium-based energy storage device that is at least 5% greater, at least 10% greater, or at least 15% greater than the volumetric capacity of the same electrical energy storage device with a graphite electrode. In still other embodiments, the composite material has a volumetric capacity in a lithium-based energy storage device that is at least 20% greater, at least 30% greater, at least 40% greater, at least 50% greater, at least 200% greater, at least 100% greater, at least 150% greater, or at least 200% greater than the volumetric capacity of the same electrical energy storage device with a graphite electrode.

[0271] As is known in the art, the composite material may be pre-lithiated. The lithium atoms may or may not be separated from the carbon. The number of lithium atoms per 6 carbon atoms can be calculated by techniques known to those skilled in the art: #Li=Q×3.6×MM / (C%×F) [wherein Q is the lithium extraction capacity (mAh / g) measured at voltages between 5 mV and 2.0 V vs. lithium metal; MM is 72, the molecular weight of 6 carbons; F is the Faraday constant of 96,500 C% is the mass % of carbon present in the structure as measured by CHNO or XPS.]

[0272] Composite materials exhibiting highly durable intercalation of lithium can be characterized by a lithium atom to carbon atom ratio (Li:C) that can vary between about 0:6 and 2:6. In some embodiments, the Li:C ratio is about 0.05:6 to about 1.9:6. In other embodiments, the maximum Li:C ratio at which lithium is in ionic, not metallic, form is 2.2. In certain other embodiments, the Li:C ratio is about 1.2:6 to about 2:6, about 1.3:6 to about 1.9:6, about 1.4:6 to about 1.9:6, about 1.6:6 to about 1.8:6, about 1.7:6 to about 1.8:6. In other embodiments, the Li:C ratio is greater than 1:6, greater than 1.2:6, greater than 1.4:6, greater than 1.6:6, or even greater than 1.8:6. In other embodiments, the Li:C ratio is about 1.4:6, about 1.5:6, about 1.6:6, about 1.6:6, about 1.7:6, about 1.8:6, or about 2:6. In certain embodiments, the Li:C ratio is about 1.78:6.

[0273] In certain other embodiments, composite materials exhibiting highly durable intercalation of lithium have Li:C ratios that are about 1:6 to about 2.5:6, about 1.4:6 to about 2.2:6, or about 1.4:6 to about 2. In still other embodiments, the composite material may not necessarily contain lithium, but may have lithium uptake capacity (i.e., the ability to incorporate an amount of lithium) (e.g., can be used in cycling the material between two voltage conditions (for a lithium ion half cell), with exemplary voltage windows being 0 to 3 V, e.g., 0.005 V to 2.7 V, e.g., 0.005 V to 1 V, e.g., 0.005 V to 0.8 V). Without wishing to be bound by theory, it is believed that the lithium uptake capacity of the composite materials contributes to their superior performance in lithium-based energy storage devices. Lithium uptake capacity is expressed as the percentage of atoms of lithium incorporated by the composite. In certain other embodiments, composite materials exhibiting highly durable intercalation of lithium have a lithium uptake capacity in the range of from about 1:6 to about 2.5:6, from about 1.4:6 to about 2.2:6, or from about 1.4:6 to about 2:6.

[0274] In certain other embodiments, the lithium uptake capacity is in the range of about 1.2:6 to about 2:6, about 1.3:6 to about 1.9:6, about 1.4:6 to about 1.9:6, about 1.6:6 to about 1.8:6, or about 1.7:6 to about 1.8. In other embodiments, the lithium uptake capacity is greater than 1:6, greater than 1.2:6, greater than 1.4:6, greater than 1.6:6, or greater than 1.8:6. Even in other embodiments, the Li:C ratio is about 1.4:6, about 1.5:6, about 1.6:6, about 1.6:6, about 1.7:6, about 1.8:6, or about 2:6. In certain embodiments, the Li:C ratio is about 1.78:6.

[0275] In certain embodiments, the composite materials that exhibit highly durable intercalation are doped with an electrochemical modifier, such as lithium. Different methods of doping the lithium can include chemical reactions, electrochemical reactions, physical mixing of particles, gas phase reactions, solid phase reactions, and liquid phase reactions. In other embodiments, the lithium is in the form of lithium metal.

[0276] As described in more detail below, the surface functionality of the composite materials of the present disclosure, which exhibit very durable lithium intercalation, can be modified to obtain desired electrochemical properties. One property that can predict surface functionality is the pH of the composite material. The composite materials of the present disclosure have pH values ​​ranging from 1 to about 14, such as less than 5, 5 to 8, or greater than 8. In some embodiments, the pH of the composite material may be less than 4, less than 3, less than 2, or less than 1. In other embodiments, the pH of the composite material is about 5 to 6, 6 to 7, 7 to 8, 8 to 9, or 9 to 10. In still other embodiments, the pH is high and the pH of the composite material is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.

[0277] The pore size distribution of the carbon scaffold can be important to both the storage capacity of the material and the kinetics and power capabilities of the system, as well as the ability to incorporate large amounts of electrochemical modifiers. The pore size distribution can range from micro-meso-macropore sizes and can be either unimodal, bimodal or multimodal. Micropores with an average pore size of less than 1 nm can form additional storage sites as well as lithium (or sodium) ion diffusion pathways. Graphite sheets are typically 0.33 nm apart for lithium storage. Without wishing to be bound by theory, it is believed that a large amount of similarly sized pores can result in a graphite-like structure within the pores with additional hard carbon-type storage within the bulk structure. Mesopores are typically less than 100 nm. These pores are ideal locations for nanoparticle dopants such as metals, providing pathways for both electrolytes and conductive additives for ionic and electronic conduction. In some embodiments, the carbon materials have macropores greater than 100 nm that can be particularly suitable for large particle doping.

[0278] The pore size distribution of composite materials that exhibit very durable intercalation of lithium can be important to both the storage capacity of the material and the kinetic and power capacity of the system, as well as the ability to incorporate large amounts of electrochemical modifiers. The pore size distribution can range from micro-meso-macro and can be either unimodal, bimodal or multimodal. In some embodiments, the composite materials have micropores less than 100 nm that can be particularly suitable for lithium diffusion.

[0279] Thus, in one embodiment, the composite material has a partial pore volume of pores that are 1 nm or less that have at least 50% of the total pore volume, at least 75% of the total pore volume, at least 90% of the total pore volume, or at least 99% of the total pore volume. In another embodiment, the composite material has a partial pore volume of pores that are 10 nm or less that have at least 50% of the total pore volume, at least 75% of the total pore volume, at least 90% of the total pore volume, or at least 99% of the total pore volume. In another embodiment, the composite material has a partial pore volume of pores that are 50 nm or less that have at least 50% of the total pore volume, at least 75% of the total pore volume, at least 90% of the total pore volume, or at least 99% of the total pore volume.

[0280] In other embodiments, the composite material has a partial pore surface area of ​​pores that are 100 nm or less having at least 50% of the total pore surface area, at least 75% of the total pore surface area, at least 90% of the total pore surface area, or at least 99% of the total pore surface area. In another embodiment, the composite material has a partial pore surface area of ​​pores that are 100 nm or greater having at least 50% of the total pore surface area, at least 75% of the total pore surface area, at least 90% of the total pore surface area, or at least 99% of the total pore surface area.

[0281] In another embodiment, the composite material has pores predominantly in the range of 100 nm or less, such as 10 nm or less, such as 5 nm or less. Alternatively, the composite material has micropores in the range of 0-2 nm and mesopores in the range of 2-100 nm. The ratio of pore volume or pore surface area in the micropore range compared to the mesopore range can be in the range of 95:5 to 5:95.

[0282] The inventors have found that the degree of disorder in a composite material containing an electrochemical modifier can affect the electrochemical properties of the carbon material. Thus, controlling the degree of disorder in a composite material provides a possible means to improve the rate capability, as smaller crystallite dimensions can allow for less resistive lithium ion diffusion through the amorphous structure. The present invention includes embodiments that include both high and low levels of disorder.

[0283] Disorder, as recorded by Raman spectroscopy, is a measure of the size of crystallites found in both amorphous and crystalline structures (MA Pimenta, G. Dresselhaus, MS Dresselhaus, LG Canado, A. Jorio, and R. Saito, “Studying disorder in graphite-based systems by Raman spectroscopy,” Physical Chemistry Chemical Physics, vol. 9, no. 11, p. 1276, 2007). An exemplary Raman spectrum of carbon is shown in FIG. 4. For carbon structures, the crystallite size (L a ) can be calculated from the relative peak intensities of the D and G Raman shifts (Equation 1): L a (nm) = (2.4 × 10 -10 )λ 4 laser R -1 (1) Here, R=I D / I G (2)

[0284] R and L aThe values ​​of can vary in certain embodiments, and can affect the electrochemical properties of the carbon material, such as the capacity of the second lithium intercalation. (The second lithium intercalation is related to the first cycle efficiency because first cycle efficiency = (capacity at second lithium intercalation / capacity at second lithium intercalation) x 100.) For example, in some embodiments, R ranges from about 0 to about 1 or from about 0.50 to about 0.95. In other embodiments, R ranges from about 0.60 to about 0.90. In other embodiments, R ranges from about 0.80 to about 0.90. L a In certain other embodiments, L may vary and range from about 1 nm to about 500 nm. a In another embodiment, L is in the range of about 5 nm to about 100 nm or about 10 to about 50 nm. a is in the range of about 15 nm to about 30 nm, for example, in the range of about 20 to about 30 nm or about 25 to 30 nm.

[0285] In related embodiments, the electrochemical properties of the materials constituting the composite are related to the level of crystallinity as measured by X-ray diffraction (XRD). Raman measures the size of crystallites, whereas XRD records the level of periodicity of the bulk structure by scattering of incident X-rays. The invention includes materials that are non-graphitic (<10% crystalline) and semi-graphitic (10-50% crystalline). In some embodiments, the crystallinity of the materials ranges from about 0% to about 99%. The materials constituting the composite are less than 10% crystalline, less than 5% crystalline, or even less than 1% crystalline (i.e., highly amorphous). In other embodiments, the materials constituting the composite are 10%-50% crystalline. In still other embodiments, the materials constituting the composite are less than 50% crystalline, less than 40% crystalline, less than 30% crystalline, or less than 20% crystalline.

[0286] In related embodiments, the electrochemical properties of the materials constituting the composite are related to the level of crystallinity as measured by X-ray diffraction (XRD). The invention includes amorphous (<10% crystalline) and semi-crystalline (10-50% crystalline) and crystalline (>50%) materials. In some embodiments, the crystallinity of the materials constituting the composite ranges from about 0% to about 99%. The materials constituting the composite are less than 10% crystalline, less than 5% crystalline, or less than 1% crystalline (i.e., highly amorphous). In other embodiments, the materials constituting the composite are 10%-50% crystalline. In still other embodiments, the materials constituting the composite are less than 50% crystalline, less than 40% crystalline, less than 30% crystalline, or less than 20% crystalline.

[0287] In a related embodiment, the electrochemical performance of the composite is related to an experimental value R, calculated from small angle X-ray diffraction (SAXS), R=B / A, where B is the height of the bilayer peak and A is the baseline of a single graphene sheet measured by SAXS.

[0288] SAXS has the ability to measure interior pores that are possibly inaccessible by gas adsorption techniques, but where lithium storage is possible. In certain embodiments, the R-factor is less than 1, including a single layer of graphene. In other embodiments, the R-factor ranges from about 0.1 to about 20 or about 1 to 10. In still other embodiments, the R-factor ranges from 1 to 5, 1 to 2, or 1.5 to 2. In still other embodiments, the R-factor ranges from 1.5 to 5, 1.75 to 3, or 2 to 2.5. Alternatively, the R-factor is 10 or greater. SAXS patterns may also be analyzed by the number of peaks found between 10° and 40°. In some embodiments, the number of peaks determined by SAXS at low scattering angles is 1, 2, 3, or greater than 3.

[0289] In certain embodiments, the organic content of the materials that make up the composite can be manipulated to provide desired properties. For example, contact with a hydrocarbon compound such as cyclohexane can provide desired properties. Infrared spectroscopy (FTIR) can be used as a metric to determine the organic content of both the surface and bulk structures of the material. In one embodiment, the materials that make up the composite are essentially free of organic material. An essentially featureless FTIR spectrum is indicative of such an embodiment. In another embodiment, the carbon material that does not contain an electrochemical modifier contains organic material either on the surface or within the bulk structure. In such an embodiment, the FTIR spectrum generally shows large peaks and valleys that indicate the presence of organic content.

[0290] The organic content can have a direct relationship with the electrochemical performance and response of the material when it is placed in a lithium-containing device for energy storage. Materials that make up the composite with a flat FTIR signal (without organics) often display a low extraction peak in the voltage profile at 0.2V. As is well known in the art, the extraction voltage is typical of lithium dissolution (lithium stripping). In certain embodiments, the materials that make up the composite have organic content and the lithium dissolution plateau is absent or almost absent.

[0291] The composite material may also contain varying amounts of carbon, oxygen, hydrogen, and nitrogen as measured by gas chromatography CHNO analysis. In one embodiment, the carbon content of the composite is greater than 98% or even greater than 99.9% by weight as measured by CHNO analysis. In another embodiment, the carbon content of the composite ranges from about 10% to about 99.9% by weight of the total mass, such as from about 50 to about 98% by weight of the total mass. In other embodiments, the carbon content of the composite is 90 to 98%, 92 to 98% by weight, or greater than 95% by weight of the total mass. In yet other embodiments, the carbon content of the composite is 80 to 90% by weight of the total mass. In other embodiments, the carbon content of the composite is 70 to 80% by weight of the total mass. In yet other embodiments, the carbon content of the composite is 60 to 70% by weight of the total mass. In yet other embodiments, the carbon content of the composite is 50 to 60% by weight of the total mass. In yet other embodiments, the carbon content of the composite is 40 to 50% by weight of the total mass. In yet another embodiment, the carbon content of the composite is 30-40 wt% of the total mass. In yet another embodiment, the carbon content of the composite is 20-30 wt% of the total mass. In yet another embodiment, the carbon content of the composite is 10-20 wt% of the total mass. In yet another embodiment, the carbon content of the composite is 1-10 wt% of the total mass.

[0292] In another embodiment, the nitrogen content is in the range of 0-90 wt% based on the total mass of all components in the composite material as measured by CHNO analysis. In another embodiment, the nitrogen content is 1-10 wt% of the total mass. In yet another embodiment, the nitrogen content is 10-20 wt% of the total mass. In yet another embodiment, the nitrogen content is in the range of 20-30 wt% of the total mass. In another embodiment, the nitrogen content is greater than 30 wt%. In some specific embodiments, the nitrogen content is in the range of about 1% to about 6%, and in other embodiments, the nitrogen content is in the range of about 0.1% to about 1%. In some of the above embodiments, the nitrogen content is based on the weight of all components in the composite material relative to the total weight.

[0293] The carbon and nitrogen content can also be measured as the ratio of C:N (carbon atoms to nitrogen atoms). In one embodiment, the C:N ratio is in the range of 1:0.001 to 0.001:1 or 1:0.001 to 1:1. In one embodiment, the C:N ratio is in the range of 1:0.001 to 1:0.01. In yet another embodiment, the C:N ratio is in the range of 1:0.01 to 1:1. In yet another embodiment, the nitrogen content exceeds the carbon content, for example, the C:N ratio can be in the range of about 0.01:1 to about 0.1:1 or 0.1:1 to about 0.5:1.

[0294] Composite materials including silicon materials can also include varying amounts of carbon, oxygen, nitrogen, Cl, Na, to name a few, as measured by XPS analysis. In one embodiment, the carbon content is greater than 98% by weight, as measured by XPS analysis. In another embodiment, the carbon content is 50-98% by weight of the total mass. In yet another embodiment, the carbon content is 90-98% by weight of the total mass. In yet another embodiment, the carbon content is 80-90% by weight of the total mass. In yet another embodiment, the carbon content is 70-80% by weight of the total mass. In yet another embodiment, the carbon content is 60-70% by weight of the total mass.

[0295] In other embodiments, the carbon content is in the range of 10%-99.9%, 10%-99%, 10%-98%, 50%-99.9%, 50%-99%, 50%-98%, 75%-99.9%, 75%-99%, or 75%-98% based on the combined mass of all components in the carbon material, as measured by XPS analysis.

[0296] In another embodiment, the nitrogen content is in the range of 0 to 90% by weight, as measured by XPS analysis. In another embodiment, the nitrogen content is 1 to 75% by weight of the total mass. In another embodiment, the nitrogen content is 1 to 50% by weight of the total mass. In another embodiment, the nitrogen content is 1 to 25% by weight of the total mass. In another embodiment, the nitrogen content is 1 to 20% by weight of the total mass. In another embodiment, the nitrogen content is 1 to 10% by weight of the total mass. In another embodiment, the nitrogen content is 1 to 6% by weight of the total mass. In another embodiment, the nitrogen content is 10 to 20% by weight of the total mass. In another embodiment, the nitrogen content is 20 to 30% by weight of the total mass. In another embodiment, the nitrogen content is greater than 30% by weight.

[0297] The carbon and nitrogen content may also be measured as the C:N ratio by XPS. In one embodiment, the C:N ratio of the composite is in the range of 0.001:1 to 1:0.001. In one embodiment, the C:N ratio is in the range of 0.01:1 to 1:0.01. In one embodiment, the C:N ratio is in the range of 0.1:1 to 1:0.01. In one embodiment, the C:N ratio is in the range of 1:0.5 to 1:0.001. In one embodiment, the C:N ratio is in the range of 1:0.5 to 1:0.01. In one embodiment, the C:N ratio is in the range of 1:0.5 to 1:0.1. In one embodiment, the C:N ratio is in the range of 1:0.2 to 1:0.01. In one embodiment, the C:N ratio is in the range of 1:0.001 to 1:1. In another embodiment, the C:N ratio is in the range of 1:0.01 to 1:1. In yet another embodiment, the C:N ratio is from 1:0.01 to 1: 1. In yet another aspect, the nitrogen content exceeds the carbon content.

[0298] The carbon and phosphorus content of the composite can also be measured as the C:P ratio by XPS. In one embodiment, the C:P ratio of the composite ranges from 0.001:1 to 1:0.001. In one embodiment, the C:P ratio ranges from 0.01:1 to 1:0.01. In one embodiment, the C:P ratio ranges from 0.1:1 to 1:0.01. In one embodiment, the C:P ratio ranges from 1:0.5 to 1:0.001. In one embodiment, the C:P ratio ranges from 1:0.5 to 1:0.01. In one embodiment, the C:P ratio ranges from 1:0.5 to 1:0.01. In one embodiment, the C:P ratio ranges from 1:0.2 to 1:0.01. In one embodiment, the C:P ratio ranges from 1:0.001 to 1:1. In yet another embodiment, the C:P ratio ranges from 1:0.01 to 1:1. In yet another embodiment, the nitrogen content exceeds the carbon content.

[0299] XPS can also be used to detect individual bonds between elements. In the case of a composite, the interface between carbon and silicon can include CX bonds, where X is a primary element that can be alloyed with lithium (such as a C-Si bond for silicon electrochemical modifiers). The presence of CX can affect the performance of the material. The percentage of CX bonds in the composite can be characterized using XPS. In one embodiment, the percentage of CX bonds is 0% to 50% as measured by XPS. In another embodiment, the percentage of CX bonds is 0% to 10%, 0% to 5%, 0% to 3%, 0% to 2%, 0% to 1%, 1% to 2%, and in yet another embodiment, 10% to 50%, or greater than 50%. CX bonds also produce in situ materials that can be electrochemically alloyed with silicon.

[0300] Carbon materials, including composite materials, can include both sp3 and sp2 hybridized carbon. The percentage of sp2 hybridization can be measured by XPS with Auger spectroscopy as known in the art. For materials having less than 100% sp2, the remainder of the bonds are considered to be sp3. Carbon materials range from about 1% sp2 hybridization to 100% sp2 hybridization. Other embodiments include carbon materials that include about 25% to about 95% sp2, about 50% to about 75% sp2, about 50% to 95% sp2, about 50% to about 75% sp2, about 50% to about 75% sp2, or about 65% to about 95% sp2 or about 65% sp2.

[0301] In certain embodiments, XPS can be tested to determine the specific nature of the specific bond structure in the silicon that constitutes the composite. For example, XPS can be tested in the region near 100 eV to confirm the details of the Si 2p bond in the silicon structure. In certain embodiments, the silicon material includes elemental silicon that exhibits an XPS peak located at 99.4 eV. In certain embodiments, the silicon material includes Si3N4 that exhibits an XPS peak located at 101.7 eV. In certain embodiments, the silicon includes organosilicon that exhibits an XPS peak located at 10000 eV. In certain embodiments, the silicon includes organosilicon that exhibits an XPS peak located at 103.5 eV.

[0302] The composite material can also include an electrochemical modifier selected to optimize the electrochemical performance of the unmodified composite. The electrochemical modifier can be incorporated into the pore structure of the carbon material and / or on the surface of the porous carbon scaffold, into embedded silicon, or into the final layer of carbon, into a conductive polymer or coating, or can be incorporated in any number of other ways. For example, in some embodiments, the carbon material comprises a coating of electrochemical modifier (e.g., silicon or Al2O3) on the surface of the carbon material. In some embodiments, the carbon material comprises more than about 100 ppm of electrochemical modifier. In certain embodiments, the electrochemical modifier is selected from iron, tin, silicon, nickel, aluminum, and manganese.

[0303] In certain embodiments, the electrochemical modifier comprises an element capable of lithiating from 3 to 0 V versus lithium metal (e.g., silicon, tin, sulfur). In other embodiments, the electrochemical modifier comprises a metal oxide capable of lithiating from 3 to 0 V versus lithium metal (e.g., iron oxide, molybdenum oxide, titanium oxide). In yet other embodiments, the electrochemical modifier comprises an element that does not lithiate from 3 to 0 V versus lithium metal (e.g., aluminum, manganese, nickel, metal phosphates). In yet other embodiments, the electrochemical modifier comprises a non-metal element (e.g., fluorine, nitrogen, hydrogen). In yet other embodiments, the electrochemical modifier comprises any of the above electrochemical modifiers or any combination thereof (e.g., tin-silicon, nickel-titanium oxide).

[0304] The electrochemical regulator can be provided in a number of forms. For example, in some embodiments, the electrochemical regulator comprises a salt. In other embodiments, the electrochemical regulator comprises one or more elements in elemental form, such as elemental iron, tin, silicon, nickel, or manganese. In other embodiments, the electrochemical regulator comprises one or more elements in oxidized form, such as iron oxide, tin oxide, silicon oxide, nickel oxide, aluminum oxide, or manganese oxide.

[0305] In other embodiments, the electrochemical modifier comprises iron. In other embodiments, the electrochemical modifier comprises tin. In other embodiments, the electrochemical modifier comprises silicon. In some other embodiments, the electrochemical modifier comprises nickel. In still other embodiments, the electrochemical modifier comprises aluminum. In still other embodiments, the electrochemical modifier comprises manganese. In still other embodiments, the electrochemical modifier comprises Al2O3. In still other embodiments, the electrochemical modifier comprises titanium. In still other embodiments, the electrochemical modifier comprises titanium oxide. In still other embodiments, the electrochemical modifier comprises lithium. In still other embodiments, the electrochemical modifier comprises sulfur. In still other embodiments, the electrochemical modifier comprises phosphorus. In still other embodiments, the electrochemical modifier comprises molybdenum. In still other embodiments, the electrochemical modifier comprises germanium. In still other embodiments, the electrochemical modifier comprises arsenic. In still other embodiments, the electrochemical modifier comprises gallium. In still other embodiments, the electrochemical modifier comprises phosphorus. In still other embodiments, the electrochemical modifier comprises selenium. In still other embodiments, the electrochemical modifier comprises antimony. In yet another embodiment, the electrochemical modifier comprises bismuth. In yet another embodiment, the electrochemical modifier comprises tellurium. In yet another embodiment, the electrochemical modifier comprises indium.

[0306] Thus, in some embodiments, the composite material comprises more than one carbon allotrope, including hard carbon and a second allotrope, the carbon allotrope being selected from species including, but not limited to, graphite, amorphous carbon (soft and hard), C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene, and carbon fibers. In some embodiments, the second carbon form is graphite. In other embodiments, the second form is soft carbon. The ratio of the carbon material (e.g., hard carbon) to the second carbon allotrope can be tailored to suit any desired electrochemical application.

[0307] In certain embodiments, the mass ratio of the hard carbon to the second carbon allotrope in the composite ranges from about 0.01:1 to about 100:1. The mass ratio of the hard carbon to the second carbon allotrope ranges from about 1:1 to about 10:1 or about 5:1. In other embodiments, the mass ratio of the hard carbon to the second carbon allotrope ranges from about 1:10 to about 10:1. In other embodiments, the mass ratio of the hard carbon to the second carbon allotrope ranges from about 1:5 to about 5:1. In other embodiments, the mass ratio of the hard carbon to the second carbon allotrope ranges from about 1:3 to about 3:1. In other embodiments, the mass ratio of the hard carbon to the second carbon allotrope ranges from about 1:2 to about 2:1.

[0308] Multiple carbon allotropes can be combined in a single composite to further improve electrochemical performance. For example, hard carbon can be blended with both graphite and soft carbon to change density and capacity or first cycle efficiency. Three or more carbon allotropes have synergistic effects to produce unique structures and performance. In certain embodiments, the mass ratio of the hard carbon to the total mass of all other carbon allotropes in the composite ranges from about 0.01:1 to about 100:1. The mass ratio of the hard carbon to the total mass of all other carbon allotropes in the composite ranges from about 1:1 to about 10:1 or about 5:1. In other embodiments, the mass ratio of the hard carbon to the total mass of all other carbon allotropes in the composite ranges from about 1:10 to about 10:1. In other embodiments, the mass ratio of the hard carbon to the total mass of all other carbon allotropes in the composite ranges from about 1:5 to about 5:1. In another embodiment, the mass ratio of the hard carbon to the total mass of all other carbon allotropes in the composite ranges from about 1:3 to about 3: 1. In another embodiment, the mass ratio of the hard carbon to the total mass of all other carbon allotropes in the composite ranges from about 1:2 to about 2:1.

[0309] The electrochemical properties of the composite material can be modified, at least in part, by the amount of electrochemical modifier in the composite material. The electrochemical modifier is an alloy material such as silicon, tin, indium, aluminum, germanium, gallium. Thus, in some embodiments, the composite material comprises at least 0.10%, at least 0.25%, at least 0.50%, at least 1.0%, at least 5.0%, at least 10%, at least 25%, at least 50%, at least 75%, at least 90%, at least 95%, at least 99% or at least 99.5% electrochemical modifier. For example, in some embodiments, the composite material comprises 0.5%-99.5% carbon and 0.5%-99.5% electrochemical modifier. In a preferred embodiment, the composite material comprises 70%-99% silicon, such as in the range of 75%-95%, such as 80%-95%. The percentage of electrochemical modifier is calculated on a weight percent basis (wt%). In some other more specific embodiments, the electrochemical modifier comprises iron, tin, silicon, nickel and manganese. In preferred embodiments, the composite comprises 70%-99% silicon, such as in the range of 75%-95%, for example 80%-95%.

[0310] The unmodified carbon material has a purity not previously available in hard carbon materials. Without wishing to be bound by theory, it is believed that the high purity of the unmodified carbon material contributes to its superior electrochemical properties. In some embodiments, the unmodified carbon material contains low total TXRF impurities (excluding any intentionally included electrochemical modifiers). Thus, in some embodiments, the total TXRF impurity content of all other TXRF elements in the carbon material (excluding any intentionally included electrochemical modifiers) is less than 1000 ppm (as measured by proton induced x-ray emission). In other embodiments, the total TXRF impurity content of all other TXRF elements in the carbon material (excluding any intentionally included electrochemical modifiers) is less than 800 ppm, less than 500 ppm, less than 300 ppm, less than 200 ppm, less than 150 ppm, less than 100 ppm, less than 50 ppm, less than 25 ppm, less than 10 ppm, less than 5 ppm, or less than 1 ppm.

[0311] In addition to a low content of undesirable TXRF impurities, the disclosed unmodified carbon materials can include a high total carbon content. In some examples, in addition to carbon, the carbon materials can also include oxygen, hydrogen, nitrogen, and any electrochemical modifiers. In some embodiments, the materials include at least 75% carbon, 80% carbon, at least 90% carbon, at least 90% carbon, at least 90% carbon, at least 90% carbon, at least 90% carbon, at least 90% carbon, at least 95% carbon, at least 96% carbon, at least 97% carbon, at least 98% carbon, or at least 99% carbon, on a weight / weight basis. In some other embodiments, the carbon materials include less than 10% oxygen, less than 5% oxygen, less than 3.0% oxygen, less than 2.5% oxygen, less than 1% oxygen, or less than 0.5% oxygen, on a weight / weight basis. In other embodiments, the carbon material contains less than 10% hydrogen, less than 5% hydrogen, less than 2.5% hydrogen, less than 1% hydrogen, less than 0.5% hydrogen, or less than 0.1% hydrogen on a weight / weight basis. In other embodiments, the carbon material contains less than 5% nitrogen, less than 2.5% nitrogen, less than 1% nitrogen, less than 0.5% nitrogen, less than 0.25% nitrogen, or less than 0.01% nitrogen on a weight / weight basis. The oxygen, hydrogen, and nitrogen content of the disclosed carbon materials can be determined by combustion analysis. Techniques for determining elemental composition by combustion analysis are well known in the art.

[0312] The total ash content of the unmodified carbon material, in some instances, affects the electrochemical performance of the carbon material. Thus, in some embodiments, the ash content of the carbon material (excluding any intentionally included electrochemical modifiers) ranges from 0.1 wt% to 0.001 wt% ash. For example, in some specific embodiments, the ash content of the carbon material (excluding any intentionally included electrochemical modifiers) is less than 0.1%, less than 0.08 wt%, less than 0.05%, less than 0.03%, less than 0.025%, less than 0.01%, less than 0.0075%, less than 0.005%, or less than 0.001%.

[0313] In another embodiment, the carbon material comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of less than 500 ppm and an ash content of less than 0.08% (excluding any intentionally included electrochemical modifiers). In another further embodiment, the carbon material comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of less than 300 ppm and an ash content of less than 0.05% (excluding any intentionally included electrochemical modifiers). In another further embodiment, the carbon material comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of less than 200 ppm and an ash content of less than 0.05% (excluding any intentionally included electrochemical modifiers). In another further embodiment, the carbon material comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of less than 200 ppm and an ash content of less than 0.025% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the carbon material comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of less than 100 ppm and an ash content (excluding any intentionally included electrochemical modifiers) of less than 0.02%. In other further embodiments, the carbon material comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of less than 50 ppm and an ash content (excluding any intentionally included electrochemical modifiers) of less than 0.01%.

[0314] In another embodiment, the composite material comprising the porous silicon material comprises a total TXRF impurity content of all other elements (excluding any electrochemical modifiers intentionally included) of greater than 500 ppm and an ash content (excluding any electrochemical modifiers intentionally included) of greater than 0.08%. In a further embodiment, the composite material comprises a total TXRF impurity content of all other elements (excluding any electrochemical modifiers intentionally included) of greater than 5000 ppm and an ash content (excluding any electrochemical modifiers intentionally included) of greater than 0.5%. In another further embodiment, the composite material comprises a total TXRF impurity content of all other elements (excluding any electrochemical modifiers intentionally included) of greater than 1% and an ash content (excluding any electrochemical modifiers intentionally included) of greater than 0.5%. In another further embodiment, the composite material comprises a total TXRF impurity content of all other elements (excluding any electrochemical modifiers intentionally included) of greater than 2% and an ash content (excluding any electrochemical modifiers intentionally included) of greater than 1%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 3% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 2%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 4% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 3%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 5% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 4%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 6% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 5%.In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 7% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 6%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 8% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 7%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 9% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 8%. In other further embodiments, the composite comprises a total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) of greater than 10% and an ash content (excluding any intentionally included electrochemical modifiers) of greater than 9%.

[0315] The amount of each TXRF impurity present in the disclosed composite material comprising porous silicon material can be measured by proton-induced X-ray emission. Each TXRF impurity can contribute differently to the overall electrochemical performance of the disclosed carbon material. Thus, in some embodiments, the concentration of sodium present in the carbon material is less than 1,000 ppm, less than 500 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, or less than 1 ppm. In some embodiments, the concentration of magnesium present in the composite material is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, or less than 1 ppm. In some embodiments, the concentration of aluminum present in the composite material is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, or less than 1 ppm. In some embodiments, the concentration of silicon present in the composite is less than 500 ppm, less than 300 ppm, less than 100 ppm, less than 50 ppm, less than 20 ppm, less than 10 ppm, less than 1 ppm.In some embodiments, the concentration of phosphorus present in the composite is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, or less than 1 ppm.In some embodiments, the concentration of sulfur present in the composite is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 30 ppm, less than 10 ppm, less than 5 ppm, or less than 1 ppm.In some embodiments, the concentration of chlorine present in the composite is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, or less than 1 ppm. In some embodiments, the concentration of potassium present in the composite is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, or less than 1 ppm. In other embodiments, the concentration of calcium present in the composite is less than 100 ppm, less than 50 ppm, less than 20 ppm, less than 10 ppm, less than 5 ppm, or less than 1 ppm. In some embodiments, the concentration of chromium present in the composite is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm.In other embodiments, the concentration of iron present in the composite is less than 50 ppm, less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm. In other embodiments, the concentration of nickel present in the composite is less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm. In some other embodiments, the concentration of copper present in the composite is less than 140 ppm, less than 100 ppm, less than 40 ppm, less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm. In still other embodiments, the concentration of zinc present in the composite is less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 2 ppm, or less than 1 ppm. In still other embodiments, the sum of all other TXRF impurities (excluding any electrochemical modifiers not intentionally included) present in the composite is less than 1000 ppm, less than 500 ppm, less than 300 ppm, less than 200 ppm, less than 100 ppm, less than 50 ppm, less than 25 ppm, less than 10 ppm, or less than 1 ppm. As noted above, in some embodiments, other impurities, such as hydrogen, oxygen, and / or nitrogen, may be present at concentrations of less than 10% to less than 0.01%.

[0316] In some embodiments, the unmodified composite material comprising porous silicon material comprises undesired TXRF impurities near or below the detection limit of proton induced X-ray emission spectroscopy analysis.For example, in some embodiments, the unmodified composite material contains less than 50 ppm sodium, less than 15 ppm magnesium, less than 10 ppm aluminum, less than 8 ppm silicon, less than 4 ppm phosphorus, less than 3 ppm sulfur, less than 3 ppm chlorine, less than 2 ppm potassium, less than 3 ppm calcium, less than 2 ppm scandium, less than 1 ppm titanium, less than 1 ppm vanadium, less than 0.5 ppm chromium, less than 0.5 ppm manganese, less than 0.5 ppm iron, less than 0.25 ppm cobalt, less than 0.25 ppm zinc ... of nickel, less than 0.25 ppm copper, less than 0.5 ppm zinc, less than 0.5 ppm gallium, less than 0.5 ppm germanium, less than 0.5 ppm arsenic, less than 0.5 ppm selenium, less than 1 ppm bromine, less than 1 ppm rubidium, less than 1.5 ppm strontium, less than 2 ppm yttrium, less than 3 ppm zirconium, less than 2 ppm niobium, less than 4 ppm molybdenum, less than 4 ppm technetium, less than 7 ppm rubidium, less than 6 ppm rhodium, less than 6 ppm palladium, less than 9 ppm silver , less than 6 ppm cadmium, less than 6 ppm indium, less than 5 ppm tin, less than 6 ppm antimony, less than 6 ppm tellurium, less than 5 ppm iodine, less than 4 ppm cesium, less than 4 ppm barium, less than 3 ppm lanthanum, less than 3 ppm cerium, less than 2 ppm praseodymium, less than 2 ppm neodymium, less than 1.5 ppm promethium, less than 1 ppm samarium, less than 1 ppm europium, less than 1 ppm gadolinium, less than 1 ppm terbium, less than 1 ppm dysprosium, less than 1 ppm of holmium, less than 1 ppm erbium, less than 1 ppm thulium, less than 1 ppm ytterbium, less than 1 ppm lutetium, less than 1 ppm hafnium, less than 1 ppm tantalum, less than 1 ppm tungsten, less than 1.5 ppm rhenium, less than 1 ppm osmium, less than 1 ppm iridium, less than 1 ppm platinum, less than 1 ppm silver, less than 1 ppm mercury, less than 1 ppm thallium, less than 1 ppm lead, less than 1.5 ppm bismuth, less than 2 ppm thorium, or less than 4 ppm uranium.

[0317] In some embodiments, the unmodified composite material comprising porous silicon material comprises undesired TXRF impurities that are close to or below the detection limit of proton-induced X-ray emission analysis.For example, in some specific embodiments, the unmodified composite material comprises less than 100ppm sodium, less than 300ppm silicon, less than 50ppm sulfur, less than 100ppm calcium, less than 20ppm iron, less than 10ppm nickel, less than 140ppm copper, less than 5ppm chromium, and less than 5ppm zinc, as measured by TXRF.In other specific embodiments, the unmodified composite material comprises less than 50ppm sodium, less than 30ppm sulfur, less than 100ppm silicon, less than 50ppm calcium, less than 10ppm iron, less than 5ppm nickel, less than 20ppm copper, less than 2ppm chromium, and less than 2ppm zinc.

[0318] In other specific embodiments, the unmodified composite material comprises less than 50 ppm sodium, less than 50 ppm silicon, less than 30 ppm sulfur, less than 10 ppm calcium, less than 2 ppm iron, less than 1 ppm nickel, less than 1 ppm copper, less than 1 ppm chromium, and less than 1 ppm zinc.

[0319] In some other specific embodiments, the unmodified composite material comprises less than 100 ppm sodium, less than 50 ppm magnesium, less than 50 ppm aluminum, less than 10 ppm sulfur, less than 10 ppm chlorine, less than 10 ppm potassium, less than 1 ppm chromium, and less than 1 ppm manganese.

[0320] In certain embodiments, the composite material comprising the porous silicon material comprises carbon and two or more different electrochemical modifiers. In embodiments, the composite material comprises silicon and one or more of the following species (or combinations thereof): phosphorus, nitrogen, sulfur, boron, or aluminum. In certain embodiments, the composite material comprises carbon, silicon, and 1-20% of a Group 13 element, or a combination thereof. In other certain embodiments, the composite material comprises carbon, silicon, and 1-20% of a Group 15 element, or a combination thereof. In other certain embodiments, the composite material comprises carbon, silicon, and 1-20% of a lithium, sodium, or potassium, or a combination thereof. In other certain embodiments, the composite material comprises carbon, silicon, and 1-20% of a lithium, sodium, potassium, or a combination thereof.

[0321] The particle size of the composite material can expand upon lithiation compared to the delithiation state. For example, the expansion coefficient is defined as the average particle size of the composite material comprising the porous silicon material upon lithiation divided by the average particle size under delithiation conditions. As explained in the art, this expansion coefficient can be significantly larger for previously known non-optimal silicon-containing materials, for example, about 4 (corresponding to a 400% volume expansion upon lithiation). The inventors have found composite materials comprising porous silicon materials that can exhibit a lower degree of expansion. For example, the expansion coefficient can vary in the range of 3.5 to 4, 3.0 to 3.5, 2.5 to 3.0, 2.0 to 2.5, 1.5 to 2.0, or 1.0 to 1.5.

[0322] It is understood that the composite material in certain embodiments has a fraction of trapped pore volume, i.e., the ratio of inaccessible void volume to nitrogen gas, as determined by nitrogen gas adsorption measurements. Without wishing to be bound by theory, this trapped pore volume is important in that it provides a volume into which silicon can expand upon lithiation.

[0323] Thus, the composite material can have a ratio of captured pore volume to measured pore volume (as determined by nitrogen gas adsorption) that is between 0.01:1 and 100:1. In certain embodiments, the composite material has a ratio of captured pore volume to measured pore volume between 0.01:1 and 0.05:1. In certain embodiments, the composite material has a ratio of captured pore volume to measured pore volume between 0.05:1 and 0.1:1. In certain embodiments, the composite material has a ratio of captured pore volume to measured pore volume between 0.1:1 and 0.2:1. In certain embodiments, the composite material has a ratio of captured pore volume to measured pore volume between 0.2:1 and 0.5:1. In certain embodiments, the composite material has a ratio of captured pore volume to measured pore volume between 0.5:1 and 1:1. In certain embodiments, the composite material has a ratio of captured pore volume to measured pore volume between 1:1 and 2:1. In certain embodiments, the composite material has a ratio of supplemental pore volume to measured pore volume of 2:1 to 5:1. In certain embodiments, the composite material has a ratio of supplemental pore volume to measured pore volume of 5:1 to 10:1. In certain embodiments, the composite material has a ratio of supplemental pore volume to measured pore volume of 10:1 to 20:1. In certain embodiments, the composite material has a ratio of supplemental pore volume to measured pore volume of 20:1 to 50:1. In certain embodiments, the composite material has a ratio of supplemental pore volume to measured pore volume of 50:1 and 100:1.

[0324] In certain preferred embodiments, the ratio of the supplemental pore volume to the silicon volume constituting the composite particle is 0.1:1 to 10:1. For example, the ratio of the supplemental pore volume to the silicon volume constituting the composite particle is 1:1 to 5:1, or 5:1 to 10:1. In a preferred embodiment, the ratio of the supplemental pore volume to the silicon volume constituting the composite particle is 2:1 to 5:1, or about 3:1, so as to efficiently accommodate the maximum degree of expansion of silicon upon lithiation. EXAMPLES

[0325] Example 1 A novel composite performance model. A full-cell model was developed to simulate the approximate size and energy of an 18650 type cell. LCO was selected as the standard cathode. The model accounts for material properties (density, packing, volume expansion), electrochemical performance characteristics (operating voltage, capacity, irreversible capacity), and cell level changes (electrolyte required, void volume). Table 2 compares the cell level properties from a commercial cell with the output from the model. Similar values ​​were calculated using the model to provide confidence in the model's ability to represent system level changes.

[0326] [Table 2]

[0327] The values ​​in Table 3 then show the change in cell level performance when the anode is modified to include the novel composite material disclosed herein. At the cell level, there is a significant increase (about 43%) in the cantilever energy density, with a limited change in Wh / kg due in part to additional SEI loss. Without wishing to be bound by theory, prelithiation further increases the gravimetric energy density.

[0328] [Table 3]

[0329] Example 2 Examples of porous carbon scaffold materials Various porous carbon scaffold materials were obtained for study. Table 4 lists the physicochemical properties of the carbons.

[0330] Carbon 1 was a commercially available carbon. In addition to the properties reported in Table 2, the Dv100 was 11.62 microns, the Dv10 was 0.6 microns, and the tap density was 0.27 g / cm 3The pH was 5.3, the ash content was 0.016%, and the total impurities detected by PIXE were: calcium = 12.910 ppm, iron = 22.830 ppm, nickel = 3.604 ppm, chromium = 5.521.

[0331] Carbon 2 was a commercially available carbon. In addition to the properties reported in Table 1, the Dv100 was 18.662 microns, the Dv10 was 1.2 microns, the particle size span was 1.194, the uniformity of the particle size distribution was 0.367, and the tap density was 0.2347 g / cm 3 The pH was 6.709, the ash was 0.005%, and the total impurities detected by PIXE were as follows: calcium = 20.5 ppm, iron = 4.14 ppm, zinc = 2.24 ppm, titanium = 6.7 ppm.

[0332] Carbon 3 was a commercially available carbon. In addition to the properties reported in Table 1, the Dv100 was 21.2 microns, the Dv10 was 3.8 microns, the particle size span was 1.261, the uniformity of the particle size distribution was 0.387, and the tap density was 0.52 / cm 3 The pH was 9.418, the ash was 0.075%, and the sum of all impurities detected by PIXE was as follows: iron = 3.183 ppm, zinc = 0.555, potassium = 6.952 ppm.

[0333] Carbon 4 was produced from resorcinol formaldehyde resin as follows. First, deionized water (388 g) was mixed with glacial acetic acid (26 mL) and resorcinol (156 g) in a 1 L beaker. The solution was mixed on a stir plate until all of the resorcinol was dissolved. With continuous mixing of the solution, 2.2 g of ammonium acetate was added and allowed to dissolve. Next, formaldehyde solution (212 mL) (37 wt% formaldehyde in water) was added to the stirred solution. This solution was stirred for 5-10 minutes. The final solution was then poured into a 1 L polypropylene bottle and placed at 85°C for 24 hours. The resulting hardened solid resin was then freeze-dried to remove all excess water, acid and formaldehyde to produce a cryogel, which was then pyrolyzed according to the methods described herein.

[0334] Carbon 5 and Carbon 6 were commercially available carbons.

[0335] Carbon 7 was a commercially available carbon. In addition to the properties reported in Table 1, the Dv100 was 35.2 microns, the Dv10 was 2.69 microns, the particle size span was 1.765, the uniformity of the particle size distribution was 0.539, and the tap density was 1.015-1.020 g / cm. 3 and the pH was 3.9099.

[0336] Carbon 8 was a commercially available carbon.

[0337] Carbon 9 was made from urea citric acid resin as follows: First, pre-dried urea (400 g) was mixed with pre-dried citric acid (200 g). The mixture was then ground into a very fine powder. The powder mixture was poured into a curing vessel and placed at 140° C. for 24 hours. The resulting cured solid resin was then pyrolyzed according to the methods described herein.

[0338] Carbon 10 was a commercially available carbon. In addition to the properties reported in Table 1, the Dv100 was 18.6 microns, the Dv10 was 2.48 microns, the particle size span was 1.348, the uniformity of the particle size distribution was 0.406, and the tap density was 0.32 g / cm 3 and the pH was 7.616.

[0339] Carbon 11 was graphite.

[0340] Carbon 12 was a commercially available carbon. Carbon 13 was commercial carbon 1 heated to 1100 °C for 1 h in 5 mol % H gas in argon.

[0341] Carbon 14 was a hard carbon made in a solvent-free process using polyols and organic acids according to the procedures described herein.

[0342] Carbon 15 was a hard carbon made using an epoxy compound and phosphoric acid according to the procedures described herein.

[0343] [Table 4]

[0344] Example 3 Fabrication of various composite materials by deposition of silicon onto porous silicon scaffolds In this example, a variety of different composites were produced according to the current disclosure. Silicon was embedded within the porous carbon scaffold by chemical vapor deposition techniques using silane gas, as generally described herein. In this particular example, samples were processed in a tube furnace with a 2 mole % silane gas flow mixed with nitrogen gas and held for various times and temperatures as described. A summary of sample processing is provided in Table 5. The final loading of silicon in the silicon carbon composite can be determined as known in the art, for example, from the weight loss observed using thermogravimetric analysis (TGA), a technique known in the art.

[0345] [Table 5]

[0346] [Table 6]

[0347] Example 4 Fabrication of various composite materials via silicon deposition onto a porous silicon scaffold, followed by chemical vapor deposition and the formation of a carbon layer surrounding the particles Some samples from the previous examples were further processed in a tube furnace to form a surface carbon layer by chemical vapor deposition using propane gas at high temperatures and times as noted. The production data is summarized in Table 6.

[0348] [Table 7]

[0349] Example 5 Physicochemical properties of various composite materials The surface area, pore volume and pore volume distribution of the various samples from the above examples were determined by nitrogen adsorption as described in this disclosure. The data are summarized in Table 7.

[0350] [Table 8]

[0351] [Table 9]

[0352] Example 6 Electrochemical properties of various composite materials A variety of composites were prepared in the above examples. The composite samples were examined for their electrochemical properties. Table 8 shows data for materials tested as anodes in half cells, where the anodes consisted of active material, binder, and 60%, 20%, and 20% conductive carbon based on the electrode mass. These samples were assembled into half cells and tested for 5 cycles at a rate of c / 10. The electrochemical test data are summarized in Table 8. Unless otherwise stated, average coulombic efficiency and capacity retention from cycle 7 to cycle 25 are reported, and capacity at cycle 6 is reported.

[0353] [Table 10]

[0354] [Table 11]

[0355] Example 7 Electrochemical characteristics of various composites in blends with graphite. According to the above examples, various composites were prepared. A selected number of samples were examined for their electrochemical properties. Table 9 shows data for materials tested as anodes in half cells. Here, the anodes consisted of active material, binder, and 80%, 10%, and 10% conductive carbon with respect to the electrode mass. The active material further included graphite, and the % of graphite and % of sample were adjusted to achieve an approximate capacity in the range of 500-800 mAh / g. In sample 13, the electrode included 24% sample 13 and 76% graphite. In sample 14, the electrode included 30% sample 14 and 70% graphite. In sample 15, the electrode included 19% sample 15 and 81% graphite. In sample 32, the electrode included 24% sample 32 and 76% graphite. In sample 33, the electrode contained 27% sample 33 and 73% graphite. In sample 35, the electrode contained 24% sample 35 and 76% graphite. In sample 50, the electrode contained 25% sample 35 and 75% graphite. These samples were assembled into half cells and cycled at a rate of C / 10 for 5 cycles and then at C / 5. Electrochemical test data are summarized in Table 8. Unless otherwise stated, average coulombic efficiency and capacity retention from cycle 7 through cycle 25 are reported, and capacity at cycle 6 is reported.

[0356] [Table 12]

[0357] Example 8 Filling the pores of microporous carbon materials by silicon deposition Microporous carbon (Carbon 3) was examined for pore volume distribution before and after silanization for 120 minutes (Sample 31) or 150 minutes (Sample 34) to create a composite containing silicon and carbon. The pore volume distributions for these samples are shown in Figure 2. As can be seen, there is a substantial reduction in pore volume in the micropore range, consistent with the filling of the micropores in the carbon scaffold with silicon.

[0358] Example 9 A carbon with mixed micro-, meso-, and macroporous properties (Carbon 2) was examined for pore volume distribution before and after silanization for 60 minutes (Sample 11) or 90 minutes (Sample 9) to create a composite with silicon and carbon. The pore volume distributions for these samples are shown in Figure 3. As can be seen, there is a substantial reduction in pore volume in the micropore, mesopore, and macropore ranges, consistent with the filling of the micropores, mesopores, and macropores within the carbon scaffold with silicon.

[0359] Example 10 Filling the pores of macroporous carbon materials by silicon deposition The pore volume distribution of a macroporous carbon (carbon 4) was examined before and after silane treatment for 90 minutes (sample 8), or after silane treatment for 90 minutes followed by propane treatment for 30 minutes (sample 10), or after silane treatment for 120 minutes followed by propane treatment for an additional 10 minutes (sample 13) to create a composite containing silicon and carbon. The pore volume distributions of these samples are shown in FIG. 4. As can be seen, there is a substantial reduction in pore volume in the macropore range, consistent with filling of the macropores in the carbon scaffold with silicon. Furthermore, upon subsequent propane treatment (layering of additional carbon on the particle surface), there was a further loss in macropore volume. Without being bound by theory, this observation is consistent with a CVD carbon coating providing capping of the macropores with a concomitant reduction in macropore volume.

[0360] It is therefore understood that the composite material in certain embodiments has a portion of trapped pore volume, i.e., void volume that is inaccessible to nitrogen gas as measured by nitrogen gas adsorption measurements. Without being bound by theory, this trapped pore volume is important in that it provides a volume into which silicon can expand upon lithiation.

[0361] Example 11 Capping off in porous carbon scaffolds by CVD Carbon coated porous materials by thermal chemical vapor deposition cap the micropores rather than filling the pores with carbon. This is best observed by carbon CVD on a purely microporous carbon (carbon 3). As can be seen in the table below, the specific surface area of ​​the material is 1720 m 2 / g is 6m 2 / g. The pore volume is also reduced to negligible values. Evidence of capping is seen in the nitrogen pycnometry data, pellet density and acetone pycnometry. The powder in the die is pressurized at 2000 kg / cm 2 The pellets were measured by compressing at a pressure of 1000 MPa. Acetone pycnometry was measured by immersing the powder in acetone and measuring the displacement of the liquid. The starting apparent skeletal density is 2.24 g / cc for pure microporous carbon. After CVD of carbon on the material, the apparent skeletal density drops to 1.49 g / cc, suggesting the formation of void spaces in the material. The data is summarized in Table 10 and shown graphically in the pore volume distribution in Figure 5.

[0362] [Table 13]

[0363] Example 12 Electrochemical characterization of the composites in full-cell and coin cells The electrochemical performance of the composite sample was tested for the material as an anode containing 80% active material, 10% conductive carbon and 10% binder. The activity further includes 30% of the sample being tested and 70% graphite. Alternatively, the electrochemical performance of the composite sample was tested for an anode containing 80% active material, 10% conductive carbon and 10% binder. Alternatively, the electrochemical performance of the composite sample was tested for an anode containing 90% active material, 5% conductive carbon and 5% binder. Alternatively, the electrochemical performance of the composite sample was tested for an anode containing 90% active material, 2% conductive carbon and 8% binder. Alternatively, the electrochemical performance of the composite sample was tested for an anode containing 93% active material, 2% conductive carbon and 5% binder. Active material in this context includes the sample to be tested, for example silicon carbon composite and graphite, where the active material comprises 10-60% silicon carbon composite and 40-90% graphite.

[0364] Full coin cells were constructed as follows: anodes and cathodes were paired by collecting the absolute 5th cycle insertion (anode) and 1st cycle withdrawal (cathode) capacities of the half cells and matching the electrodes such that an excess anode ratio of 5-15% was satisfied. Coin cells were constructed using a LiNiCoAlO anode. After fabrication, the cells were electrochemically prepared with five charge-discharge sequences from 2.0-4.2 V. The first two sequences were performed at C / 10 current with a C / 20 hold at 4.2 V, and the next three sequences were performed at C / 5 again with a C / 20 hold. For evaluation of cycling stability, the cells were cycled from 2.0-4.2 V at C / 2 with a C / 20 hold.

[0365] Alternatively, cells were electrochemically prepared with two charge-discharge sequences from 2.5-4.2 V. The first sequence was performed at C / 10 current with C / 20 hold, and the subsequent sequence was performed at C / 5 with C / 10 hold. For evaluation of cycling stability, cells were cycled from 2.5-4.2 V at 1 C with C / 2 hold. Some such cells were periodically cycled (at a rate of 1 every 20 cycles) from 2.5-4.2 V at C / 10 with C / 5 hold during the cycling stability phase.

[0366] Example 13 Calculation of the mean free path of adsorbed gas For either 150 pm or 300 pm sized molecules, the mean free path (MFP) was calculated for a variety of different temperatures, pressures and gases according to kinetic gas theory as known in the art (see Table 11). Additional calculations are understood as known in the art.

[0367] [Table 14]

[0368] Example 14 Anodes were made according to the procedures generally described herein. The anode material to be tested is typically diluted with graphite to achieve a range of 400-700 mAh / g. The percentage of graphite in the blend for each sample is listed below, and in such cases the electrode formulation generally consists of 80% active material (material in the graphite blend), 10% conductivity enhancer, e.g., Super P, and 10% binder, e.g., SBR-CMC. In some cases, materials were tested in the absence of graphite, and in such cases typically contained 60% active material, 20% conductivity enhancer, and 20% binder in the anode formulation. In some cases, the anode contained 90% active material, 5% conductivity enhancer, and 5% binder in the anode formulation. The electrodes used were 1M LiPF6EC:DEC+10%FEC with lithium metal as the cathode, and were constructed as half-cell coin cells. The cells were electrochemically tested as generally described herein. The voltage was cycled from 0.8 V to 0.005 V at a C / 10 rate for 5 cycles, followed by 25 cycles at a C / 5 rate. After cycling, the coin cells were brought to 100% charge for a final time, then disassembled and the thickness of the anode was measured, compared to the starting thickness before electrochemical testing. The different types of samples fabricated were graphite-based, carbon composite nanosilicon, carbon composite nanofeatured silicon, carbon composite silicon oxide (SiO x ), as well as a carbon-silicon composite (C-Si-C composite) fabricated via silane deposition onto a porous carbon scaffold, and a final carbon coating achieved via hydrocarbon chemical vapor deposition. Samples were fabricated according to the general procedures described elsewhere herein. Also included are some samples containing bare nanosilicon, not composited with carbon. Unless otherwise stated, any contents, either by weight or volume, refer to the contents of the delithiated material. These samples are summarized in Table 12 below.

[0369] Data showing the relationship between anode expansion and gravimetric capacity for uncomposited (so-called bare) nanosilicon and the same nanosilicon in silicon carbon composite is shown in FIG. 6. As can be seen, the bare material expands dramatically with increasing weight gain in the blend of nanosilicon and graphite. In contrast, when the nanosilicon is composited with carbon, there is a dramatically reduced expansion for the carbon composite nanosilicon blend with graphite. FIG. 7 shows the relationship between anode expansion and gravimetric capacity for various different samples. FIG. 8 shows data for anode expansion versus volumetric capacity (in the delithiated state). Carbon composite nanosilicon sample, carbon composite nanofeatured silicon sample, carbon composite silicon oxide (SiO x All of the 100% SiO2 (C-Si-C) samples showed similar expansion and increased gravimetric capacity in their respective blends with graphite. In contrast, a surprising and unexpected finding was the dramatically lower expansion for the sample (C-Si-C) containing a carbon-silicon composite fabricated by silane deposition onto a porous carbon scaffold with a final carbon coating formed via hydrocarbon chemical vapor deposition.

[0370] [Table 15]

[0371] Without being bound by theory, the low expansion of the C-Si-C samples translates into a reduced tendency of the material to crack due to unstable SEI formation upon cycling in the battery. From the data, it is understood that the C-Si-C composites can exhibit less than 30% anode expansion and greater than 400 mAh / g gravimetric capacity when blended with, for example, graphite or other suitable matrix, or when tested as pure materials. In certain embodiments, the C-Si-C composites can exhibit less than 30% anode expansion and greater than 500 mAh / g gravimetric capacity. In certain embodiments, the C-Si-C composites can exhibit less than 30% anode expansion and greater than 600 mAh / g gravimetric capacity. In certain embodiments, the C-Si-C composites can exhibit less than 30% anode expansion and greater than 800 mAh / g gravimetric capacity. In certain embodiments, the C-Si-C composites can exhibit less than 30% anode expansion and greater than 1000 mAh / g gravimetric capacity.

[0372] In further embodiments, the C-Si-C composites can exhibit less than 40% anode expansion and greater than 500 mAh / g gravimetric capacity, for example when blended with graphite or other suitable matrix, or when tested as pure materials. In further embodiments, the C-Si-C composites can exhibit less than 40% anode expansion and greater than 600 mAh / g gravimetric capacity. In further embodiments, the C-Si-C composites can exhibit less than 40% anode expansion and greater than 800 mAh / g gravimetric capacity. In further embodiments, the C-Si-C composites can exhibit less than 40% anode expansion and greater than 1000 mAh / g gravimetric capacity.

[0373] In other embodiments, C-Si-C composites can exhibit, for example, less than 50% anode expansion and greater than 800 mAh / g gravimetric capacity when blended with graphite or other suitable matrix or when tested as a pure material. In other embodiments, C-Si-C composites can exhibit, for example, less than 60% anode expansion and greater than 1000 mAh / g gravimetric capacity when blended with graphite or other suitable matrix or when tested as a pure material.

[0374] In some embodiments, the C-Si-C composites can exhibit less than 20% anode expansion and greater than 500 mAh / g gravimetric capacity, for example when blended with graphite or other suitable matrix, or when tested as pure materials. In further embodiments, the C-Si-C composites can exhibit less than 20% anode expansion and greater than 600 mAh / g gravimetric capacity. In further embodiments, the C-Si-C composites can exhibit less than 20% anode expansion and greater than 800 mAh / g gravimetric capacity. In further embodiments, the C-Si-C composites can exhibit less than 20% anode expansion and greater than 1000 mAh / g gravimetric capacity.

[0375] FIG. 8 shows data on the relationship between the expansion and volumetric capacity of the samples. As can be seen, the carbon composite nanosilicon sample, the carbon composite nanofeature silicon sample, and the carbon composite silicon oxide (SiO x ) all exhibited similar expansion and increased volumetric capacity in their respective blends with graphite. A surprising and unexpected finding was that the C-Si-C samples exhibited a highly flat dependence of expansion on volumetric capacity.

[0376] Without being bound by theory, the low expansion of the C-Si-C samples is interpreted as a reduced tendency of the material to crack due to unstable SEI formation during cycling in the battery. The data show that the C-Si-C composites exhibited anode expansion of less than 30% and anode expansion of 400 mAh / cm when blended with, for example, graphite or other suitable matrices, or when tested as pure materials. 3 It is understood that the C-Si-C composite can exhibit anode expansion of less than 30% and volumetric capacity of more than 500 mAh / cm. 3 In certain embodiments, the C—Si—C composites can exhibit anode expansion of less than 30% and volumetric capacity of more than 600 mAh / cm 3 In certain embodiments, the C—Si—C composites can exhibit an anode expansion of less than 30% and a volumetric capacity of 800 mAh / cm 3 In certain embodiments, the C—Si—C composites can exhibit an anode expansion of less than 30% and a volumetric capacity of more than 1000 mAh / cm 3 It can exhibit a volumetric capacity of over 10 ...

[0377] In a further embodiment, the C-Si-C composite has an anode expansion of less than 40% and a capacitance of 400 mAh / cm, for example, when blended with graphite or other suitable matrix or when tested as a pure material. 3 In some embodiments, the C—Si—C composites can exhibit an anode expansion of less than 40% and a volumetric capacity of more than 500 mAh / cm 3 In some embodiments, the C—Si—C composites can exhibit an anode expansion of less than 40% and a volumetric capacity of more than 600 mAh / cm 3 In some embodiments, the C—Si—C composites can exhibit an anode expansion of less than 40% and a volumetric capacity of 800 mAh / cm 3 In some embodiments, the C—Si—C composites can exhibit an anode expansion of less than 40% and a volumetric capacity of more than 1000 mAh / cm 3 It can exhibit a volumetric capacity of over 10 ...

[0378] In other embodiments, C-Si-C composites can exhibit, for example, less than 50% anode expansion and 400 mAh / cm when blended with graphite or other suitable matrix or when tested as pure materials. 3 In some embodiments, the C—Si—C composites can exhibit less than 50% anode expansion and a volumetric capacity of more than 500 mAh / cm. 3 In some embodiments, the C—Si—C composites can exhibit less than 50% anode expansion and a volumetric capacity of over 600 mAh / cm. 3 In some embodiments, the C—Si—C composites can exhibit an anode expansion of less than 40% and a volumetric capacity of 800 mAh / cm 3 In some embodiments, the C—Si—C composites can exhibit an anode expansion of less than 40% and a volumetric capacity of more than 1000 mAh / cm 3 It can exhibit a volumetric capacity of over 10 ...

[0379] Example 15 Cycling data for various samples in Li-ion full cells Graphite, carbon composite nanosilicon sample, carbon composite silicon oxide (SiO x Full-coin cells were fabricated for the 1000-nm C-Si-C sample and for a sample containing a carbon-silicon composite fabricated by silane deposition on a porous carbon scaffold followed by a final carbon coating achieved via hydrocarbon chemical vapor deposition (C-Si-C). The cathode material was NCA and the electrolyte was 1M LiPF6EC:DEC+10%FEC. The anode capacity was approximately 650 mAh / g as measured in a half cell. Cycling was performed at a rate of C / 2 with a voltage window of 2.0-4.2 V and I / 2 maintenance. Figure 9 shows the cycling stability data in terms of Wh / L relative to the average data for graphite. The coulombic efficiency of the C-Si-C sample was 0.999 ± 0.0016 (N=5 cells).

[0380] Example 16 Filling the pores of mixed micro- and meso-porous carbon materials by silicon deposition To create a composite material containing silicon and carbon, a carbon with both micropores and mesopores (carbon 13) was examined for pore volume distribution before and after treatment with 2 mol% silane flowing at 380 sccm and 450° C. for 60 or 120 minutes. The pore volume distributions for these samples are shown in FIG. 10. There was a substantial reduction in pore volume in the micropore and mesopore ranges consistent with filling of the micropores and filling of the mesopores. The data show a more pronounced reduction in the micropores compared to the reduction in the mesopores, indicating preferential deposition of silicon that favors the reduction of the mesopores over the micropores.

[0381] The same conclusion can be drawn by examining the pore volume distribution data of the various samples. The measured pore volume distribution of the porous carbon scaffold had 41% silicon loading on the porous scaffold with 48% micropores, 52% mesopores and 0% macropores. The measured pore volume distribution of the 60 min silane treated sample resulted in 26% silicon loading on the porous scaffold with 45% micropores, 54% mesopores and 1% macropores. These values ​​are very similar to the starting scaffold. In contrast, the measured pore volume distribution of the 120 min silane treated sample resulted in 41% silicon loading on the porous scaffold with 5% micropores, 45% mesopores and 50% macropores. In terms of percent reduction, the micropore volume of the 60 minute silane treated sample, which gave a 26% silicon loading on the porous scaffold, showed a 58% reduction in micropore volume compared to the starting scaffold, and a 79% reduction in micropore volume compared to the starting scaffold. In terms of percent reduction, the micropore volume of the 120 minute silane treated sample, which gave a 41% silicon loading on the porous scaffold, showed a 100% reduction in micropore volume compared to the starting scaffold, and a 99% reduction in micropore volume compared to the starting scaffold.

[0382] Example 17 Pycnometry data indicating capping of micropores within microporous carbon scaffolds by hydrocarbon CVD The microporous carbon scaffold material was generally treated by hydrocarbon CVD according to the methods described herein. Prior to the hydrocarbon CVD treatment, the measured surface area, pore volume and density by pycnometry were 1744 m 2 / g, 0.72cm 3 / g, 2.24g / cm 3 After the hydrocarbon CVD treatment, the measured surface area, pore volume, and pycnometric density were 6 m 2 / g, 0.701cm 3 / g, 1.49g / cm 3 Without being bound by theory, the dramatically lower surface area and pore volume, together with the dramatically reduced skeletal density, are consistent with capping of the carbon micropores. Thus, hydrocarbon processing or equivalent methods known in the art are suitable for capping carbon pores, the carbon pores filled with silicon deposited according to the principles generally described herein. Without being bound by theory, such capping allows the internal voids within the particles to accommodate the expansion of silicon while minimizing the expansion of the particle envelope volume.

[0383] Example 18 Effect of porous carbon scaffold particle size on silane deposition and electrochemical performance of the resulting silicon-carbon scaffolds A variety of pyrolytic carbons with different particle sizes and mixed micropores and mesopores were tested for their silicon deposition via silane gas, as generally described herein. Samples include carbons that are granular (up to 1 mm or greater) and particles that have been size reduced using a FRITSCH planetary mill (FM) or a jet mill (JM). The data are summarized in Table 13 and include electrochemical testing in half cells, as generally described herein.

[0384] [Table 16]

[0385] As can be seen, all of the carbon scaffold particles were tested, ranging from Dv50 greater than 1 mm to about 4 μm, and all were capable of incorporating silicon by the silane attachment technique. There was a notable trend for improved electrochemical performance (e.g., higher FCE and higher average CE) with decreasing carbon scaffold particle size. Without being bound by theory, further reductions in carbon particle size, such as Dv50 of 2-5 μm, or Dv50 of 2 μm-3 μm, Dv50 of 1 μm and 3 μm, or Dv50 of 1 μm and 2 μm, would be beneficial as well. Alternatively, it is understood that the Dv50 of the carbon scaffold exhibits superior properties for the carbon scaffold particles of the present invention exhibiting a Dv50 of less than 1 μm, and techniques to achieve this are known in the art. For example, the carbon scaffold particle size can be 0.1 μm-1 μm, such as 0.2 μm-0.8 μm, such as 0.4 μm-0.6 μm.

[0386] Example 19 Silicon deposition by silane decomposition on macroporous carbon scaffolds and electrochemical performance of the resulting silicon-carbon composites A variety of different macroporous carbon scaffolds were treated with silane to produce silicon carbon composites as generally described herein. The data are shown in Table 14 and include electrochemical testing in half cells as generally described herein.

[0387] [Table 17]

[0388] As can be seen, the macroporous carbon scaffolds could be processed into silicon carbon composites via the silane treatment generally described herein. However, the electrochemical properties of silicon carbon composites made from macroporous carbon scaffolds give relatively low first cycle efficiencies and low average CEs compared to similar silicon carbon composites made from mesoporous, microporous or mixed microporous and mesoporous carbon scaffolds as presented elsewhere herein.

[0389] Example 20 Silicon deposition on mixed microporous and mesoporous carbon scaffolds by silane decomposition and electrochemical performance of the resulting silicon carbon composites A variety of different carbon scaffolds having micropores and mesopores were treated with silane to produce silicon carbon composites, as generally described herein. The data are shown in Table 15 and include electrochemical testing in half cells, as generally described herein.

[0390] [Table 18]

[0391] As can be seen, carbon scaffolds having micropores and mesopores could be processed into silicon carbon composites via silane treatment as generally described herein. Importantly, the electrochemical properties of silicon carbon composites made from carbon scaffolds having micropores and mesopores generally gave higher average CE compared to similar silicon carbon composites made from macroporous carbon scaffolds.

[0392] Example 21 Effect of pyrolysis temperature of carbon scaffold on silane decomposition and electrochemical performance of the resulting silicon carbon composites Carbon scaffolds with micropores and mesopores were pyrolyzed at various temperatures and tested for silicon deposition via silane gas, as generally described herein. Samples included carbon pyrolyzed at temperatures ranging from 500°C to 1100°C. Data are presented in Table 16 and include electrochemical testing in half cells, as generally described herein.

[0393] [Table 19]

[0394] As can be seen, the carbon scaffolds with micropores and mesopores could be processed into silicon carbon composites via silane treatment at various temperatures as generally described herein. However, the samples pyrolyzed at 500°C were found to be brown in color and not suitable for processing into electrodes for subsequent electrochemical testing. Importantly, the electrochemical properties of silicon carbon composites made from the carbon scaffolds with micropores and mesopores pyrolyzed at various temperatures showed higher average CE with increasing pyrolysis temperature. Higher pyrolysis temperature also provides for improved capacity retention (see FIG. 11).

[0395] Without being bound by theory, it is understood that higher pyrolysis temperatures provide further improved electrochemical performance of silicon carbon composites, and higher pyrolysis temperatures can be implemented as known in the art. For example, preferred carbon scaffold pyrolysis temperatures can be greater than 800° C., such as in the range of 800-1200° C. Alternatively, the pyrolysis temperature can be 900-1300° C., or 1000-1400° C., or 1100-1500° C., or 1200-1600° C., or 1300-1700° C. In some embodiments, the carbon scaffold pyrolysis temperature can be greater than 1700° C.

[0396] Example 22 The effects of different treatments on porous carbon and its impact on its suitability as a scaffold for fabricating silicon carbon composites Porous carbon scaffolds with mixed micro- and mesopore structures were subjected to various treatments. These treatments included heating in the presence of nitrogen at 1100, 1300, 1500 and 1700°C, heating in the presence of hydrogen gas at 1100°C, heating in the presence of ammonia gas at 900°C, or heating in the presence of N2 at 1300°C followed by ...

Claims

1. A composite comprising a porous carbon scaffold and silicon, The composite contains 15-85% silicon by weight and 0.05-0.5 cm 3 / g range of nitrogen inaccessible volume, The composite has a density of 1.5-2.2 g / cm as measured by helium pycnometry. 3 A composite comprising a plurality of particles having a particle skeletal density in the range of

2. The nitrogen inaccessible volume is 0.2-0.4 cm 3 The composite of claim 1, wherein the molecular weight is in the range of 1 / g.

3. The nitrogen inaccessible volume is 0.1-0.3 cm 3 The composite of claim 1, wherein the molecular weight is in the range of 1 / g.

4. Skeletal density is 1.9 to 2.2 g / cm 3 The complex of claim 1, wherein the range is

5. Skeletal density is 1.5 to 1.8 g / cm 3 The complex of claim 1, wherein the range is

6. 1.0~1.5g / cm 3 10. The composite of claim 1 having a pellet density in the range of

7. The composite has less than 10% micropores, more than 30% mesopores, more than 30% macropores, and less than 0.1 cm pores as determined by nitrogen adsorption. 3 13. The composite of claim 1 having a pore structure with a total pore volume of less than 1 / g.

8. The composite has 30-60% micropores, 30-60% mesopores, less than 10% macropores, and a pore size of less than 0.1 cm as determined by nitrogen adsorption. 3 13. The composite of claim 1, having a pore structure with a total pore volume of less than 1 / g.

9. The composite has less than 20% micropores, more than 60% mesopores, less than 30% macropores, and less than 0.1 cm 2 as determined by nitrogen adsorption. 3 13. The composite of claim 1 having a pore structure with a total pore volume of less than 1 / g.

10. The porous carbon scaffolds have 30-60% micropores, 30-60% mesopores, less than 10% macropores, and 0.1-0.5 cm2 pores as determined by nitrogen adsorption. 3 13. The composite of claim 1 having a pore structure with a total pore volume of less than 1 / g.

11. The porous carbon scaffold has 40-60% micropores, 40-60% mesopores, less than 1% macropores, and 0.1-0.5 cm2 porous structures as determined by nitrogen adsorption. 3 13. The composite of claim 1 having a pore structure with a total pore volume of less than 1 / g.

12. Particle skeleton density is 1.5 to 1.8 g / cm 3 The complex of claim 1, wherein the range is

13. 2. The composite of claim 1, wherein the porous carbon scaffold has 10-50% of the pores with a diameter of 50-200A and 90% or more of the pores with a diameter less than 200A.

14. 2. The composite of claim 1, wherein the silicon content ranges from 25% to 65%.

15. 2. The composite of claim 1, wherein the silicon content is in the range of 35% to 45%.

16. 2. The composite of claim 1 having a ratio of carbon scaffold pore volume to silicon volume that is from 0.3:1 to 1:

1.

17. 2. The composite of claim 1 having a ratio of nitrogen inaccessible pore volume to silicon volume that is from 0.3:1 to 1:

1.

18. 10. The composite of claim 1 having an average particle size of less than 5 microns.

19. 20. The composite of claim 18 having an average particle size of less than 1 micron.

20. 10. The composite of claim 1 comprising a plurality of particles, each particle having a surface layer of carbon.

21. 21. The composite of claim 20, wherein the surface layer of carbon is 1-20% of the total mass of the particle.

22. 21. The composite of claim 20, wherein the surface layer of carbon is 2-10% of the total mass of the particle.

23. 21. The composite of claim 20, wherein the surface layer of carbon comprises a pyrolyzed or partially pyrolyzed conductive polymer material.

24. 24. The composite of claim 23, wherein the conductive polymer material comprises polyacrylonitrile or poly(3,4-ethylenedioxythiophene).

25. 21. The composite of claim 20, wherein the surface layer of carbon comprises graphitizable carbon.

26. The composite of claim 1 further comprising a metal.

27. 27. The composite of claim 26, wherein the metal is aluminum, nickel or manganese.

28. 10. The composite of claim 1, wherein the particles of the composite have an average expansion upon lithiation in the range of 10 to 100%, as determined by in situ TEM.

29. 29. The composite of claim 28, having an average expansion in the range of 10 to 50%.

30. 30. The composite of claim 29, having an average expansion in the range of 20-30%.

31. 10. The complex of claim 1, wherein the complex comprises a plurality of particles having an average diameter of less than 50 nm as determined by sequential TEM.

32. An electrode comprising the composite of any one of claims 1 to 31.

33. 33. The electrode of claim 32, wherein the electrode is an anode.

34. An energy storage device comprising a composite according to any one of claims 1 to 31 or an electrode according to claim 32 or 33.

35. 35. The energy storage device of claim 34, wherein the device is a lithium ion battery.

36. 1. An electrode comprising a carbon-silicon composite, The electrode is 250 to 350 mAh / cm 3 and a swelling of less than 40%.

37. 37. The electrode of claim 36 having an expansion of less than 30%.

38. 1. An electrode comprising a carbon-silicon composite, The electrode is 350 to 450 mAh / cm 3 and swelling of less than 60%.

39. 40. The electrode of claim 38 having an expansion of less than 40%.

40. 1. An electrode comprising a carbon-silicon composite, The electrode is 450 to 600 mAh / cm 3 and a volumetric capacity at full lithiation in the range of 0.1 to 100% and a swelling of less than 100%.

41. 41. The electrode of claim 40 having an expansion of less than 80%.

42. 1. An electrode comprising a carbon-silicon composite, The electrode has a capacity retention rate of 100% or more over at least 100 charge / discharge cycles.

43. 1. An electrode comprising a carbon-silicon composite, the anode has a gravimetric capacity of greater than 400 mAh / g, based on the mass of the anode electrode, for at least 500 charge / discharge cycles when tested in a lithium ion full cell; The anode is not prelithiated; The full cell is a LiNi battery with an anode:cathode capacity ratio of 1.05 to 1.

15. 0.8 Co 0.15 A 0.05 O 2 and a cathode containing 1M LiPF in a 2:1 (w:w) ethylene carbonate:diethyl carbonate solvent containing 10% (w / w) fluoroethylene carbonate. 6 and an electrolyte comprising The full cells are tested at 25° C. at voltages between 4.2 and 2.5 V with a symmetric charge / discharge current density corresponding to C / 10 for the first cycle, followed by 20 cycles with a symmetric charge / discharge current density corresponding to 1C, and then every 20 cycles thereafter with a symmetric charge / discharge current density corresponding to C / 10; After each charge the voltage is maintained at 4.2 V until the current reaches half the symmetric charging current.

44. 1. An electrode comprising a carbon-silicon composite, Over at least 500 charge / discharge cycles, the electrode has a gravimetric capacity, based on the mass of the electrode, of greater than 600 mAh / g.

45. 1. An electrode comprising a carbon-silicon composite, When tested in a half cell at a cycle rate of 2C, the electrode has a gravimetric capacity of over 400 mAh / g.

46. 46. ​​The electrode of claim 45, having a gravimetric capacity of greater than 600 mAh / g.

47. 46. ​​The electrode of claim 45, having a gravimetric capacity of greater than 800 mAh / g.

48. 46. ​​The electrode of claim 45, which exhibits a gravimetric capacity loss of 80% or less after 100 or more charge-discharge cycles.

49. 1. An electrode comprising a carbon-silicon composite, The electrode has a density of at least 1.2 g / cm 3 and a gravimetric capacity of greater than 400 mAh / g for at least 500 charge / discharge cycles.

50. The density is at least 1.3 g / cm 3 50. The electrode of claim 49,

51. The density is at least 1.4 g / cm 3 50. The electrode of claim 49,

52. The density is at least 1.5 g / cm 3 50. The electrode of claim 49,

53. 1. An electrode comprising a carbon-silicon composite, The electrode has a gravimetric capacity, based on the total mass of the electrode, that is greater than the gravimetric capacity of a corresponding graphite electrode for at least 400 charge / discharge cycles.

54. 1. An electrode comprising a carbon-silicon composite, The electrodes have an expansion upon lithiation in the range of 10-100%, as determined by in situ TEM.

55. 55. The electrode of claim 54, wherein the expansion is in the range of 10 to 50%.

56. 55. The electrode of claim 54, wherein the expansion is in the range of 20-30%.

57. The electrode according to any one of claims 36 to 56, wherein the electrode is an anode.

58. 57. An electrode according to any one of claims 36 to 56, wherein the carbon-silicon composite comprises a composite according to any one of claims 1 to 31.

59. 57. The electrode of any one of claims 36 to 56, wherein the electrode comprises an electronically and / or ionically conductive binder.

60. 60. The electrode of claim 59, wherein the binder is a conductive polymer or a partially pyrolyzed form thereof.

61. 100-2000m 2 / g of surface area and total pore volume, A carbon material having less than 10% of its pore volume in micropores, more than 80% of its pore volume in mesopores, and less than 5% of its pore volume in macropores.

62. 62. The carbon material of claim 61, wherein 90% or more of the pore volume is present in mesopores.

63. 62. The carbon material of claim 61, wherein less than 5% of the pore volume is in micropores.

64. 62. The carbon material of claim 61, wherein less than 5% of the pore volume is in macropores.

65. 100-1000m 2 62. The carbon material of claim 61 having a surface area of ​​1 / g.

66. 100 to 500 m 2 62. The carbon material of claim 61 having a surface area of ​​1 / g.

67. A method for producing a composite comprising a porous scaffold material and silicon, comprising the steps of: a) making a porous scaffold material, the porous scaffold material having 10-50% of pores with a diameter of 50-200A and more than 90% of pores with a diameter less than 200A; b) impregnating the porous scaffold with silicon to obtain a silicon-impregnated scaffold. The manufacturing method comprising the steps of:

68. A method for producing a composite material comprising a porous carbon scaffold and silicon, comprising the steps of: a. mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b. carbonizing the resulting polymeric material to obtain a porous carbon material having 10-50% of pores with a diameter of 50-200A and more than 90% of pores with a diameter of less than 200A; and c) subjecting the porous carbon material to high temperature in the presence of a silicon-containing gas to obtain a silicon-impregnated carbon material. A method for producing a composite material having the following structure:

69. A method for producing a composite material comprising a porous carbon scaffold and silicon, comprising the steps of: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material having 10-50% of pores with a diameter of 50-200A and more than 90% of pores with a diameter less than 200A; c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to form a silicon-impregnated carbon material; and d) applying a carbon layer onto the silicon-impregnated carbon material to obtain a carbon-coated silicon-impregnated carbon material. A method for producing a composite material having the following structure:

70. A method for producing a composite material comprising a porous carbon scaffold and silicon, comprising the steps of: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material having 10-50% of pores with a diameter of 50-200A and more than 90% of pores with a diameter less than 200A; c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to form a silicon-impregnated carbon material; and d) applying a conductive polymer around the silicon impregnated carbon material to produce a silicon impregnated carbon material embedded within a conductive polymer network. A method for producing a composite material having the following structure:

71. A method for producing a composite material comprising a porous carbon scaffold and silicon, comprising the steps of: a) mixing and storing polymer precursor materials at a temperature and for a time sufficient to permit polymerization of the precursors; b) carbonizing the resulting polymeric material to produce a porous carbon material having 10-50% of pores with a diameter of 50-200A and more than 90% of pores with a diameter less than 200A; c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to form a silicon-impregnated carbon material; and d) applying a carbon layer onto the silicon-impregnated carbon material to obtain a carbon-coated silicon-impregnated carbon material. e) applying a conductive polymer around the carbon coated silicon impregnated carbon material to produce a carbon coated silicon impregnated carbon material embedded within a conductive polymer network. A method for producing a composite material having the following structure:

72. A method according to any one of claims 67 to 71, in which the deposition of silicon is carried out by treatment in a reactor at a temperature between 300 and 600°C in the presence of a silicon-containing gas.

73. 73. The method of claim 72, wherein the silicon-containing gas and the reactor are a tubular furnace, a fluidized bed reactor, a rotary kiln reactor, an elevator kiln, or a roller hearth kiln.

74. 73. The method of claim 72, wherein the silicon-containing gas is silane, dichlorosilane, trichlorosilane, or tetrachlorosilane.

75. 73. The method of claim 72, wherein the silicon-containing gas is a silane.

76. 72. A method according to claim 69 or claim 71, wherein applying the carbon layer according to step (d) is carried out by chemical vapour deposition in a reactor at elevated temperature in the presence of organic gases.

77. 77. The method of claim 76, wherein the organic gas is methane, ethane, propane or butane and the temperature is from 500 to 900°C.

78. 78. The method of claim 77, wherein the organic gas is propane and the temperature is between 750 and 850°C.

79. 79. The method of any one of claims 67 to 78, further comprising contacting the porous carbon material or porous scaffold with a catalyst prior to producing the silicon impregnated scaffold material or silicon impregnated carbon material.

80. 80. The method of claim 79, wherein the catalyst is a metal.

81. 81. The method of claim 80, wherein the metal is aluminum, nickel or manganese.

82. A method according to any one of claims 67 to 81, wherein the composite material is a composite according to any one of claims 1 to 31.

Citation Information

Patent Citations

  • Electrochemical electric energy storage device and its manufacturing method

    JP2006059558A

  • Porous carbon material, its manufacturing process and adsorbent, mask, adsorption sheet, and supporting member

    JP2008273816A

  • Nanostructured silicon-carbon composite materials for battery electrodes

    JP2012533498A